Physicochemical Changes, Bioactive Compound Dynamics, and Proteomic Remodeling During Ligustrum sp. Fruit Development - Gilson Gustavo Lucinda Machado; Elda Eller; Ana Beatriz Silva Araújo; Camila Giovana Carvalho Souza; Cháid Acácio António Mussalafo; Carlos Alexandre Rocha da Costa; Sidney Vasconcelos do Nascimento; Sayure Mariana Raad Nahon; Alice de Paula de Sousa Cavalcante; Isa Rebecca Chagas da Costa; Rafael Borges da Silva Valadares; Elisângela Elena Nunes Carvalho; et al. (Plant Molecular Biology Reporter, 2026)

Normalizing eye-tracking metrics: Correcting area bias in visual attention studies - Alexandre Henrique Silas Souza; Katiúcia Alves Amorim; Louise Paiva Passos; Jéssica Sousa Guimarães; André Pimenta Freire; Cleiton Antonio Nunes; Ana Carla Marques Pinheiro (Food Quality and Preference, 2026)

The biogeographic ignorance in the distribution of South American goliath catfish - Ana Karolina Mendes Moreno; Geiziane Tessarolo; José Alexandre Felizola Diniz-Filho; Lisiane Hahn; Lucas Jardim; Fabrício Barreto Teresa; Guilherme Rogie Gonçalves Tavares; Laura Barreto de Paula-Souza; Levi Carina Terribile (Reviews in Fish Biology and Fisheries, 2026)
Biodiversity conservation is challenged not only by the lack of knowledge about species distributions but also by an often-overlooked factor: the unquantifiable uncertainty in the quality and reliability of the data used for decision-making. This challenge is intensified for migratory and overexploited species, such as the goliath catfish Brachyplatystoma filamentosum (‘piraíba’), where management decisions based on data of uncertain reliability can lead to management failures and intensify population declines. Thus, our goal here was to generate Maps of Biogeographic Ignorance (MoBIs) for B. filamentosum based on inventory completeness, taxonomic quality, temporal data decay, and environmental-spatial distance to sub-basins with information, in order to quantify the uncertainty associated with species occurrence data. The MoBIs revealed high spatial heterogeneity in species knowledge. The most comprehensive and recent inventories were concentrated along the main channels of the major river of the Amazon basin, in contrast to the high level of ignorance found in Orinoco, and North Atlantic basins. We also combined these MoBIs with environmental suitability predictions derived from species distribution models. The bivariate maps allowed us to identify sub-basins where high predicted suitability coincides with low ignorance (such as along the main Amazon River), as well as those with high suitability but high ignorance (such as in the western Amazon, the upper Orinoco, and the North Atlantic regions). By quantifying and spatially mapping the quality of occurrence data, our study provides an basis for optimizing research, conservation, and management strategies for this goliath catfish. Graphical Abstract

Genetic deletion of MrgD receptor disrupts cardiac protein homeostasis in mice - Beatriz Alexandre-Santos; Luiza Mazzali Ferraz; Ana Beatriz Proença; Nícia Pedreira Soares; Guilherme dos Santos Reis; Maria Eduarda Lima da Silva; D’Angelo Carlo Magliano; Maria Jose Campagnole-Santos; Antonio Claudio Lucas da Nóbrega; Robson Augusto Souza Santos; Eliete Dalla Corte Frantz (Molecular Biology Reports, 2026)
Background Cardiovascular diseases are the leading cause of death worldwide. An important mechanism involved is the disruption in protein homeostasis by overactivation of the classical axis of the renin-angiotensin system. The counterregulatory axis counteracts these effects; however, the MrgD receptor has recently been described, and its effects are unknown. Thus, this study aims to evaluate the impact of MrgD deficiency on cardiac protein homeostasis. Methods 16-week-old wild-type (WT) and MrgD knockout (MrgD KO) male C57BL/6J mice were evaluated for systolic blood pressure (SBP), cardiac morphology, MDA levels, carbonyl content, and protein homeostasis markers. Results SBP and heart mass remained unaltered. MrgD deficiency increased left ventricular mass and led to cardiac atrophy by reduced left ventricular wall thickness and cardiomyocyte cross-sectional area. Collagen (types 1 and 3) deposition and MMP-2 cardiac protein expression were elevated in MrgD KO. Genetic deletion of MrgD increased NOX2, NOX4, and ERO1α cardiac protein expression. MDA levels were similar between groups, and carbonyl content was higher in MrgD KO. GRP78, CHOP, MuRF-1, Atrogin-1, and polyubiquitinated proteins were increased in MrgD KO mice, indicating a loss of protein homeostasis. Conclusions The genetic deletion of MrgD promoted cardiac remodeling and disrupted protein homeostasis, with increased pro-oxidative response and ER stress. This was associated with protein degradation by the activation of the ubiquitin-proteasome pathway.

Salience Network Dynamics Across Spontaneous Attacks, Interictal Rest and Interictal Pain Imagery in Menstrually Related Migraine - Inês Esteves; Alexandre Perdigão; Ana R. Fouto; Amparo Ruiz-Tagle; Gina Caetano; Joana Cabral; Isabel Pavão Martins; Raquel Gil-Gouveia; César Caballero-Gaudes; Patrícia Figueiredo (Brain Topography, 2026)

Modulation of the physicochemical and functional properties of pea and faba bean protein isolates by high-intensity ultrasound and enzymatic hydrolysis - Ana Claudia Silveira Alexandre; Cassia Galves; Andrea K. Stone; Yineth Ruiz Garcia; Yuk Chu Lui; Supratim Ghosh; Takuji Tanaka; Michael T. Nickerson (Food Hydrocolloids, 2026)

Spatial mapping of Notch signaling components along the bull genital tract and in epididymal and vas deferens vesicles - Patrícia Diniz; Inês Leites; Graça Alexandre-Pires; Ana Catarina Torres; Luísa Mateus; Luís Lopes-da-Costa; Elisabete Silva (Animal Reproduction Science, 2026)

Cytogenotoxic effects of Artocarpus heterophyllus Lam. leaf extracts: implications for the safe use of medicinal plants - Ellen Borges da Rocha; Renata Gomes Gonçalves; Brenda Christie Castro de Oliveira; Alexia Barreto da Silveira; Ana Beatriz Franco de Jesus; Luiz Carnevale Eberhardt; Débora Moura Peixoto; Brena Guerra Paixão; Matheus de Lima Rodrigues; Alexandre Felipe de Araújo Desidério; Dayana Palmeira da Silva Rosa; Helena Regina Pinto Lima; et al. (South African Journal of Botany, 2026)

Phenylmercury induces structural and functional alterations on hemoglobin: From isolated protein to a biological model - Sheila Oliveira de Souza; Marcos Vinicius dos Santos Sales; Maiara Ingrid Cavalcante Queiroz; Ana Flávia Silva Lima; Wallison dos Santos Dias; Laís Farias Azevedo de Magalhães Oliveira; Josefa Gerlane Silva; Júlio Cosme Santos da Silva; Eduardo Jorge da Silva Fonseca; Letícia Anderson; Alexandre Urban Borbely; Rafael David Souto de Azevedo; et al. (Journal of Hazardous Materials, 2026)

Sex-specific effects of therapeutic hypothermia on short- and long-term microglial and astrocytic reactivity after severe neonatal hypoxia–ischemia - Ricardo Ribeiro Nunes; João Vitor Miotto Tauffer; Bianca Büchele Martins; Isadora D’Ávila Tassinari; Carlos Alexandre Netto; Ana Helena Paz; Luciano Stürmer de Fraga (Metabolic Brain Disease, 2026)

First Report of Mansonella sp. Microfilariae in Sapajus nigritus: Insights into the Host-Parasite Relationship - Juliana de Moura Medeiros; Diogo Pignatara Coimbra; Alexandre Carvalho Costa; Ana Elisa Barros Medeiros; Beatriz Pereira Coelho; Gustavo Azevedo Quintanilha; Claudia Bezerra da Silva; Jonathan David Ribas Chagas; Cristiane Divan Baldani; Daniel de Almeida Balthazar; Bruna de Azevedo Baeta; Denise Monnerat Nogueira (International Journal of Primatology, 2026)
Primates can share parasites with humans, and understanding host-parasite interactions is essential for evaluating the condition of wild primates, ecological dynamics, and One Health interface, which integrates humans, animal, and environmental health in shared environments. One example is filarial nematodes of the genus Mansonella , for which a lack of in-depth studies of symptoms or blood alterations limits our understanding of their impact on host health and parasite-host dynamics in wild populations. We investigated microfilariae in Sapajus nigritus on Marambaia Island in Rio de Janeiro, Brazil. We also evaluated the host-parasite relationship by assessing the association between microfilarial load with physical and hematological parameters of the hosts. We captured 27 S. nigritus and screened them for microfilariae using blood samples via microscopy—based on morphological and morphometric characteristics—and polymerase chain reaction (PCR), followed by ITS1 sequencing for molecular species identification. We also assessed physical and hematological parameters. We detected microfilariae in 25 individuals (93%) by PCR and in 22 (81%) by microscopy with high mean intensity, mean abundance, and parasite load. We classified the infected S. nigritus as healthy based on both physical and hematological parameters. A multivariate linear model revealed a significant positive association between Mansonella sp. load and red blood cell parameters, while associations with white blood cell parameters were negative and nonsignificant. These results suggest that S. nigritus coexists with Mansonella sp. microfilariae without apparent clinical signs of disease, potentially indicating immunological tolerance. Our findings highlight the importance of understanding host-parasite interactions in wild primates, particularly in environments where human-primate interfaces may occur, suggesting a potential risk of cross-species parasite transmission.

Integrative cytogenetic and molecular analyses in Hypostomus sertanejo reveal the lowest diploid number in the genus (Siluriformes: Loricariidae) - Daniela Rodrigues; Ligia Carla Balini; Bárbara Scorsim; Cláudio Henrique Zawadzki; Alessandra Valéria de Oliveira; Marcos Otávio Ribeiro; Ana Luiza de Brito Portela-Castro; Carlos Alexandre Fernandes; Eliane Papa Ambrosio-Albuquerque; Luciana Andreia Borin-Carvalho (Biologia, 2026)
Expanding integrative cytogenetic and molecular analyses is essential for understanding the evolutionary dynamics of chromosome number variation in fishes. This study presents the first cytogenetic characterization of Hypostomus sertanejo , an endemic species native to the semi-arid Jaguaribe River basin in Northeastern Brazil. Cytogenetic analysis revealed a diploid number of 2n = 52, which is the lowest documented for the genus, with a karyotype composed of 22m + 8sm + 16st + 6a and a fundamental number of 98. This value aligns with the ancestral diploid number suggested for the tribe Hypostomini. Fluorescence in situ hybridization identified a single 18S rDNA site coinciding with the nucleolar organizer region, while 5S rDNA was localized to an interstitial position on a unique chromosome pair. Molecular analysis based on COI gene confirmed the identity of H. sertanejo and its distinction from closely related species. These results reveal a distinctive evolutionary trajectory for H. sertanejo relative to other Hypostomus species and highlight the importance of integrating data to elucidate diversification patterns in endemic fish lineages.

Policy roadmap for governing new oil frontiers under environmental constraints: Lessons from Brazil's Foz do Amazonas basin - Camila Ludovique Callegari; Julia Paletta; Ana Carolina Oliveira Fiorini; Rebecca Draeger; Pedro Henrique Batista de Barros; Renan Medeiros; Alexandre Szklo (Energy Policy, 2026)

Diagnosis of acetaminophen and codeine poisoning in a dog using earwax analysis by headspace gas chromatography-mass spectrometry (HS/GC-MS) - Monica Chacon de Vicente; Alexandre Có Mangoni Barros; Gabriela Scarpin de Souza; Lais di Pauli Taborda Prado; João Marcos Gonçalves Barbosa; Rayanne Henrique Santana da Silva; Leidiane de Souza Gomes; Danieli Brolo Martins; Nelson Roberto Antoniosi Filho; Ana Flávia Machado Botelho (Veterinary Research Communications, 2026)
Poisoning of companion animals resulting from exposure to analgesics intended for human use is a frequent and clinically relevant problem in veterinary practice, usually associated with administration without professional supervision. This can induce severe systemic toxicity. Diagnostic confirmation can be particularly challenging in cases presenting with nonspecific clinical signs or when conventional biological samples are unavailable. This case report describes the innovative use of earwax as a non-invasive biological matrix for toxicological confirmation in veterinary medicine. A 9-year-old male mixed-breed dog was admitted following a traumatic accident and subsequent administration by its owner of a human medication containing acetaminophen and codeine. Clinical evaluation revealed lethargy, hypersalivation, hyporexia, dehydration, and neurological abnormalities. Laboratory findings demonstrated neutrophilic leukocytosis and marked increases in hepatic enzyme activities, consistent with acute hepatocellular injury. Toxicological investigation using headspace gas chromatography–mass spectrometry detected acetaminophen-related signatures in an earwax sample, supporting suspected exposure to the drug. Intensive treatment was promptly initiated and included fluid therapy, antidotal treatment with N-acetylcysteine, opioid antagonism, analgesia, and supportive care. The patient showed progressive clinical improvement, with complete resolution of clinical signs and full recovery. This case highlights the significant risks of administering human medications to companion animals and underscores the need to improve owner awareness of self-medication practices. Furthermore, it demonstrates the diagnostic potential of earwax as a non-invasive biological matrix for toxicological confirmation, expanding the range of complementary diagnostic tools available for veterinary toxicology and supporting improved clinical decision-making in cases of suspected pharmaceutical intoxication.

Correction: Supplementing the diet of Nile tilapia (Oreochromis niloticus) with microalgae Nannochloropsis oculata and Phaeodactylum tricornutum enhanced immune function, lipid profile, and resistance to Edwardsiella tarda infection - Domickson Silva Costa; Jucimauro de Araújo Pereira Júnior; Paola Capistrano dos Santos; Maria Clara Miguel Libanori; Gracienhe Gomes dos Santos; Ana Paula de Souza; Alexandre Vaz da Silva; Cláudia Andrea Lima Cardoso; Arlene Sobrinho Ventura; Aline Brum Figueredo Ruschel; Rafael Sales; Fábio de Farias Neves; et al. (Veterinary Research Communications, 2026)

Supplementing the diet of Nile tilapia (Oreochromis niloticus) with microalgae Nannochloropsis oculata and Phaeodactylum tricornutum enhanced immune function, lipid profile, and resistance to Edwardsiella tarda infection - Domickson Silva Costa; Jucimauro de Araújo Pereira Júnior; Paola Capistrano dos Santos; Maria Clara Miguel Libanori; Gracienhe Gomes dos Santos; Ana Paula de Souza; Alexandre Vaz da Silva; Cláudia Andrea Lima Cardoso; Arlene Sobrinho Ventura; Aline Brum Figueredo Ruschel; Rafael Sales; Fábio de Farias Neves; et al. (Veterinary Research Communications, 2026)
The aim of the present study was to evaluate the effects of dietary supplementation with the microalgae Nannochloropsis oculata and Phaeodactylum tricornutum , either separately or in combination, on growth performance, lipid profile, haematoimmunological parameters, and resistance to Edwardsiella tarda infection in Nile tilapia ( Oreochromis niloticus ). A total of 960 juvenile Nile tilapia (2.87 ± 0.68 g and 5.65 ± 0.16 cm) were allocated to 24 experimental units ( n = 40) and fed six experimental diets for 60 days: DC 0% (no microalgae inclusion), DN 0.5% (0.5% N. oculata ), DN 1% (1% N. oculata ), DP 0.5% (0.5% P. tricornutum ), DP 1% (1% P. tricornutum ), and DPN 1% (0.5% N. oculata + 0.5% P. tricornutum ). After the feeding period, fish were challenged with E. tarda (2 × 10⁸ CFU mL⁻¹). Microalgal inclusion increased significantly ( p < 0.05) dietary contents of phenolic compounds, flavonoids, tannins, and antioxidant potential of diets without affecting fish growth. The DP 1% and DPN 1% diets increased significantly ( p < 0.05) eicosapentaenoic and docosahexaenoic acid levels and reduced monounsaturated fatty acids and ∑saturated fatty acids in muscle, thereby improving the lipid profile and flesh quality. Following infection, reductions in erythrocytic parameters were observed, along with increases in lymphocyte, monocyte, basophil, neutrophil, and thrombocyte counts, as well as higher ( p < 0.05) agglutination and antimicrobial titres, total plasma protein, and immunoglobulin levels in the DP 1% and DPN 1% groups. Survival was higher in the microalgae-supplemented groups, particularly in DPN 1% (91.67 ± 1.8%) compared with the control (65.0 ± 2.0%). Supplementation with DP 1% and DPN 1% improved haematoimmunological responses, lipid composition, and resistance to E. tarda in Nile tilapia.

N-acetylcysteine mitigates oxidative stress and reduces alveolar bone damage on experimental periodontitis in rats - Ana Paula de Andrade Silva; Erick Alves dos Santos; Deborah Ribeiro Frazão; Vinicius Ruan Neves dos Santos; José Mario Matos-Sousa; Beatriz Risuenho Peinado; Deiweson Souza-Monteiro; Wallacy Watson Pereira Melo; Zuleni Alexandre da Silva; Everton Luiz Pompeu Varela; Jorddy Neves da Cruz; Carina Maciel da Silva-Boghossian; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
This study evaluated the effect of N-acetylcysteine ​​on oxidative biochemistry and bone damage during the development of ligature-induced experimental periodontitis in rats. The rats were divided into three groups (n = 8/group): control, experimental periodontitis (EP), or experimental periodontitis plus daily N-acetylcysteine administration (EP + NA) (100 mg/kg/day). Periodontitis was induced by bilateral silk ligatures on the mandibular first molars for 14 days. The antioxidant capacity of N-acetylcysteine ​​was measured by (2,2-azinobis [3-ethylbenzothiazoline-6-sulfonate] (ABTS• +) and 1,1-dipheny-2-picrylhydrazyl (DPPH•) assays. Gingival samples were collected for analysis of oxidative parameters, while mandibles were used for histopathological evaluations of inflammation and collagen content, as well as for micro-computed tomography assessments of bone quality and vertical bone loss. Data were analyzed by Analysis of Variance (ANOVA), Multivariate Analysis of Variance (MANOVA), and Pearson’s correlation ( p

Structural abnormalities in erythrocytes and a potential denucleation process induced by metformin, compromising cell viability in specimens of Astyanax lacustris (Pisces, Characidae) - Luara Lupepsa; Pablo Américo Barbieri; Brennda Ribeiro Paupitz; Vanessa Oliveira Sales-Zampar; Helito Volpato; Fernanda Errero Porto Saparolli; Eliane Papa Ambrosio-Albuquerque; Carlos Alexandre Fernandes; Luciana Andreia Borin-Carvalho; Ana Luiza de Brito Portela-Castro (Environmental Science and Pollution Research, 2026)
Hematological studies in fish are sensitive indicators of physiological and pathological changes caused by aquatic pollution, including pharmaceutical contaminants. Among these pollutants, metformin is one of the most prevalent and has been associated with adverse effects on aquatic organisms. However, its impact on fish erythrocyte morphology remains poorly understood. This study evaluated the cyto- and genotoxic effects of metformin on erythrocytes of Astyanax lacustris through morphological analyses, membrane integrity assessment by flow cytometry, and DNA damage evaluation using comet assay. Fish were exposed to metformin concentrations of 50, 100, and 10,000 µg/L for 90 days. Exposure induced significant erythrocyte alterations, particularly at higher metformin concentrations, including membrane invaginations and ruptures, cytoplasmic vacuolization, nuclear abnormalities, DNA damage, peripheral nuclei, and formation of erythroplastids, suggesting denucleation process. Flow cytometry also revealed an increased proportion of non-viable cells. These findings suggest that metformin may significantly impair erythrocyte physiology and viability, potentially compromising the health of exposed fish.

Evaluation of episcleral silicone matrix cyclosporine implants for presumed equine immune-mediated keratitis: a retrospective study - Emma Bruneel; Tanguy Hermange; Jean Michel Casamatta; Alexandre Pereira; José Pimenta; Ana Rita Caseiro (Journal of Equine Veterinary Science, 2026)

Integrative structural and kinetic analysis of the molecular basis for reduced carbamate inhibition in atypical butyrylcholinesterase - Ana Matošević; Nikola Maraković; Danijela Barić; Alexandre Igert; Xavier Brazzolotto; Zrinka Kovarik; Anita Bosak (Chemico-Biological Interactions, 2026)

Soil contamination assessment of a 19th-century abandoned Sb–Au mine in northern Portugal - Giulia Resta; Patrícia Santos; Marcus Monteiro; Rui Melo; Morgana Carvalho; Ana Carvalho; Alexandre Lima; Eric Font; José A. Ribeiro; Manuel Azenha; Thierry Adatte; Deolinda Flores (Environmental Geochemistry and Health, 2026)
Abandoned mines are among the main sources of long-term soil contamination, often leaving behind persistent concentrations of potentially toxic elements (PTE) that pose environmental and health risks. Ribeiro da Serra Sb–Au mine, in Portugal, active from 1858 to 1890, has left a significant environmental legacy. This study mapped the spatial distribution of mine processing residues, elemental characterisation distinguishing between anthropogenic and natural enrichment by determining soil sample concentrations of PTE, Hg mobility, and Total Organic Carbon (TOC) quantification. Multivariate analysis, spatial interpolation and comparison with Enrichment Factor were employed with the aim of understanding the distributions and sources of PTEs in the soils. Mercury is still present at the site, revealing high mobile (18.72 mg kg −1 ) and semi-mobile (3.58 mg kg −1 ) concentrations accumulated in waste piles, a remnant of Au amalgamation processes. High Hg concentrations (20.75 mg kg −1 ) pose significant environmental risks, even after more than a century, such as bioaccumulation potential and soil toxicity. Also, there are high concentrations of Pb (449.03 mg kg −1 ) in the waste piles from the Sb processing. This study highlights the critical importance of interpreting natural enrichment values of elements of Hg (EF = 267) and Pb (EF = 18) to discern pollution pathways resulting from mining and processing activities. Interpretation of natural enrichment values leads to a more accurate evaluation of environmental contamination and its sources. The Enrichment Factor shows that Sb (EF = 133) and Hg (EF = 267) are the elements that present extremely high enrichment (EF > 40).

Brazil’s science–policy effort to monitor native vegetation restoration - André L. Giles; Marina G. Freitas; Ana L. V. Espada; Pedro Constantino; Bruno S. Francisco; Silvia B. Rodrigues; Alexandre B. Sampaio; Isis F. de Freitas; Gabriela C. S. Bueno; Raquel C. A. Lacerda; R. Edson; Kirsten Silvius; et al. (Ambio, 2026)
In its early years, the UN Decade on Ecosystem Restoration has mobilized unprecedented global commitments. Yet, measuring restoration success remains contested, particularly in megadiverse countries where the absence of standardized indicators and assessment protocols often leads to subjective decisions by environmental agencies. Here, we present a core set of leading indicators developed through a pioneering Brazil-led science–policy collaboration between environmental agencies and research institutions. The indicators capture early vegetation recovery within four years and whether restoration trajectories are sustained or at risk of reversal. The initiative also establishes a framework that bridges science and policy to deliver practical monitoring tools. It offers a model for other megadiverse countries with complex governance, showing how simple, standardized indicators can translate restoration pledges into measurable results for the UN Decade.

Ocean to Ocean: First Documented Migration of a Southern Right Whale From the Southwest Atlantic to the Southeast Pacific Ocean - Santiago José Fernández; Marcela M. Uhart; Ana María García‐Cegarra; Valeria Falabella; Mads Peter Heide‐Jørgensen; Melinda Holland; Aluminé Orce; Matías Pujana; Mariano Sironi; Federico Sucunza; Mariano Coscarella; Alexandre N. Zerbini (Marine Mammal Science, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

House of the blue dragon: Ecological niche models predict range expansion of Glaucus atlanticus Forster, 1777 (Mollusca: Nudibranchia) under different climate change scenarios - Ana Paula Ferreira; Alexandre R. da Silva (Regional Studies in Marine Science, 2026)

Early evidence of arrested succession in riparian forests after a large savanna wildfire - André L. Giles; Marcio B. Cure; Ana Christina Barbosa; Anna Abrahão; Patrícia de Britto Costa; Michele de Sá Dechoum; Rafael S. Oliveira; Alexandre B. Sampaio; Isabel B. Schmidt; Bruno M.T. Walter; Bernardo M. Flores (Journal of Environmental Management, 2026)

Potential of guava pulps treated by ohmic heating as a delivery vehicle for probiotic bacteria: stability, functional properties, and in vitro digestibility - Newton C. Santos; Raphael L.J. Almeida; Virgínia M. de A. Silva; Thalis L.B. de Lima; Ronildo P. de Sousa Júnior; Victor H. de A. Ribeiro; Yaroslávia F. Paiva; Francislaine S. dos Santos; Deyzi S. Gouveia; Rennan P. de Gusmão; Alexandre J. de M. Queiroz; Josivanda P. Gomes; et al. (International Journal of Food Microbiology, 2026)

Effect of zinc oxide nanoparticle supplementation in Santa Inês ewes during the transition period - Willinton Hernan Pinchao Pinchao; Henrique de Brito Guedes; Carolina Rodriguez Jimenez; Gabriele Rossini Moreira; Murilo Antônio Fernandes; Bruna Gonçalves Santos Costa; Luciana Morita Katiki; Elisabete Aparecida de Nadai Fernandes; Mateus Oliveira Mena; César Cristiano Bassetto; Ana Cláudia Alexandre de Albuquerque; Alessandro Francisco Talamini do Amarante; et al. (Tropical Animal Health and Production, 2026)
Zinc oxide nanoparticles (N-ZnO) represent a promising alternative for zinc (Zn) supplementation, since their reduced size provides greater bioavailability and better integration into the body. Furthermore, this characteristic becomes particularly relevant during periods of increased metabolic stress, such as the transition phase. Thus, the objective was to evaluate the effects of N-ZnO supplementation in Santa Inês sheep during the peripartum period. Thirty-three ewes with an average body weight of 43.3 ± 2.05 kg were, distributed into three experimental groups: control group (CON), without supplementation, receiving only Cynodon spp. hay; and groups supplemented with 300 mg/animal/day of N-ZnO (40 nm) and zinc oxide microparticles (M-ZnO). The supplementation was administered orally in capsules daily from late pregnancy until weaning. The results showed no significant differences ( P > 0.05) in body weight, egg count per gram of feces (EPG), and in most of the hematological, biochemical, and immunological parameters evaluated. However, differences ( P < 0.05) were observed in monocyte counts and albumin levels, with higher means in the N-ZnO group, showing differences compared with the M-ZnO group, while the CON group maintained intermediate values. The N-ZnO group showed differences compared to the M-ZnO group, while the CON group maintained intermediate values. Regarding antioxidant activity, a significant effect ( P < 0.05) was observed on the enzymes Superoxidase dismutase (SOD), Glutathione peroxidase (GPx), Catalase (Cat), and on the total antioxidant status (ORAC) of the sheep supplemented with N-ZnO. It is concluded that N-ZnO supplementation improved the antioxidant response, with no signs of intoxication, using a dose of 300 mg during the period of greatest oxidative stress.

Regional Crosstalk Between the Amygdala, Hippocampus, and Prefrontal Cortex Following Na+,K+-ATPase Inhibition by Ouabain - Bianca Estefani Schmidt; Ana Karla Oliveira Leite; Clarissa Penha Farias; Alessandra Schmitt Rieder; Gustavo Ricardo Krupp Prauchner; Carlos Alexandre Netto; Angela T. S. Wyse (Neurotoxicity Research, 2026)
The Na⁺,K⁺-ATPase plays a fundamental role in memory formation by regulating neuronal excitability and NMDA receptor-dependent synaptic plasticity. While this enzyme’s dysfunction is broadly linked to cognitive disorders, its specific contribution to fear memory consolidation, particularly within the key brain structure of the basolateral amygdala (BLA), remains undefined. We investigate whether Na + ,K + -ATPase inhibition disrupts contextual fear conditioning (CFC) memory consolidation and examine downstream molecular, oxidative, and inflammatory responses in interconnected brain regions. Fifty-day-old male Wistar rats received bilateral cerebral infusions of the Na + ,K + -ATPase inhibitor ouabain (1 μm) or vehicle immediately after CFC training. Memory retention was assessed 24 h later. Additional cohorts were euthanized 6–24 h after infusion for biochemical analysis of Na + ,K + -ATPase activity, expression of Na + ,K + -ATPase isoforms (α1, α2, α3, β1), oxidative stress markers, and pro-inflammatory cytokines in the amygdala, hippocampus, and prefrontal cortex. Post-training Na + ,K + -ATPase inhibition in the BLA selectively impaired fear memory consolidation. Ouabain induced changes in Na⁺,K⁺-ATPase activity in the hippocampus and prefrontal cortex, and induces time-dependent upregulation of α1 and β1 isoforms. Six hours after infusion, ouabain triggered oxidative imbalance – characterized by reduced CAT activity. Pro-inflammatory cytokine expression was markedly elevated in the hippocampus and prefrontal cortex, while D-serine co-administration failed to rescue memory deficits. These findings establish a previously unrecognized role for Na⁺,K⁺-ATPase signaling in the BLA in coordinating the neurobiological processes essential for fear memory consolidation, indicating that its precise regulation is required for adaptive fear memory formation.

Molecular epidemiological surveillance of circovirus in avian and mammalian species on the Brazilian coast - Ana Julia Chaves Gomes; Yasmin Luisa Neves Lemes Garcia; Dayla Bott Geraldini; Camila Domit; Fábio Henrique de Lima; João Pessoa Araújo; Juliana Schons Gularte; Micheli Filippi; Vyctoria Malayhka de Abreu Góes Pereira; Meriane Demoliner; Alexandre Sita; Fernando Rosado Spilki; et al. (Archives of Virology, 2026)
Circoviruses (CVs) infect diverse mammals, birds, and freshwater fish and are linked to diseases causing major economic losses. Despite being well studied in psittacines, their circulation in other avian groups and mammals is poorly understood. We conducted molecular surveillance of CVs in migratory birds and mammals along the Paraná coast, southern Brazil. Sterna hirundinacea specimen tested positive by Nested-PCR for GullCV. In the GullCV-infected bird, histopathology revealed nonspecific lesions, including marked splenic lymphoid atrophy, cachexia-related changes, acute tubular necrosis, and generalized congestion. Sanger sequencing revealed 83% nucleotide identity with CV sequences previously reported in gulls from the United States, which was consistent with results obtained by NGS and Rep-based phylogenetic analysis. These findings contribute to the understanding of CV diversity, distribution, and host range.

In silico and in vitro assessment of the eucalyptus wood vinegar impact on reproduction of ticks Rhipicephalus microplus (Acari: Ixodidae) - Ana Karolinne de Alencar França; Alexandre Santos Pimenta; Yandra Thais Rocha da Mota; Pablo Leandro Filgueira Feitosa; Ana Carolyna Diógenes Bezerra; Thays Vieira da Costa Monteiro; Maíra Fasciotti; Rafael Rodolfo de Melo; Lúcio César Dantas de Medeiros; Ana Carla Diógenes Suassuna Bezerra (Veterinary Parasitology, 2026)

Equipping the next generation of plant taxonomists: Insights and recommendations - Ana Rita G. Simões; Frederik Leliaert; Gemma L.C. Bramley; Ruth P. Clark; Rhian J. Smith; Manuel Luján; Ian Ondo; Matilda J.M. Brown; Gabriel K. Ameka; Catherine W. Lukhoba; Renata Borosova; Bente B. Klitgård; et al. (Trends in Plant Science, 2026)

Bisphenol S and high-fat diet drive structural and inflammatory remodeling of the colon in C57Bl/6 male mice - Beatriz Gouvêa de Luca; Beatriz Alexandre-Santos; Kauet de Matos Gama e Souza; Emanuelle Barreto-Reis; Ana Paula de Paula Alves; Thaís de Souza Carvalho-Laureano; Vinicius Sepúlveda-Fragoso; Luiza Gil Diniz; Milena Barcza Stockler-Pinto; Clarice Machado dos Santos; Denise Pires de Carvalho; Leandro Miranda-Alves; et al. (Toxicology Letters, 2026)

Environmental gradients shape fish assemblages across estuarine-coastal ecosystems on the eastern Brazilian coast - Rafael L. Oliveira; Germano Henrique Costa Barrilli; Mauricio Hostim-Silva; Ronaldo R. Oliveira-Filho; Helen A. Pichler; André P. Cattani; Ryan Andrades; Ciro C. Vilar; Ana C. Martins; Valéria M. Lemos; Alexandre M. Garcia; Henry L. Spach; et al. (Marine Environmental Research, 2026)

Food use, behavioral and cultural significance of the wood-boring mollusc Turu (Teredo sp.) in the Brazilian Amazon - Danilo Vitor Vilhena Batista; Larissa Aparecida Moreira de Castro; Adriana Fernandes de Barros; Caio Francisco Santana Farias; Ana Paula de Souza; Alexandre Vaz da Silva; Carolina Cerqueira Lima Dittrich; Emilly Monteiro Lopes; Elenice Martins Brasil; Marco Shizuo Owatari; José Luiz Pedreira Mouriño; Maurício Laterça Martins (Food and Humanity, 2026)

A hybrid simulated moving bed/pressure swing adsorption process for methane and nitrogen separation - Rafael O.M. Dias; Alexandre F.P. Ferreira; Alírio E. Rodrigues; Ana M. Ribeiro (Chemical Engineering Journal, 2026)

Sex-specific cardiac responses to subacute exposure to tributyltin in rats - Ana Beatriz Araújo Mendes; Nadia Alice Vieira Motta; Gabriel Ferreira Lima; Lis Jappour Autran; Stephani Correia Brazão; Nikolas Cunha de Assis Pereira; Ana Rebecca da Silveira de Souza; Beatriz Alexandre-Santos; D'Angelo Carlo Magliano; Leandro Miranda-Alves; Fernanda Carla Ferreira Brito (Chemico-Biological Interactions, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Effects of okadaic acid and phytoplankton ingestion on nr1j1, cyp, and abcb1 gene expression in Mytilus galloprovincialis - Juliana Rodrigues; Cristina Plata-Calzado; Maria Paula Gómez-Román; Sergio Boo; Elza Fonseca; Mário Araújo; Vitor Vasconcelos; Ana I. Prieto; Angeles Jos; Alexandre Campos (Marine Environmental Research, 2026)

Stakeholder perspectives on local and seasonal food in Brazil and Portugal: Pathways to sustainability - Alexandre Maia Vargas; Ana Pinto Moura; Rosires Deliza; Luís Miguel Cunha (International Journal of Gastronomy and Food Science, 2026)

Neurotoxicity and teratogenicity induced by carbendazim and ametryn in zebrafish: Implications for environmental and biological health - Júlia Robert Teixeira; Livia Alves de Macedo Tavares; Ariana Pereira da Silva; João Vitor de Macedo-Sampaio; Hugo Alexandre de Oliveira Rocha; Katia Castanho Scortecci; Bruno Fiorelini Pereira; Ana Carolina Luchiari (Environmental Toxicology and Pharmacology, 2026)

Orange (Citrus sinensis) essential oil as feed additive for sheep: nutrient intake and apparent digestibility, nitrogen balance, and rumen fermentation characteristics - Paulo César G. Dias Junior; Ana Carolina S. Vicente; Isabela J. dos Santos; Letícia C. B. Soares; Adrielly L. A. da Silva; Rhaissa G. de Assis; Jamile Haddad Comelli; Daniel M. Polizel; Janaina S. Biava; Diogo F. A. Costa; Alexandre V. Pires; Evandro M. Ferreira (Tropical Animal Health and Production, 2026)

A Diachronic Analysis of the Relationships Between Humans and Araucaria Forests - Ana H. Ladio; Alexandre Siminski; Karine L. dos Santos; Mauricio Sedrez dos Reis (Ethnobotany and Economic Botany, 2026)

Seasonal biochemical fingerprints of outdoor cultivated Spirulina (Limnospira platensis) and Microchloropsis gaditana: insights into compositional and functional shifts - Diana Lopes; Ana S.P. Moreira; Tiago Conde; Andreia Ferreira; Kayane Oliveira; Alexandra Conde; Helena R. Rocha; Marta Coelho; Ana Gomes; Manuela Pintado; Ana Alexandra Ramos; Hugo Pereira; et al. (Algal Research, 2026)

Fights in a tight space: wax scale Ceroplastes deodorensis Hempel (Hemiptera: Coccidae: Ceroplastinae) and associated parasitoids (Hymenoptera: Chalcidoidea) on a new host plant (Arecaceae) - Nyeppson de Sousa Soares; Anne Caroline Santos Küll; Alexandre Santos Araújo; Gabriel Silva Dias; Ana Lúcia Benfatti Gonzalez Peronti; Leonardo Souza Duarte; Bianca Mendes de Almeida; Yanka Silva de Sousa; Valmir Antonio Costa; Roberto Antonio Zucchi; Marcoandre Savaris (International Journal of Tropical Insect Science, 2026)
The hosts of Ceroplastes deodorensis Hempel (Hemiptera: Coccidae) belong to the families Annonaceae and Moraceae, which are exclusively recorded in Brazil. In this report, we document for the first time the occurrence and impact of C. deodorensis on adult plants of the dwarf date palm, Phoenix roebelenii O’Brien (Arecaceae), in Brazil. The wax scale was collected and examined on P. roebelenii at the “Luiz de Queiroz” campus in Piracicaba, São Paulo, Brazil, between April 2024 and March 2025. The population of C. deodorensis peaked from April to October 2024, causing damage solely to the leaves (leaflets) of the dwarf date palm, which manifested as yellowing and drying. The scale insect was found to be parasitized by four species of Chalcidoidea from four families: Aprostocetus sp. (Eulophidae), Brasema sp. (Eupelmidae), Metaphycus floridensis Santos & Tavares (Encyrtidae) (new record), and Scutellista caerulea (Fonscolombe) (Eunotidae) (new record). Notably, M. floridensis and S. caerulea comprised over 90% of the total parasitoids collected. This study serves to compile and update information regarding the hosts and parasitoids of C. deodorensis.

Acute toxicity and redox-modulating potential of nanoparticles loaded with phenolic compounds from cantaloupe melon (Cucumis melo L.) in zebrafish (Danio rerio) - Aslan Costa Trajano; Ana Carolina Luchiari; Yasmim Pessoa de Oliveira; Jéssica Anarellis Barbosa dos Santos; Beatriz Silva Lopes; Cristiane Fernandes de Assis; Hugo Alexandre Oliveira Rocha; Weslley de Souza Paiva; Susana Margarida Gomes Moreira; Pablo Felipe Ferreira Farias; Ana Heloneida de Araújo Morais; Thaís Souza Passos (Food Research International, 2026)

Evaluating an isotopic model for tracing the geographic origin of soybeans in Brazil - Maria Gabriella da Silva Araújo; Deoclecio Jardim Amorim; Rodrigo Figueiredo Almeida; Edmar Mazzi; Ana Claudia Gama Batista; Isabela Maria Souza-Silva; Alexandre Tadeu Brunello; Gabriela Bielefeld Nardoto; Gabriel J. Bowen; Luiz Antonio Martinelli (Food Chemistry, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Therapeutic Efficacy of Monoterpenes in Nile Tilapia Infected With Edwardsiella tarda : A Phytogenic Alternative to Oxytetracycline - Danilo Vitor Vilhena Batista; Adolfo Jatobá; Alexandre Vaz da Silva; Ana Paula de Souza; Caio Francisco Santana Farias; Emilly Monteiro Lopes; Marco Shizuo Owatari; Arlene Sobrinho Ventura; Claudia Andrea Lima Cardoso; Silvia Terra Fontes; Fernando Yugo Yamamoto; Maurício Laterça Martins; et al. (Journal of Fish Diseases, 2026)
The purpose of this research was to assess the effectiveness of a combination of monoterpenes (thymol and carvacrol) in treating juvenile Nile tilapia ( Oreochromis niloticus ) infected with Edwardsiella tarda as a potential substitute for the antibiotic oxytetracycline. The study utilised different concentrations of the monoterpenes blend (MTs): 0.4, 0.6 and 0.8 g kg −1 of feed. A negative control group received a diet without the additive, while a positive control group was given medicated feed containing oxytetracycline (OTC) (11.85 g kg −1 ) for a 10‐day treatment period. Cumulative mortality (%), haematological and immunological parameters were assessed after the feed administration. The negative control group experienced a mortality rate of 53%, while fish treated with medicated feed had a significantly lower mortality rate of 3%. The addition of MTs at concentrations of 0.4 g kg −1 (13% mortality), 0.6 g kg −1 (8% mortality) and 0.8 g kg −1 (0% mortality) also resulted in reduced mortality rates, with the highest concentration showing survival rates comparable to the oxytetracycline group. Following the 10‐day treatment period, no mortality was observed in the treated groups, indicating the efficacy of MTs‐supplemented feed in alleviating the clinical symptoms of Edwardsiellosis. The haematological parameters indicated that as the dosage of MTs increased, the mean corpuscular volume (MCV) decreased. The MCV was significantly lower in the 0.6 and 0.8 g kg −1 treatments compared to the control. Mean corpuscular haemoglobin initially increased with the 0.4 g kg −1 MTs treatment but then decreased with higher doses. The mean corpuscular haemoglobin concentration was higher in the treated groups compared to the control. Red blood cell levels were higher in the 0.8 g kg −1 MTs treatment and lower in the 0.4 g kg −1 treatment. Ht was higher in the control group and lower in the 0.4 g kg −1 MTs treatment. Haemoglobin levels followed a similar trend, with higher values in the control group. The 0.8 g kg −1 MTs treatment had the highest number of total leucocytes and lymphocytes. The control group had the highest number of neutrophils, while the 0.8 g kg −1 MTs group had higher numbers of monocytes, eosinophils, basophils and thrombocytes. The negative control exhibited the lowest antimicrobial titre compared to the OTC and the various concentrations of MTs. The concentrations of MTs (0.4, 0.6 and 0.8 g kg −1 ) demonstrated similar average values and were more effective than the control and OTC. There was no significant difference in agglutinating titre among MTs, control and OTC. Thymol and carvacrol notably decreased the mortality of tilapia infected with E. tarda , with a dosage as high as 0.8 g kg −1 showing equivalent effectiveness to oxytetracycline. Furthermore, they enhanced haematological and immunological parameters, indicating that MTs could be a promising alternative to antibiotic use.

Reply to Figueroa‐Muñoz et al.'s comment on ‘multiple tools to investigate the origin of the exotic species Chinook salmon Oncorhynchus tshawytscha (Walbaum, 1792) (Salmonidae) in the world's largest chocked coastal lagoon’ - Yan Gonçalves Gowert; Valéria Marques Lemos; Fabiano Corrêa; Sabrina Vollrath; João Paes Vieira; Mario Vinicius Condini; Rodrigo Ferreira Bastos; Mylla Carla Cescon Freire; Ana Paula Cazerta Farro; Antonio Sergio Varela Junior; Cristiano Albuquerque; Maurício Hostim‐Silva; et al. (Journal of Fish Biology, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

First report of Penicillium digitatum causing postharvest rot in lemon in Brazil - Glícia Silva de Moraes; Amanda Cupertino de Queiroz Brito; Ana Elisa de Almeida Souza; Jordana Alves da Silva Melo; José Vitorino da Silva Neto; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Journal of Plant Pathology, 2026)

Biochemical parameters of lambs under frequent treatment with antiparasitic association - Hornblenda Joaquina Silva Bello; José Gabriel Gonçalves Lins; Naiara Mirelly Marinho da Silva; Ana Cláudia Alexandre de Albuquerque; Mônica Regina Vendrame Amarante; Regina Kiomi Takahira; Alessandro F.T. Amarante (Small Ruminant Research, 2026)

Delta-endotoxin production and toxicity enhancement by using vegetable oils as oxygen vectors - Túlio Alexandre Freire da Silva; Beatriz Rayana Damásio de Andrade; Lívia Santos de Freitas; Evelyn Geovanna Gomes Carvalho e Silva; Emmily Vitoria Gomes da Silva; Leandro Fragoso Lins; José de Paula Oliveira; Raquel Pedrosa Bezerra; Ana Lúcia Figueiredo Porto (World Journal of Microbiology and Biotechnology, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Effect of Physical Exercise on Acute Post-traumatic Hyperexcitability: The Role of Thrombin/PAR1 Signaling - Alexandre Seixas Nascimento; Willian Link Papalia; Douglas Buchmann Godinho; Pamela Carvalho da Rosa; Yuri Augusto Moreira Pena; Giovana Dal Magro; Mauro Schneider Oliveira; Ana Flavia Furian; Luiz Fernando Freire Royes; Michele Rechia Fighera (Molecular Neurobiology, 2026)

Monoterpenes: Functional Additives for Reducing Antibiotics in Aquaculture - Danilo Vitor Vilhena Batista; Barbara Silveira Souza; Caio Francisco Santana Farias; Ana Paula de Souza; Alexandre Vaz da Silva; Emilly Monteiro Lopes; Elenice Martins Brasil; Maurício Laterça Martins; José Luiz Pedreira Mouriño; Marco Shizuo Owatari (Reviews in Aquaculture, 2026)
Aquaculture is a rapidly growing industry that supplies fish for global consumption. However, the intensive production practices have resulted in disease outbreaks, largely driven by the misuse of antibiotics. Natural alternatives, such as monoterpenes, which are biocompounds derived from essential oils obtained from plants like thyme and oregano, are being investigated for their antimicrobial properties. Research has shown that monoterpenes can effectively reduce mortality rates in aquaculture, providing a sustainable solution for disease management without the negative environmental impacts associated with antibiotics. This approach has the potential to promote healthier and more environmentally friendly fish production. Monoterpenes have demonstrated promising results in enhancing fish resistance to pathogens, which could potentially reduce the reliance on antibiotics in aquaculture. However, the economic feasibility of incorporating these compounds into fish diets has not been thoroughly examined, which may hinder their widespread adoption. Clear economic data is essential to evaluate the costs and benefits of using monoterpenes in aquaculture, as uncertainties regarding financial returns could discourage producers and investors. Without this information, the market acceptance of aquafeeds containing monoterpenes may be limited, affecting the progress of cleaner and more sustainable fish farming practices. This review aims to address the gaps in knowledge regarding the widespread use of phytobiotics, specifically focusing on monoterpenes and their impact on the aquaculture industry. It will delve into their mechanisms of action, effectiveness in protecting aquatic animals, and recent developments in combating bacterial infections, while also discussing the risks posed by antimicrobial resistance.

Natural deep eutectic systems-based Ginkgo biloba extracts: A natural and sustainable solution for skin care - Marta Marques; Ana Rita Jesus; Ana Rita C. Duarte; Alexandre Paiva (Sustainable Chemistry and Pharmacy, 2025)

Kinetics of thermochemical sulfate reduction based on pyrolysis gold-tube experiments on lacustrine oil: Implications for H2S prediction in Brazilian pre-salt reservoirs - Igor V.A.F. Souza; Yongchun Tang; Le Lu; Alexandre A. Ferreira; Geoffrey S. Ellis; Rut A. Díaz; Luiz Felipe Carvalho Coutinho; Ana Luiza S. Albuquerque (Marine and Petroleum Geology, 2025)

Paleoecological context of Homo aff. erectus (ATE7-1) at Sima del Elefante (late Early Pleistocene, Atapuerca, Spain) inferred from the herpetofaunal assemblage - Christian Sánchez-Bandera; Ana Fagoaga; Hugues-Alexandre Blain; Juan Manuel López-García; Carmen Núñez-Lahuerta; Àngel Blanco-Lapaz; Julia Galán; Raquel Moya-Costa; Gloria Cuenca-Bescós; Xosé Pedro Rodríguez-Álvarez; Rosa Huguet (Journal of Human Evolution, 2025)

Cashew nut protein concentrate as a potential ingredient for the emerging alternative protein industry - Jéssica Silva do Carmo; José Diogo da Rocha Viana; Arthur Claudio Rodrigues de Souza; Kelvi Wilson Evaristo Miranda; Celli Rodrigues Muniz; Lorena Mara Alexandre e Silva; Matheus Dias de Carvalho; Ana Carla Kawazoe Sato; Daniele Maria Alves Teixeira Sá; Wellington da Silva Oliveira; Fernanda Furlan Gonçalves Dias; Ana Paula Dionísio (Food Chemistry, 2025)

Retrospective analysis of sperm metrics in fresh ejaculates of collared peccaries presenting contrasting semen freezability - Samara Sandy Jerônimo Moreira; Romário Parente dos Santos; Luana Grasiele Pereira Bezerra; Ana Glória Pereira; Náyra Rachel Nascimento Luz; Andreza Vieira Brasil; Thales Pinheiro Cavalcanti; Moacir Franco de Oliveira; Simone Maria Massami Kitamura Martins; André Furugen Cesar de Andrade; Alexandre Rodrigues Silva (Cryobiology, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Multiomic insights into sucrose accumulation in sugarcane - Alexandre Hild Aono; Ricardo José Gonzaga Pimenta; Jéssica Faversani Diniz; Marishani Marin Carrasco; Guilherme Kenichi Hosaka; Fernando Henrique Correr; Ana Letycia Basso Garcia; Estela Araujo Costa; Alisson Esdras Coutinho; Luciana Rossini Pinto; Marcos Guimarães de Andrade Landell; Mauro Alexandre Xavier; et al. (Plant Molecular Biology, 2025)

Safety and efficacy of an intramuscular bivalent vaccine against influenza and Streptococcus pneumoniae infections in mice - Kimberly Freitas Cardoso; Lara Regina Alves de Souza; Débora Silva Martins; Beatriz Senra Álvares da Silva Santos; Ketyllen Reis Andrade de Carvalho; Sarah Giarola da Silva Messias; Ana Paula de Faria Gonçalves; Rayanne Rosa Do Nascimento Macário; Deyse Julia Ferreira de Jesus; Ana Luiza Pessoa De Mendonça Ângelo; Leonardo de Paula Pereira; Sâmick Layene Moreira Nascimento; et al. (Medical Microbiology and Immunology, 2025)

Isolation of Orthopoxvirus vaccinia during an outbreak of vesicular disease in dairy cattle from Viçosa, state of Minas Gerais, southeast Brazil - Alex Pauvolid-Corrêa; Larissa Berdine Gomes de Jesus; Vivian Alves Piuzana Barbosa; Yuri Elias Teixeira Oliveira; Marcos Alexandre Nunes da Silva; Milena de Paula Rebello; Gabriel Soares de Freitas; Gabriela de Souza Bem; Ana Alice Pimenta-Pereira; Ana Gabriela Coelho Rabelo; Ewelyn Vitoria Jesus Dias Gonçalves; Mariana Freitas Moreira; et al. (Brazilian Journal of Microbiology, 2025)

Copper/zinc ratio and erythrocyte superoxide dismutase in patients with thyroid nodules - Bruna Aparecida Melo Batista; Matheus Aragão Dias Firmino; Paula Alexandre de Freitas; Morgana Pinheiro Sousa; Ana Carolina Marinho Ferreira; André Pires Cortez; Wladiana Oliveira Matos; Francisco Luan Fonsêca da Silva; Carla Soraya Costa Maia (BioMetals, 2025)

Molecular expression of glycosaminoglycans modifies the plasticity of biphasic mesothelioma in favor of tumor progression - Camila Machado Baldavira; Aline Nery Qualiotto; Tabatha Gutierrez Prieto; Sandra de Morais Fernezlian; Aline Assato; Marcelo Balancin; Teresa Takagaki; Alexandre Ab’Saber; Ana Paula Pereira Velosa; Walcy Rosolia Teodoro; Vera Luiza Capelozzi (Glycoconjugate Journal, 2025)

Crown Exposure Regulates Aboveground Wood Productivity Responses to Soil Fertility in Lowland Tropical Forests - José A. Medina‐Vega; Álvaro Duque; Daniel Zuleta; Nicolás Castaño; Renato Valencia; Salomón Aguilar; David Mitre; Rolando Pérez; Shawn K. Y. Lum; David F. R. P. Burslem; Michael J. O'Brien; Glen Reynolds; et al. (Ecology Letters, 2025)
Understanding the drivers of aboveground wood productivity (AWP) in tropical forests is crucial for explaining ecosystem functioning and predicting their responses to environmental change. While climatic water availability is a well‐established driver, the role of soil nutrients and their interaction with other resources remains uncertain. We investigated how soil nutrients and light interactions shape AWP in lowland tropical forests using fine‐scale soil and tree (≥ 1 cm DBH) data from 15 large forest plots. Canopy‐exposed trees are nutrient‐limited, with AWP increasing more with phosphorus (P) than with potassium (K), indicating P's greater role in plant growth and productivity. Conversely, understory AWP declined in fertile areas, likely due to intensified size‐asymmetric competition. At the population level (mean across canopy layers), no relationship between soil nutrients and AWP emerged because contrasting responses among layers offset any overall association. Our results suggest that fine‐scale heterogeneity and canopy stratification drive nutrient effects on tropical forest productivity.

Experimental assessment of beauvericin toxicity in tadpoles of Dendropsophus minutus (Anura: Hylidae) - Monica Chacon de Vicente; Luiza Gabriella Ferreira de Paula; Renata Maria Pereira de Freitas; Adieli dos Anjos Almeida; Diego da Silva Lima; Rebeca dos Santos Gabriel; Nathany Geraldino Nogueira; Nádya Raquel dos Santos Batista; Alexandre Có Mangoni Barros; Marcelino Benvindo de Souza; Rogério Pereira Bastos; Pedro Vale de Azevedo Brito; et al. (Toxicon, 2025)

Sustainable agriculture with cyanobacterial biomass: Soil experiments on spinach and radish plants - Anabella Massa; Diogo Martins; Joana Azevedo; Ana I. Prieto; Ana M. Camean; Leticia Diez-Quijada; Angeles Jos; Mariana Reimão; Rui Azevedo; Edgar Pinto; Agostinho Almeida; Vitor Vasconcelos; et al. (Science of The Total Environment, 2025)

Combining wood traits as a promising timber origin verification and its application in the Brazilian trade chain - Bruna Hornink; Daigard Ricardo Ortega-Rodriguez; Deoclecio J. Amorim; Peter Groenendijk; Kathelyn Paredes-Villanueva; José Guilherme Roquette; Ana Carolina M.C. Barbosa; Edson Vidal; Alexandre Bahia Gontijo; Monique S. Costa; Norma Rodrigues Nunes de Senna; Davi Neves de Lemos; et al. (Science of The Total Environment, 2025)

New palaeoecological insights for the early human occupation in Europe: amphibians and reptiles from the Early Pleistocene of Pirro Nord 13 (Apricena, southern Italy) - Christian Sánchez-Bandera; Hugues-Alexandre Blain; Josep Francesc Bisbal-Chinesta; Ana Fagoaga; Marco Pavia; Massimo Delfino (Quaternary Science Reviews, 2025)

Enriching BIM-BEPS workflows to support natural ventilation simulations using AirflowNetwork - Liége Garlet; Carlos Alexandre Dias; James O’Donnell; Ana Paula Melo (Energy and Buildings, 2025)

Substituting grass hay and ground corn with forage cactus genotypes on mineral status of lambs - Luiz Carlos Leal Torres; Tomás Guilherme Pereira da Silva; Ricardo Alexandre Silva Pessoa; Roberto Germano Costa; Daurivane Rodrigues Sousa; Ângela Maria Vieira Batista; Diana Valadares Pessoa; Ihasmyn dos Santos Nunes; Ana Paula Silveira Paim; Dorgival Morais de Lima Júnior; Pierre Castro Soares; Francisco Fernando Ramos de Carvalho (Tropical Animal Health and Production, 2025)

Aerobic exercise training combined with enalapril treatment improves obesity-induced brown adipose tissue whitening - Gabriela Rodrigues Medeiros; Luiza França Losito; Ana Beatriz Proença; Guilherme Santos Reis; Nathalia Silva Carlos Oliveira; D’Angelo Carlo Magliano; Beatriz Alexandre-Santos; Antonio Claudio Lucas Nóbrega; Eliete Dalla Corte Frantz (Journal of Physiology and Biochemistry, 2025)

Multiple tools to investigate the origin of the exotic species Chinook salmon Oncorhynchus tshawytscha ( W albaum, 1792) ( S almonidae) in the world's largest chocked coastal lagoon - Yan Gonçalves Gowert; Valéria Marques Lemos; Fabiano Corrêa; Sabrina Vollrath; João Paes Vieira; Mario Vinicius Condini; Rodrigo Ferreira Bastos; Mylla Carla Cescon Freire; Ana Paula Cazerta Farro; Antonio Sergio Varela Junior; Cristiano Albuquerque; Maurício Hostim‐Silva; et al. (Journal of Fish Biology, 2025)
Salmonid species have increasingly been established in South America for aquaculture and recreational fishing purposes. This study provides the first scientific record of the Chinook salmon ( Oncorhynchus tshawytscha ) in the Patos Lagoon (32°S), the world's largest choked coastal lagoon. The specimen was a female with 770 mm (total length), 3992.1 g, estimated age of 6 years and an advanced sexual maturation stage. Based on multiple tools (DNA barcoding, stable isotopes in eye lens, otolith growth layers and egg's histological analysis), we discussed potential entry routes for this species into the lagoon.

Hyperactive Otolith-Ocular Reflex During Heat Tilt (Rabbit’s Eye Sign) In Anti-Ma2 Rhombencephalitis - João Lemos; Sara Matos; Ana Inês Martins; João Durães; Alexandre Dionísio; Egídio Machado; André Jorge (The Cerebellum, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Antioxidant potential and phytochemical analysis of an infusion obtained from the leaves of Talisia esculenta - Katia Castanho Scortecci; Maria Lúcia da Silva Cordeiro; Leticia Barbosa Santos; Verônica Giuliani de Queiroz Aquino Martins; Ariana Pereira da Silva; Weslley de Souza Paiva; Hasan Karimi; Ana Carolina Luchiari; Hugo Alexandre Oliveira Rocha; Fabio Boylan (Phytochemistry Letters, 2025)

The legacy and future of multiple anthropogenic stressors: Organohalogen compounds in the vulnerable Guiana dolphin (Sotalia guianensis) - Nara de Oliveira-Ferreira; Elitieri B. Santos-Neto; Bárbara M.R. Manhães; Monizze Vannuci-Silva; Adriana Castaldo Colosio; Hernani Gomes da Cunha Ramos; Ian Augusto Gusman Cunha; Lupércio Araújo Barbosa; Ana Paula Cazerta Farro; Drienne Messa Faria; Haydée A. Cunha; Tatiana L. Bisi; et al. (Journal of Hazardous Materials, 2025)

Chronic exposure to bisphenol S impairs hepatic mitochondrial dynamics, induces endoplasmic reticulum stress, and worsens metabolism in high-fat diet fed mice - Emanuelle Barreto-Reis; Vinicius Sepúlveda-Fragoso; Luiza Gil Diniz; Débora Júlia Silva Soares; Thaís de Souza Carvalho-Laureano; Ana Paula de Paula Alves; Beatriz Gouvêa de Luca; Beatriz Alexandre-Santos; Milena Barcza Stockler-Pinto; Denise Pires de Carvalho; Eliete Dalla Corte Frantz; Leandro Miranda-Alves; et al. (Environmental Pollution, 2025)

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Comparative analysis of sperm selection methods and their impact on in vitro fertility in the red-rumped agouti (Dasyprocta leporina) - Lhara Ricarliany Medeiros de Oliveira; Leonardo Vitorino Costa de Aquino; Antonia Beatriz Mendonça Pereira; Ana Lívia Rocha Rodrigues; Luanna Lorenna Vieira Rodrigues; Luana Grasiele Pereira Bezerra; Moacir Franco de Oliveira; Alexandre Rodrigues Silva; Alexsandra Fernandes Pereira (Research in Veterinary Science, 2025)

Networks of interactions between Marine Protected Areas and their effects on the conservation of the South American sea lion and the Southern right whale in the Western South Atlantic Ocean - Lorena Oliveira do Nascimento; Cleverson Zapelini; Julián Olaya-Restrepo; Ana Cinti; Guillermo Chalar; Rodrigo Machado; Alexandre Schiavetti (Journal of Environmental Management, 2025)

Ontogenic, Immunological, and Behavioral Changes of Crack Cocaine Exposure During the Gestational Period - Yngrid Mickaelli Oliveira dos Santos; Igor Santana-Melo; Amanda Larissa Dias Pacheco; Milenna Maria Jatoba Hasten Reiter; Maisa de Araújo Costa; Keyla Silva Nobre Pires; Fernanda Maria Araújo de Souza; Jucilene Freitas-Santos; Mayara Rodrigues Barbosa; Jeferson Santana Ursulino; Marvin Paulo Lins; Rayssa Gabriely Duarte Torres; et al. (Molecular Neurobiology, 2025)

Correction: Tetramethylpyrazine alleviates hepatic fibrosis induced by experimental mansonic schistosomiasis - Ana Carolina Campos dos Santos; Daniel Figueiredo-Vanzan; Josiane Bentes; Juliana Maria Motta; Hilton Antônio Mata-Santos; Alexandre dos Santos Pyrrho; Morgana Teixeira Lima Castelo-Branco (Inflammopharmacology, 2025)

Microbial communities in the rhizosphere of tropical soils cultivated with maize as a function of nitrogen and phosphorus fertilizers - Ana Carolina Benites Aquino; Lucas William Mendes; Thierry Alexandre Pellegrinetti; Luís Reynaldo Ferracciú Alleoni (Brazilian Journal of Microbiology, 2025)

Engaging and legitimizing communities: co-designing a community-based Marine Protected Area - Mafalda Rangel; Barbara Horta e Costa; Mª Helena Guimarães; Adriana Ressurreição; Pedro Monteiro; Frederico Oliveira; Luís Bentes; Nuno Sales Henriques; Inês Sousa; Sofia Alexandre; João Pontes; Carlos ML Afonso; et al. (Marine Policy, 2025)

New paleoecological insights for the Late Pleistocene Neanderthal mountain occurrence at Buena Pinta Cave (Iberian Central System, Pinilla-del-Valle, Madrid, Spain) - Hugues-Alexandre Blain; César Laplana; Christian Sánchez-Bandera; Clara Mielgo; Ángel Blanco-Lapaz; Rafael Marquina-Blasco; Ana Fagoaga; Josep Francesc Bisbal-Chinesta; David Manuel Martín-Perea; Christophe Falguères; Tom Higham; Maria Blanca Ruiz Zapata; et al. (Quaternary Science Reviews, 2025)

Dietary supplementation with açai (Euterpe oleracea) improved the haemato-immunological parameters and growth performance of koi carp (Cyprinus Carpio Linnaeus, 1758) - Alexandre Vaz da Silva; Emilly Monteiro Lopes; Domickson Silva Costa; Gracienhe Gomes dos Santos; Caio Francisco Santana Farias; Paola Capistrano dos Santos; Ana Paula de Souza; Gabriele Bueno dos Anjos; Manoela Clemente Fernandes; Arlene Sobrinho Ventura; Claudia Andrea Lima Cardoso; Marco Shizuo Owatari; et al. (Veterinary Research Communications, 2025)

Sulfated polysaccharides of Caulerpa cupressoides var. flabellata: An investigation into their antioxidant properties and biocompatibility - Pablo Felipe Ferreira Farias; Victor Moraes Rodrigues; Augusto Monteiro de Souza; Douglas Dourado Oliveira; Ana Carolina Luchiari; Hugo Alexandre Oliveira Rocha; Susana Margarida Gomes Moreira (Journal of Applied Phycology, 2025)

Integrated microalgae biorefinery using produced water: Simultaneous obtaining of biomass, biofuels and exopolysaccharides - Bianca Bomfim Andrade; Carolina Oliveira de Souza; Natália Hlavnicka Miranda; Jadson dos Santos França; Ana Teresa Lombardi; Silvana Mattedi e Silva; Denilson de Jesus Assis; Jania Betania Alves da Silva; Fabio Alexandre Chinalia; Lucas Guimarães Cardoso (Algal Research, 2025)

Exposure to a contaminated environment and its relationship with human health: Mercury effect on loss of functionality and increased oxidative stress of blood cells - Maiara I.C. Queiroz; Marcos V.S. Sales; Ellen dos Santos Silva Barros; Flávio O.S. D’ Amato; Camilla M. Gonçalves; Jeferson S. Ursulino; Nassib B. Bueno; Chiara Marinho; Ueslen Rocha; Thiago M. Aquino; Eduardo Jorge S. Fonseca; Alexandre U. Borbely; et al. (Journal of Hazardous Materials, 2025)

Synergistic effect of dual pretreatments and temperature gradients on convective drying and preservation of bioactive compounds in purple sweet potato - Gabriel Monteiro da Silva; Rossana Maria Feitosa de Figueirêdo; Alexandre José de Melo Queiroz; Eugênia Telis de Vilela Silva; Henrique Valentim Moura; Aline Priscila de França Silva; Newton Carlos Santos; Yaroslávia Ferreira Paiva; Francislaine Suelia dos Santos; Inácia dos Santos Moreira; Ana Regina Nascimento Campos (Food and Bioproducts Processing, 2025)

Environmental Correlates of Juvenile Fish (Trachinotus marginatus) in a Marine Surf-Zone Revealed ENSO Influence and Interannual Declining Trend in Abundance - Ana Luíza Santos Araújo; Ana Carolina Martins; Alexandre Miranda Garcia (Estuaries and Coasts, 2025)

Unlocking biochemical profile of Chaetoceros calcitrans, Cylindrotheca fusiformis, and Nannofrustulum shiloi (Bacillariophyta) for nutritional and added-value applications - Ana S.P. Moreira; Helena R. Rocha; Susana Aveiro; Andreia S. Ferreira; Kayane Oliveira; Alexandra Conde; Marta Coelho; Alexandre M.C. Rodrigues; Natacha Coelho; Hugo Pereira; Ana Gomes; Manuela Pintado; et al. (Algal Research, 2025)

Pulsed light and jabuticaba peel extract for nitrite reduction and quality enhancement in sliced mortadella - Priscila Rossato Fracari; Igor Tomasevic; Ana Guimarães Massia; Denise Adamoli Laroque; Manoela Meira Balzan; Bibiana Alves dos Santos; Alexandre José Cichoski; Roger Wagner; Bruno Augusto Matar Carciofi; Paulo Cezar Bastianello Campagnol (Meat Science, 2025)

Tissue distribution of Ocimum basilicum essential oil in Nile tilapia Oreochromis niloticus after anesthesia - Emilly Monteiro Lopes; Arlene Sobrinho Ventura; Claudia Andrea Lima Cardoso; Alexandre Vaz da Silva; Caio Francisco Santana Farias; Domickson Silva Costa; Ana Paula de Souza; Danilo Vitor Vilhena Batista; Silvia Terra Fontes; Gabriela Tomas Jerônimo; José Luiz Pedreira Mouriño; Maurício Laterça Martins (Veterinary Research Communications, 2025)

Rainiest Spain: amphibians and reptiles from the late Early Pleistocene-age site of El Chaparral (Cádiz) - Christian Sánchez-Bandera; Rafael Marquina Blasco; Josep Francesc Bisbal-Chinesta; Ana Fagoaga; Isabel Cáceres; José María Gutiérrez; Francisco Giles Pacheco; Juan Manuel López-García; Hugues-Alexandre Blain (Palaeobiodiversity and Palaeoenvironments, 2025)

Effects of Phosphate Solubility on Soil P Pools, Nutrition, and Growth of Eucalyptus Over an Eight-Year Rotation - Adam da Cruz Rodrigues; Estela Covre Foltran; Ana Paula Bettoni Teles; Antonio Leite Florentino; Silvio Henrique Menezes Gomes; José Henrique Tertulino Rocha; Paulo Sergio Pavinato; José Henrique Bazani; Alexandre de Vicente Ferraz; José Leonardo de Moraes Gonçalves (Journal of Soil Science and Plant Nutrition, 2025)

Correction: First Transcriptome Analysis of Hepatoblastoma in Brazil: Unraveling the Pivotal Role of Noncoding RNAs and Metabolic Pathways - Talita Ferreira Marques Aguiar; Maria Prates Rivas; Edson Mario de Andrade Silva; Sara Ferreira Pires; Gustavo Dib Dangoni; Taiany Curdulino Macedo; Alexandre Defelicibus; Bruna Durães de Figueiredo Barros; Estela Novak; Lilian Maria Cristofani; Vicente Odone; Monica Cypriano; et al. (Biochemical Genetics, 2025)

First Transcriptome Analysis of Hepatoblastoma in Brazil: Unraveling the Pivotal Role of Noncoding RNAs and Metabolic Pathways - Talita Ferreira Marques Aguiar; Maria Prates Rivas; Edson Mario de Andrade Silva; Sara Ferreira Pires; Gustavo Dib Dangoni; Taiany Curdulino Macedo; Alexandre Defelicibus; Bruna Durães de Figueiredo Barros; Estela Novak; Lilian Maria Cristofani; Vicente Odone; Monica Cypriano; et al. (Biochemical Genetics, 2025)

Low carbon footprint of Nile tilapia farming with recirculation aquaculture - Anderson M. de Melo Júnior; Sarian Kosten; Vitor Luis da C. Duque; Alexandre A.O. Santos; André M. Amado; Laís C. Soranço; Jochem Dreise; Arthur C. Martins; Jonas Nasário; Ana Paula Dalbem Barbosa; Ive S. Muzitano; Giovana M. Cardoso; et al. (Resources, Conservation and Recycling, 2025)

Methane and nitrogen separation by Gas-SMB in activated carbon monoliths manufactured via 3D-printing - Ana Pereira; Rafael O.M. Dias; Daniel Lourenço; Maria João Regufe; Ana Mafalda Ribeiro; Alírio Rodrigues; Alexandre F.P. Ferreira (Chemical Engineering Journal, 2025)

The Role of Ion-Transporting Proteins on Crosstalk Between the Skeletal Muscle and Central Nervous Systems Elicited by Physical Exercise - Judit Borràs Bertomeu; Letícia Paiva Fioravanço; Thiago Rozales Ramis; Douglas Buchmann Godinho; Alexandre Seixas Nascimento; Gabriel Corrêa Lima; Ana Flavia Furian; Mauro Schneider Oliveira; Michele Rechia Fighera; Luiz Fernando Freire Royes (Molecular Neurobiology, 2025)

Tetramethylpyrazine alleviates hepatic fibrosis induced by experimental mansonic schistosomiasis - Ana Carolina Campos dos Santos; Daniel Figueiredo-Vanzan; Josiane Bentes; Juliana Maria Motta; Hilton Antônio Mata-Santos; Alexandre dos Santos Pyrrho; Morgana Teixeira Lima Castelo-Branco (Inflammopharmacology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Disturbances in mitochondrial quality control and mitochondria-lysosome contact underlie the cerebral cortex and heart damage of mucopolysaccharidosis type II mice - Camila Vieira Pinheiro; Rafael Teixeira Ribeiro; Ana Cristina Roginski; Morgana Brondani; Ângela Beatris Zemniaçak; Chrístofer Ian Hernandez Hoffmann; Adriana Fernanda K. Vizuete; Carlos-Alberto Gonçalves; Alexandre Umpierrez Amaral; Moacir Wajner; Guilherme Baldo; Guilhian Leipnitz (Metabolic Brain Disease, 2025)

Reproductive characteristics of Japanese quail hatched from eggs incubated at different temperatures - Alexandre Vinhas de Souza; Ana Patrícia Alves Leão; Carina Fernanda Gomes da Silva; Juliano Vogas Peixoto; Bruna Resende Chaves; Sarah Conceição Andrade; Édison José Fassani; Renata Ribeiro Alvarenga; Márcio Gilberto Zangeronimo (Theriogenology, 2025)

Streamflow prediction based on the soil and water assessment tool in the Pajeú river basin, Brazilian semiarid - Thieres George Freire da Silva; Ana Karlla Penna Rocha; Alanderson Firmino de Lucas; Gabriel Thales Barboza Marinho; Alexandre Maniçoba da Rosa Ferraz Jardim; Luciana Sandra Bastos de Souza; Abelardo Antônio de Assunção Montenegro; Werônica Meira de Souza (Journal of South American Earth Sciences, 2025)

Evaluation of the stability and antimicrobial activity of emulsions loaded with thymol for the post-harvest sanitization of lettuce (Lactuca sativa L) - Daniel Lucino Silva dos Santos; Jeniffer Ferreira de Miranda; Rodney Alexandre Ferreira Rodrigues; Ana Silvia Prata; Nathália Cristina Cirone Silva (Food Bioscience, 2025)

Identification of purinergic system components in the venom of Bothrops mattogrossensis and the inhibitory effect of specioside extracted from Tabebuia aurea - Dhébora Albuquerque Dias; Kamylla Fernanda Souza de Souza; Iluska Senna Bonfá Moslaves; Marcus Vinicius Buri; Denise Caroline Luiz Soares Basilio; Isabelly Teixeira Espinoça; Eduardo Benedetti Parisotto; Saulo Euclides Silva-Filho; Ludovico Migliolo; Jeandre Augusto Otsubo Jaques; Daniel Guerra Franco; Ana Marisa Chudzinski-Tavassi; et al. (Purinergic Signalling, 2025)

Silvopastoral system as a climate-smart alternative for beef production: Enteric methane emission neutralization and animal thermal comfort increase - Henrique B. Brunetti; Patrícia P.A. Oliveira; José R.M. Pezzopane; Alberto C. de C. Bernardi; Alexandre R. Garcia; Alexandre Berndt; André de F. Pedroso; Ana L.J. Lelis; Sérgio R. Medeiros (Agricultural Systems, 2025)

What threats do Brazilian National parks face? - Alícia Helena Torres da Rocha; Jhonatan Guedes-Santos; Felipe Alexandre Santos Vieira; Ana Claudia Mendes Malhado; Richard J. Ladle; Jairo Lizandro Schmitt; Chiara Bragagnolo (Journal for Nature Conservation, 2025)

Analysis of germination and vigor of cashew seeds for germplasm conservation by NMR and uPLC-qTOF-MS/MS based metabolomics - Elenilson Godoy Alves Filho; João Ravelly Alves de Queirós; Oriel Herrera Bonilla; Hilton César Rodrigues Magalhães; Edy Sousa de Brito; Paulo Riceli Vasconcelos Ribeiro; Kirley Marques Canuto; Lorena Mara Alexandre e Silva; Ana Cecília Ribeiro de Castro (Food Research International, 2025)

Microencapsulating Lacticaseibacillus rhamnosus GG by spray drying using pea protein, pectin, and tapioca flour: Probiotic viability, digestibility and thermal stability - Newton Carlos Santos; Raphael Lucas Jacinto Almeida; Shênia Santos Monteiro; Thalis Leandro Bezerra de Lima; Alexandre da Silva Lúcio; Lídia Paloma da Silva Nogueira; Yaroslávia Ferreira Paiva; Mailson Gonçalves Gregório; Ana Carla de Oliveira Brito; Luanna Amado da Silva; Douglas Vinicius Pinheiro de Figueiredo; Rosenildo dos Santos Silva; et al. (Food and Bioproducts Processing, 2025)

Blanching, cooking, and ethanol are effective strategies for preserving biofunctional compounds in purple-fleshed sweet potato powder - Gabriel Monteiro da Silva; Rossana Maria Feitosa de Figueirêdo; Alexandre José de Melo Queiroz; Eugênia Telis de Vilela Silva; Henrique Valentim Moura; Aline Priscila de França Silva; Newton Carlos Santos; Flávia Carolina Alonso Buriti; Ana Júlia de Brito Araújo Carvalho; Marcos dos Santos Lima (Food and Bioproducts Processing, 2025)

Exposure assessment of metals in cave-dwelling bats: Worldwide relevance of local knowledge - Joana Alves; Ana Daniela Sansur Pavón; Daniel Ricardo; António Alves da Silva; Tiago Natal-da-Luz; Rúben Mina; Fernanda Garcia; Paulo Barros; João Alexandre Cabral; José Paulo Sousa (Environmental Pollution, 2025)

Phenotypic traits and genetic diversity of elephant grass for bioenergy purposes - Josefa Grasiela Silva Santana; Rogério Figueiredo Daher; Moisés Ambrósio; Cleudiane Lopes Leite; Ana Kesia Faria Vidal; Rafael Souza Freitas; Maxwel Rodrigues Nascimento; José Antonio Lamônica Netto; João Victor Bousquet Duarte; João Esdras Calaça Farias; Alexandre Gomes de Souza (Genetic Resources and Crop Evolution, 2025)

Molecular detection of respiratory viruses: an observational study on respiratory co-infections in children and adults - Tereza de Jesus Pinheiro Gomes Bandeira; Ana Leticia Sousa de Oliveira; Luis Fernando Pontes Martins; Rodrigo Moreira Matos; Sheryda Raynna Nobre Guedes dos Santos; Mateus Cedro Lopes; Raimundo Tadeu Pires Sobreira; Hermano Alexandre Lima Rocha (Brazilian Journal of Microbiology, 2025)

Landscape fragmentation impacts springtail community assembly in subtropical agroecosystems - Douglas Alexandre; Luís Carlos Iuñes de Oliveira Filho; Dennis Goss-Souza; Ana Carolina Lovatel; Pâmela Niederauer Pompeo; Marcos Benedito Shimalski; Dilmar Baretta; Osmar Klauberg-Filho (Applied Soil Ecology, 2025)

Phew! Roadkill hotspots are not related to protected areas - Jefferson Eduardo Silveira Miranda; Ana Clara Abadia; Alexandre Schiavetti (Biodiversity and Conservation, 2025)

A new genus of Mycosphaerellaceae associated with leaf spots in Philodendron sp. from the Brazilian Atlantic forest - Jordana Alves da Silva Melo; Eliude dos Santos Oliveira da Silva; Amanda Cupertino de Queiroz Brito; Juliana Ferreira de Mello; Ana Elisa de Almeida Souza; Cristina Maria de Souza-Motta; André Luiz Firmino; Alexandre Reis Machado (Mycological Progress, 2025)

Lippia origanoides essential oil increases longevity and ameliorates β-amyloid peptide-induced toxicity in Caenorhabditis elegans - Ana Maria Henrique Moniz; Francisco Humberto Xavier Junior; Giovanna Melo Martins Silva; Ana Cristina Gonçalves Reis de Melo; Maylla Maria Correia Leite Silva; Weslley Souza Paiva; Hugo Alexandre Oliveira Rocha; Luiz Antônio Mendonça Alves da Costa; Antônio Alves de Melo Filho; Riva de Paula Oliveira (Natural Product Research, 2025)

Evaluation of Scalibor® deltamethrin collar chronic exposure in dogs - Larissa T.P. Rodrigues; Andriele F. Qualhato; Carolle V.M. Sprícigo; Kelly C.A. Arantes; Rayanne H.S. da Silva; Alexandre C.M. Barros; Monica C. Vicente; Murilo R. Souza; Luiza G.F. de Paula; Danilo Roman-Campos; Artur S. Miranda; Danieli B. Martins; et al. (Research in Veterinary Science, 2025)

Engineering effects of hydrocolloids on drying kinetics, powder characteristics, and antioxidant preservation in grape powder - Amanda Nascimento; Alexandre Lúcio; Ana Nery; Rogério Andrade; Ana Maria Sarinho; Janaina Lima; Leonardo Batista; Hugo M. Lisboa (Journal of Food Engineering, 2025)

New reports of Rhizopus and Mucor (Mucorales, Mucoromycota) causing post-harvest rot in tropical fruits in Brazil - Ana Elisa de Almeida Souza; André Luiz Cabral Monteiro de Azevedo Santiago; Amanda Cupertino de Queiroz Brito; Jordana Alves da Silva Melo; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Journal of Plant Diseases and Protection, 2025)

Morphology and genetics of non-topotypes Pimelodus platicirris catfish suggest synonymy with P. maculatus - Rafael A. Baggio; Vinicius Abilhoa; Grazielle H. F. de Menezes; Emanuel Razzolini; Ana Carolina Lacerda Rego; Átila Rodrigues de Araújo; Mateus Moreira de Carvalho; Alexandre L. Godinho (Conservation Genetics, 2025)

Assessing the potential of Buriti and Bocaiuva fruit oils as nutritional additives for cattle in the feedlot - Jéssika Rodrigues de Figueiredo Moura; Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Marina de Nadai Bonin Gomes; Alexandre Menezes Dias; Priscilla Dutra Teixeira; Maria Lígia Rodrigues Macedo; Ana Cristina Jacobowski; Rita de Cássia Avellaneda Guimarães; Antonio Leandro Chaves Gurgel; Alexandre Guimarães Inácio; Manoel Gustavo Paranhos da Silva; et al. (Animal Feed Science and Technology, 2025)

DiverReef : A global database of the behavior of recreational divers and their interactions with reefs over 20 years - Vinicius J. Giglio; Johnatas Adelir‐Alves; Natalia Balzaretti Merino; Myrna Leticia Bravo‐Olivas; Emma F. Camp; Edoardo Casoli; Rosa Maria Chávez‐Dagostino; Eliana Ferretti; Douglas Fraser; Ana C. Grillo; Santiago Jiménez‐Guiérrez; Kelen L. Leite; et al. (Ecology, 2025)
Recreational diving is an important activity in reef environments worldwide, providing income and employment for coastal communities and connecting visiting divers to these ecosystems promoting conservation and stewardship. However, if poorly managed, diving has the potential to cause detrimental effects on benthic communities via mechanical damage caused by physical contact of divers with the reef, often in the form of unintentional fin kicks resulting from poor buoyancy. Understanding diver–reef interaction patterns is important to elucidate the potential impacts of diving tourism on the reef biota. The DiverReef database provides the first public dataset on the underwater behavior of recreational divers in shallow reef environments (

First reports of Fusarium agrestense, F. gossypinum, F. grosmichelii and F. triseptatum causing cassava root rot in Pernambuco, Brazil - Jenifer Sthephanie Araujo da Silva; Ana Carla da Silva Santos; Carlos Alberto Fragoso de Souza; Diogo Paes da Costa; Amanda Cupertino de Queiroz Brito; Renan do Nascimento Barbosa; Erika Valente de Medeiros; Alexandre Reis Machado; Cristina Maria de Souza-Motta (Crop Protection, 2025)

Comprehensive analysis of antioxidant, phenolic thermal stability, mineral profile and hygroscopic properties in germinated faba bean flours - Lumara Tatiely Santos Amadeu; Alexandre José de Melo Queiroz; Rossana Maria Feitosa de Figueirêdo; Eugênia Telis de Vilela Silva; Yaroslávia Ferrreira Paiva; Carolaine Gomes dos Reis; João Paulo de Lima Ferreira; Francislaine Suelia dos Santos; Ana Júlia de Brito Araújo Carvalho; Marcos dos Santos Lima; Antônio Daniel Buriti de Macedo; Ana Regina Nascimento Campos (Food Bioscience, 2025)

Beyond the threshold - Different accumulation of organochlorine compounds in common dolphins (Delphinus delphis) inhabiting continental and insular ecosystems in the Northeast Atlantic - Raul Valente; Nara de Oliveira-Ferreira; Rita Ferreira; Ana M. Correia; Bárbara M.R. Manhães; Ágatha Gil; Annalisa Sambolino; Elitieri B. Santos-Neto; L. Filipe C. Castro; Haydée A. Cunha; Alexandre F. Azevedo; Ana Dinis; et al. (Environmental Pollution, 2025)

Molecular detection and phylogenetic analysis of Leptospira interrogans and Leptospira borgpetersenii in cats from Central region of Rio Grande do Sul state, Brazil - Bruna Carolina Ulsenheimer; Alexandre Alberto Tonin; Ana Eucares von Laer; Helton Fernandes dos Santos; Luís Antônio Sangioni; Rafael Fighera; Matheus Yuri dos Santos; Daniela Isabel Brayer Pereira; Luciana Pötter; Sônia de Avila Botton (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Changes in the climatic water budget of an intermittent river in the Brazilian semiarid: trends in cyclical processes and their relation to teleconnection patterns - Thieres George Freire da Silva; Ana Karlla Penna Rocha; Alanderson Firmino de Lucas; Luciana Sandra Bastos de Souza; Abelardo Antônio de Assunção Montenegro; Werônica Meira de Souza; Alexandre Maniçoba da Rosa Ferraz Jardim; Carlos André Alves de Souza; Kaique Renan da Silva Salvador; Ailton Alves de Carvalho; George do Nascimento Araújo Júnior (Theoretical and Applied Climatology, 2025)

Disturbances in mitochondrial bioenergetics and control quality and unbalanced redox homeostasis in the liver of a mouse model of mucopolysaccharidosis type II - Camila Vieira Pinheiro; Rafael Teixeira Ribeiro; Ana Cristina Roginski; Morgana Brondani; Ângela Beatris Zemniaçak; Chrístofer Ian Hernandez Hoffmann; Alexandre Umpierrez Amaral; Moacir Wajner; Guilherme Baldo; Guilhian Leipnitz (Molecular and Cellular Biochemistry, 2025)

Cooling storage of collared peccary (Pecari tajacu) semen at different temperatures - Romário Parente dos Santos; Ana Gloria Pereira; Yuri Gonçalves Matos; Gabriel Santos Costa Bezerra; Lilian Leal Dantas; Alexandre Rodrigues Silva (Animal Reproduction Science, 2025)

Small-scale fisheries in ecologically sensitive areas in Latin America and the Caribbean: Do marine protected areas benefit fisheries governance? - Ana Cinti; Luisa Ramirez; Mauricio Castrejón; Jaime A. Aburto; Luciana Loto; Stuart Fulton; Mario Rueda; Alexandre Schiavetti; Francisco J. Fernández-Rivera Melo; Manuel Bravo; Daniela Trigueirinho Alarcon; Valéria Penchel Araújo; et al. (Ambio, 2025)
Many small-scale fisheries (SSFs) in Latin America and the Caribbean (LAC) operate in ecologically sensitive areas, where balancing conservation and resource use is challenging. 'Multiple-use' marine protected areas (MPAs) have been implemented to accommodate SSFs (among other uses) within areas designated for conservation, creating opportunities and challenges for SSF governance. We analyzed eleven case studies from LAC to explore: (1) how different MPA institutional designs affect key aspects of SSF governance and (2) the links between these effects and the type of initiative that promoted MPA establishment (origin). Results indicate that the existence of an MPA benefited SSF governance in many ways, with more pronounced positive effects in MPAs with mixed to bottom-up origin supported by well-organized fishing groups. In addition, the presence of supportive MPA authorities that leveraged local capacities and initiatives and adopted flexible and collaborative governance systems made a difference in several cases. Lessons for integrating MPA and SSF governance are drawn.

Determination of mometasone furoate solubility, using deep eutectic systems, and topical formulation- experimental and computational studies - Rita Craveiro; Ângelo Rocha; Cláudio Fernandes; Ana Rita C. Duarte; Joana Marto; Alexandre Paiva (Sustainable Chemistry and Pharmacy, 2024)

Comprehensive characterization of European house dust contaminants: Concentrations and profiles, geographical variability, and implications for chemical regulation and health risk - Peter Haglund; Nikiforos A. Alygizakis; Adrian Covaci; Lisa Melymuk; Pernilla Bohlin Nizzetto; Pawel Rostkowski; Alexandre Albinet; Sylvana Alirai; Dagny Aurich; Stefan Bieber; Ana Ballesteros-Gómez; Amanda A. Brennan; et al. (Science of The Total Environment, 2024)

Aerobic performance in rats subjected to incremental-speed running exercise: A multiple regression analysis study emphasizing thermoregulation-related variables - Marcelo T. Andrade; Nicolas H.S. Barbosa; Roberto C.S. Souza-Junior; Cletiana G. Fonseca; William C. Damasceno; Kássya Regina-Oliveira; Lucas R. Drummond; Myla A. Bittencourt; Ana C. Kunstetter; Pedro V.R. Andrade; Alexandre S.R. Hudson; Thales N. Prímola-Gomes; et al. (Journal of Thermal Biology, 2024)

Calibrated models to estimate Referensce evapotranspiration, for the city of Botucatu/Sp, in relation to the weighing lysimeter - Ana Cláudia Marassá Roza Boso; Firmo Sousa Campos; Alexandre Dal Pai (Modeling Earth Systems and Environment, 2024)

Correction: Drug to genome to drug: a computational large-scale chemogenomics screening for novel drug candidates against sporotrichosis - Andressa Santana Santos; Vinícius Alexandre Fiaia Costa; Vivianny Aparecida Queiroz Freitas; Laura Raniere Borges dos Anjos; Eder Soares de Almeida Santos; Thales Domingos Arantes; Carolina Rodrigues Costa; Ana Laura de Sene Amâncio Zara; Maria do Rosário Rodrigues Silva; Bruno Junior Neves (Brazilian Journal of Microbiology, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

In Vivo Test to Evaluate the Cytotoxicity and Genotoxicity of Natural Zeolite (NZ) Functionalized with Silver Nanoparticles (NZ-AgNPs) on Erythrocytes of Yellowtail Tetra Fish Astyanax lacustris - Josiane Rodrigues Rocha da Silva; Camila Oliveira de Andrade; Anna Carla Ribeiro; Paula Derksen Macruz; Elizabeth da Costa Neves FernandesAlmeida Dua; Rosângela Bergamasco; Ana Luiza de Brito Portela-Castro; Carlos Alexandre Fernandes (Biological Trace Element Research, 2024)

Eplingiella fruticosa leaf essential oil complexed with β-cyclodextrin exerts a neuroprotective effect in an Alzheimer’s disease animal model induced by Streptozotocin - Vanessa Alexandre-Silva; Beatriz Soares-Silva; Gabrielle Christine Pereira; Ana Claúdia Custódio-Silva; Patrícia Santos Carvalhinho-Lopes; Luciana Oliveira Taliano; Rafael Herling Lambertucci; Marcelo Duarte Cavalcante; Adriano Antunes de Souza Araújo; Lucindo Quintans-Júnior; José Ronaldo dos Santos; Alessandra Mussi Ribeiro (Metabolic Brain Disease, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

The impact of plant-based product denomination on consumer expectations and sensory perception: A study with vegan chocolate dessert - Alexandre Henrique Silas Souza; Katiúcia Alves Amorim; Louise Paiva Passos; Maria Laura Silva Galdino; Júlia Fernanda Urbano Marinho; Juliana Santos Marques; Karen Lendengue de Matos Regalado; Ana Carla Marques Pinheiro (Food Research International, 2024)

Diving into the metabolic interactions of titanium dioxide nanoparticles in “Sparus aurata” and “Ruditapes philippinarum” - Mário Jorge Araújo; María Vazquez; Laura Rodriguez-Lorenzo; Antonio Moreda-Piñeiro; Elza Fonseca; Natalia Mallo; Ivone Pinheiro; Monica Quarato; Elizabeth Bigorra-Ferré; Ana Matos; Aldo Barreiro-Felpeto; Maria V. Turkina; et al. (Environmental Pollution, 2024)

Integrated systems for the production of food, energy and materials as a sustainable strategy for decarbonization and land use: The case of sugarcane in Brazil - Fabio Teixeira Ferreira da Silva; Mateus Schreiner Garcez Lopes; Laura Makiko Asano; Gerd Angelkorte; Ana Karina Brambilla Costa; Alexandre Szklo; Roberto Schaeffer; Paulo Coutinho (Biomass and Bioenergy, 2024)

Productivity and economic performance of Nellore young bulls fed diets with increasing fiber content - Caroline Ferreira Medeiros; Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Alexandre Menezes Dias; Vanessa Zirondi Longhini; Gelson dos Santos Difante; Priscilla Dutra Teixeira; Manoel Gustavo Paranhos da Silva; Rafael Goes Cardoso Paro; Ana Hellen da Silva; Laura Beatriz Perez da Silva (Tropical Animal Health and Production, 2024)

ER stress improvement by aerobic training or enalapril differently ameliorates pathological cardiac remodeling in obese mice - Amanda Conceição Pimenta Salles; Beatriz Alexandre-Santos; Thais de Souza Carvalho; Ana Beatriz Proença; Vinicius Sepúlveda-Fragoso; Tiago Fernandes; Edilamar Menezes Oliveira; Antonio Claudio Lucas da Nóbrega; Eliete Dalla Corte Frantz; D’Angelo Carlo Magliano (Molecular and Cellular Biochemistry, 2024)

Antimicrobial and anthelmintic effects of copper nanoparticles against Koi carp parasites and their toxicity - Gracienhe Gomes dos Santos; Liseth Vanessa Perengue Riofrio; Ana Paula Sousa; Paola Capistrano Santos; Alexandre Vaz Silva; Emilly Monteiro Lopes; Domickson Silva Costa; Jucimauro de Araújo Pereira Júnior; Giulia Beatrice Ferreira; Graziella Vivine Gonçalves de Matos Silva; Marilia Tedesco; Diego José Nogueira; et al. (Journal of Fish Diseases, 2024)
This study investigated the in vitro antimicrobial and anthelmintic effect of copper nanoparticles (CuNPs) against the bacterium Aeromonas hydrophila , the monogeneans Dactylogyrus minutus , Dactylogyrus extensus , Gyrodactylus cyprini , and the cestode Schyzocotyle acheilognathi , as well as their toxicity to Cyprinus carpio Koi. In the antimicrobial in vitro test, the inhibition zone method and minimum inhibitory concentration (MIC) were performed. In order to determine the time and efficacy of monogenean parasite mortality, the parasites were exposed to CuNP concentrations of 20, 50, 100, 150, 200, and 300 mg L −1 , and a control group with tank water and one with copper sulphate pentahydrate (CuSO 4 . 5 H 2 O) at a concentration of 0.3 mg L −1 , performed in triplicate. The parasites were observed every 10 min for 300 min, and mortality was recorded. For the cestodes, parasites were immersed in CuNP concentrations of 50, 100, 150, and 300 mg L −1 . At the end of the in vitro tests, the anthelmintic efficacy of each treatment was calculated. To assess the tolerance and toxicity in fish, they were exposed to CuNP concentrations of 0.6, 1.25, 2.5, 5, 10, 20, and 50 mg L −1 for 12 h. The MIC demonstrated that CuNPs effectively inhibited the growth of A . hydrophila up to a dilution of 12,500 mg L −1 and showed an inhibition zone of 14.0 ± 1.6 mm for CuNPs. The results of anthelmintic activity showed a dose‐dependent effect of concentration for both groups of parasites, with the most effective concentration being 300 mg L −1 in 120 min. In the toxicity test, the carps showed tolerance to lower concentrations. The study indicated that CuNPs were effective against the studied pathogens. However, it proved to be toxic to fish at high concentrations. The use of low concentrations is recommended still requires further investigation.

Temporal dominance of Sensations: Do different concepts of “dominance” affect the results? - Katiúcia Alves Amorim; Louise Paiva Passos; Alexandre Henrique Silas Souza; Vinícius dos Santos Cardoso; Rita de Cássia Vieira; Milene de Souza Campos; Jéssica Ferreira Rodrigues; Cleiton Antônio Nunes; Ana Carla Marques Pinheiro (Food Research International, 2024)

Fertirrigation in grafted Pinus pinea L. trees: denser crowns but no effect on cone production or masting cycles - Alexandra Cristina Correia; Ana Farinha; João E.P. Silva; Alexandra Nunes; Nuno Conceição; Maria da Encarnação Marcelo; Alexandre Sarmento; Margarida Tomé; João Soares; Luis Fontes (Forest Ecology and Management, 2024)

Exploring the biological properties and bioaccessibility of orange peel extracts using deep eutectic systems - Adriana Viñas-Ospino; Isabel Sá-Nogueira; Ana Rita Duarte; Daniel López-Malo; María José Esteve; Ana Frígola; Jesús Blesa; Alexandre Paiva (Food Bioscience, 2024)

Improving preservation of bioactive compounds in mangosteen peel flour through pre-treatment with bleaching, ethanol, and vacuum pulse - Eugênia Telis de Vilela Silva; Alexandre José Melo de Queiroz; Rossana Maria Feitosa de Figueirêdo; Henrique Valentim Moura; Aline Priscila de França Silva; Gabriel Monteiro da Silva; Inácia dos Santos Moreira; Marcos dos Santos Lima; Ana Julia de Brito Araújo; Francislaine Suelia dos Santos (Food Bioscience, 2024)

Zoogeographical regions in the Atlantic Forest: patterns and potential drivers - Fernando Rodrigues da Silva; Anna Elizabeth de Oliveira‐Silva; Alexandre Antonelli; Ana Carolina Carnaval; Diogo B. Provete (Journal of Biogeography, 2024)
Aim To delineate present‐day zoogeographical regions of terrestrial vertebrates (frogs, lizards, snakes, birds and non‐volant mammals) in the Atlantic Forest. Within each taxonomic group, we examine the relative importance of abrupt climatic transitions, orographic barriers, past climate change and rivers in shaping zoogeographical boundaries. Location South America's Atlantic Forest. Methods We applied a network‐based method to delineate zoogeographical regions, using distribution data (range maps) for 455 species of frogs, 103 lizards, 220 snakes, 917 birds and 202 non‐volant mammals, in 50 × 50 km grid cells. We used hierarchical generalized linear mixed‐effects models to test environmental predictors associated with zoogeographical boundaries. Finally, we intersected the bioregion maps delineated for each group to identify general patterns across all vertebrates. Results We identified four zoogeographical regions for birds and snakes, and five for frogs, lizards and non‐volant mammals. Depending on the group, contemporary and past climate conditions, elevation variation and/or rivers were associated with zoogeographical boundaries. The combined maps indicate that the Atlantic Forest retains four spatially cohesive zoogeographical regions based on present‐day distribution of vertebrates. Main conclusions Cross‐taxon congruence indicates that the geographical and environmental characteristics of the Atlantic Forest have a strong influence on the location of zoogeographical regions for vertebrates. In contrast, transition zones appear to be associated with the spatial distribution of life history traits of each group, potentially explaining the observed differences in the number of bioregions across groups and the position of zoogeographical boundaries. This work paves the way for further research into the evolutionary assembly of the Atlantic Forest's zoogeographical regions and may help inform conservation priorities for maintaining their distinctive faunas.

Orange (Citrus sinensis) essential oil inclusion in high-energy diets for feedlot lambs: productivity, eating behavior, carcass characteristics, rumen morphometry, and fatty acid profile of the meat - Paulo César G. Dias Junior; Adrielly L.A. da Silva; Isabela J. dos Santos; Leticia C.B. Soares; Matheus S.P. Carlis; Ana Carolina S. Vicente; Terezinha T. de Souza; Rhaissa G. de Assis; Janaina S. Biava; Simon Quigley; Alexandre V. Pires; Evandro M. Ferreira (Small Ruminant Research, 2024)

Recent deep-sea nematodes and agglutinated foraminifera select specific grains and bioclasts from their environments: Ecological implications - Sunil K. Das; Raj K. Singh; Mariem Saavedra-Pellitero; Julia Gottschalk; Carlos A. Alvarez Zarikian; Lester Lembke-Jene; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; Chandranath Basak; Anieke Brombacher; et al. (Marine Micropaleontology, 2024)

Do different densities and planting orientations of forage cactus alter agronomic, morphophysiological characteristics, and soil water dynamics in a semiarid region? - Gabriel Italo Novaes da Silva; José Edson Florentino de Morais; Carlos André Alves de Souza; Alexandre Maniçoba da Rosa Ferraz Jardim; Cléber Pereira Alves; Kaique Renan da Silva Salvador; Luciana Sandra Bastos de Souza; Adriano do Nascimento Simões; Fleming Sena Campos; Antonio José Steidle Neto; Ana Virgínia Marinho Silveira; Abelardo Antônio de Assunção Montenegro; et al. (European Journal of Agronomy, 2024)

Soil Phosphorus Dynamics under Long-Term No-Till with Offseason Intercropping Systems - João Paulo Gonsiorkiewicz Rigon; Rafael Gonçalves Vilela; Ana Paula Bettoni Teles; Leila Bernart; Paulo Sérgio Pavinato; Juliano Carlos Calonego; Carlos Alexandre Costa Crusciol (Journal of Soil Science and Plant Nutrition, 2024)

Drug to genome to drug: a computational large-scale chemogenomics screening for novel drug candidates against sporotrichosis - Andressa Santana Santos; Vinícius Alexandre Fiaia Costa; Vivianny Aparecida Queiroz Freitas; Laura Raniere Borges dos Anjos; Eder Soares de Almeida Santos; Thales Domingos Arantes; Carolina Rodrigues Costa; Ana Laura de Sene Amâncio Zara; Maria do Rosário Rodrigues Silva; Bruno Junior Neves (Brazilian Journal of Microbiology, 2024)

Microcystin-degrading bacteria reduce bioaccumulation in Fragaria vulgaris and enhance fruit yield and quality - Mohammed Haida; Fatima El Khalloufi; Yasser Essadki; Diogo A. M. Alexandrino; Richard Mugani; Abdessamad Hejjaj; Alexandre Campos; Vitor Vasconcelos; Maria F. Carvalho; Leticia Díez-Quijada; Ana M. Cameán; Brahim Oudra (Environmental Science and Pollution Research, 2024)
In Morocco, red fruit production has thrived, primarily utilizing hydroponic methods to control crops, increase fruit yield and quality, and avoid soil-related problems. However, the irrigation of these expansive hydroponic farms relies heavily on water sourced from dams, many of which are contaminated with Microcystins (MCs). To address this contamination issue, ongoing research is focused on discovering effective and cost-efficient biological solutions for eliminating MCs. In this study, we isolate and identify bacterial strains capable of degrading MCs, evaluate the rate of degradation, and investigate how soil inoculated with these bacteria affects the accumulation of MCs in plant tissue. The partial 16S rRNA analyses of three bacterial sequences were conducted, identifying them through NCBI as follows: Ensifer sp. (B1) isolated from soil, Shinella sp. (B2) from a cyanobacterial bloom, and Stutzerimonas sp. (B3) from water. These bacteria exhibited the ability to degrade MCs, with approximately 34.75%, 73.75%, and 30.1% of the initial concentration (20 µg/L) being removed after a 6-day period for B1, B2, and B3, respectively. Moreover, strawberry plants were cultivated hydroponically in a greenhouse for a duration of 90 days. These plants were subjected to extracts of cyanobacteria containing 10 and 20 µg/L of Microcystins (MC), as well as water from an artificial lake contaminated with MC, both with and without the presence of isolated bacterial strains. Among these strains, Shinella sp. exhibited the highest efficacy in mitigating MC accumulation. Specifically, it resulted in a reduction of approximately 1.159 µg of MC per kilogram of root dry weight, leading to complete elimination in the leaves and fruits. The findings also indicated that the inoculation of perlite with the three MC-degrading bacterial strains significantly enhanced growth, photosynthetic pigments, yield, biochemical constituents, and quality attributes of strawberries (p ≤ 0.05). These promising outcomes suggest the potential of this approach for addressing the adverse impacts of crops irrigated with MC-contaminated water in future agricultural practices.

Relationship between season and spermatozoa traits of captive-reared agoutis from Brazilian semiarid - Maiko Roberto Tavares Dantas; Luana Grasiele Pereira Bezerra; Ana Glória Pereira; Romário Parente dos Santos; João Batista Freire Souza-Junior; Leonardo Lelis de Macedo Costa; Alexandre Rodrigues Silva (Environmental Science and Pollution Research, 2024)

Late Miocene to Early Pliocene paleoceanographic evolution of the Central South Pacific: A deep-sea benthic foraminiferal perspective - Sunil K. Das; N. Mahanta; B. Sahoo; Raj K. Singh; Carlos A. Alvarez Zarikian; Manish Tiwari; Nishant Vats; Nihal; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Ten years of directing seeding restoration in the Brazilian savanna: Lessons learned and the way forward - Ana Wiederhecker; Maxmiller Cardoso Ferreira; Silvia Barbosa Rodrigues; Alexandre Bonesso Sampaio; Isabel Belloni Schmidt; José Felipe Ribeiro; Roberto Shojirou Ogata; Maísa Isabela Rodrigues; Augusto Cesar Silva-Coelho; Icaro Sousa Abreu; Thaís Franco Montenegro; Daniel Luis Mascia Vieira (Journal of Environmental Management, 2024)

Association of emojis to the five basic tastes (sweet, salty, sour, bitter and umami) - Lenízy Cristina Reis Rocha; Louise Paiva Passos; Alexandre Henrique Silas Souza; Katiúcia Alves Amorim; Jéssica Ferreira Rodrigues; Ana Carla Marques Pinheiro (Food Quality and Preference, 2024)

Long-term administration of omeprazole in mice: a study of behavior, inflammatory, and oxidative stress alterations with focus on central nervous system - Dulce Maria Nascimento Coelho; Dilailson Carlos Costa Júnior; Daniel Moreira Alves da Silva; Ana Carolina Benício Alves; Raquell de Castro Chaves; Manoela de Oliveira Rebouças; José Tiago Valentim; Andressa Alexandre de Oliveira; Iardja Stefane Lopes Sales; Lucas Antonio Duarte Nicolau; Francisca Cléa Florenço de Sousa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Lightning-induced fire regime in Portugal based on satellite-derived and in situ data - Lucas S. Menezes; Ana Russo; Renata Libonati; Ricardo M. Trigo; José M.C. Pereira; Akli Benali; Alexandre M. Ramos; Célia M. Gouveia; Carlos A. Morales Rodriguez; Ricardo Deus (Agricultural and Forest Meteorology, 2024)

Oil Spill Mitigation with a Team of Heterogeneous Autonomous Vehicles - André Dias; Ana Mucha; Tiago Santos; Alexandre Oliveira; Guilherme Amaral; Hugo Ferreira; Alfredo Martins; José Almeida; Eduardo Silva (Journal of Marine Science and Engineering, 2024)
This paper presents the implementation of an innovative solution based on heterogeneous autonomous vehicles to tackle maritime pollution (in particular, oil spills). This solution is based on native microbial consortia with bioremediation capacity, and the adaptation of air and surface autonomous vehicles for in situ release of autochthonous microorganisms (bioaugmentation) and nutrients (biostimulation). By doing so, these systems can be applied as the first line of the response to pollution incidents from several origins that may occur inside ports, around industrial and extraction facilities, or in the open sea during transport activities in a fast, efficient, and low-cost way. The paper describes the work done in the development of a team of autonomous vehicles able to carry as payload, native organisms to naturally degrade oil spills (avoiding the introduction of additional chemical or biological additives), and the development of a multi-robot framework for efficient oil spill mitigation. Field tests have been performed in Portugal and Spain’s harbors, with a simulated oil spill, and the coordinate oil spill task between the autonomous surface vehicle (ASV) ROAZ and the unmanned aerial vehicle (UAV) STORK has been validated.

Indium(III) complexes with lapachol: cytotoxic effects against human breast tumor cells and interactions with DNA - Alexandre B. de Carvalho; Ana M. S. Souza; Larissa Pereira Bento; Mariana de Oliveira Silva; Elaine M. Souza-Fagundes; Renata Diniz; Heloisa Beraldo (JBIC Journal of Biological Inorganic Chemistry, 2024)

The effect of acute exposure of yellowtail tetra fish Astyanax lacustris (Lütken, 1875) to the glyphosate-based herbicide Templo® - Camila Oliveira de Andrade; Josiane Rodrigues Rocha da Silva; Pablo Americo Barbieri; Luciana Andrea Borin-Carvalho; Ana Luiza de Brito Portela-Castro; Carlos Alexandre Fernandes (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

The role of time to positive blood cultures in enhancing the predictive capability of DENOVA score for diagnosing infective endocarditis in patients with Enterococcus faecalis bacteremia - M Teresa Pérez-Rodríguez; Olalla Lima; Martín Garrido; Anniris Rincón; Lucía Martínez-Lamas; Alexandre Pérez-González; Alejandro Araújo; Antía Amoedo; Adrián Sousa; Ana López; Xurxo Cabrera; Martín Rubianes (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Trophic ecology and small‐scale differentiation of ecological groups of franciscana dolphin, Pontoporia blainvillei , in southeastern Brazil, revealed by carbon and nitrogen stable isotopes - Pedro H. O. Teixeira; Gleici Montanini; Ana P. C. Farro; Adriana C. Colosio; Hernani G. C. Ramos; Lupércio A. Barbosa; Ian A. G. Cunha; Maurício Hostim‐Silva; Alexandre F. Azevedo; Haydée A. Cunha; José Lailson‐Brito; Tatiana L. Bisi (Marine Mammal Science, 2024)
The franciscana, Pontoporia blainvillei, is an endemic dolphin off the east coast of South America and is considered the most endangered cetacean in the western South Atlantic. In the present study, we analyzed the muscle tissue of 24 franciscana dolphins found on the coast of Espírito Santo (ES) between 2010 and 2019 to investigate trophic ecology using carbon and nitrogen stable isotope analysis. In addition, 127 prey were analyzed to identify the preferred prey. The most important prey species in the diet of the franciscana dolphins were Trichiurus lepturus , Chirocentrodon bleekerianus , and Pellona harroweri . The franciscana dolphins were grouped into three subareas according to where they were collected throughout the distribution: 1 (North), 2 (Center), and 3 (South). In subarea 1, the preferred prey were Stellifer spp., Isopisthus parvipinnis, and P. harroweri , while in subareas 2 and 3, the prey were similar, changing the order of preference among them ( Stellifer spp., T. lepturus, and C. bleekerianus ). Finally, we identify two possible ecological groups of franciscana dolphins on the coast of ES, influenced by different carbon sources. Our results improve our understanding of the franciscana dolphin's trophic ecology and habitat use, providing new information and guidelines for species conservation in the region.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Chemical composition and anti-proliferative activity of essential oils from some medicinal plants from Cachicadán, Región La Libertad, Perú - Eveleny Tirsa Vaca Meza; Jorge Vasquez-Kool; Noé Ildefonso Costilla Sánchez; Amandio Vieira; Rodney Alexandre Ferreira Rodrigues; Adilson Sartoratto; Angela del Pilar Flores Granados; Carmen Luisa Marin Tello; Ana Lucia Tasca Gois Ruiz (Natural Product Research, 2024)

Comparison of green solvents for the revalorization of orange by-products: Carotenoid extraction and in vitro antioxidant activity - Adriana Viñas-Ospino; Ana Rita Jesus; Alexandre Paiva; Maria J Esteve; Ana Frígola; Jesús Blesa; Daniel López-Malo (Food Chemistry, 2024)

Hidden ecotoxicological dangers: Investigating pathogen circulation and non-toxic risks hazards in a crucial brazilian watershed - Milena Roberta Freire da Silva; Karolayne Silva Souza; Francisco Henrique Santana da Silva; Milena Danda Vasconcelos Santos; Bruno Oliveira de Veras; Iago José Santos da Silva; Fabricio Motteran; Ana Carolina de Oliveira Luz; Tereza Cristina Leal Balbino; Lívia Caroline Alexandre de Araújo; Guilherme Malafaia; Maria Betânia Melo de Oliveira (Aquatic Toxicology, 2024)

Leptospira borgptersenii and Leptospira interrogans identified in wild mammals in Rio Grande do Sul, Brazil - Bruna Carolina Ulsenheimer; Alexandre Alberto Tonin; Ana Eucares von Laer; Helton Fernandes dos Santos; Luís Antônio Sangioni; Rafael Fighera; Matheus Yuri dos Santos; Daniela Isabel Brayer; Sônia de Avila Botton (Brazilian Journal of Microbiology, 2024)

Genomic insights of Fictibacillus terranigra sp. nov., a versatile metabolic bacterium from Amazonian Dark Earths - Thierry Alexandre Pellegrinetti; Izadora de Cássia Mesquita da Cunha; Miriam Gonçalves de Chaves; Anderson Santos de Freitas; Gabriel Schimmelpfeng Passos; Ana Vitória Reina da Silva; Simone Raposo Cotta; Siu Mui Tsai; Lucas William Mendes (Brazilian Journal of Microbiology, 2024)

Comparison between commercial media and TRIS-egg yolk extender in the refrigerated storage of collared peccary semen at 17 °C - Romário P. Santos; Samara S.J. Moreira; Luana G.P. Bezerra; Yasmim C.S. Cavalcante; Ana G. Pereira; Tayná M. Matos; Moacir F. Oliveira; Alexandre R. Silva (Animal Reproduction Science, 2024)

Prevalence of cagA, cagM, vacA and oipA genes in isolates of Helicobacter pylori obtained from hospital patients in Northeast Brazil - Thaynara Millena de Oliveira Bezerra; Keyla Vitória Marques Xavier; Ana Carolina de Oliveira Luz; Isabella Macário Ferro Cavalcanti; Carlos Alexandre Antunes de Brito; Tereza Cristina Leal- Balbino (Brazilian Journal of Microbiology, 2024)

Green synthesis of an advanced composite membrane for the purification of water contaminated with potentially toxic metals - Ana Maria Tischer; Rafaela Reis Ferreira; João Gabriel Ribeiro; Derval dos Santos Rosa; Alexandre Tadeu Paulino (Journal of Water Process Engineering, 2024)

Detection of pathogenic Leptospira spp. in unconventional pets - Bruna Carolina Ulsenheimer; Matheus Yuri dos Santos; Bruna Della Flora; Diego Andres Rodriguez Matarrita; Sônia de Avila Botton; Ana Eucares Von Laer; Daniela Isabel Brayer Pereira; Rafael Almeida Fighera; Alexandre Alberto Tonin (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Acaricidal activity of synthetic spilanthol derivative against ticks of medical and veterinary importance - Luis Adriano Anholeto; Guilherme Andrade Brancaglion; Danilo Martins dos Santos; Rafaela Tami Ikeda Kapritchkoff; Karina Neoob de Carvalho Castro; Kirley Marques Canuto; Rodney Alexandre Ferreira Rodrigues; Daniel Souza Correa; Ana Carolina de Souza Chagas; Julio Cezar Pastre (Veterinary Parasitology, 2024)

Not seen before. Unveiling depositional context and Mammuthus meridionalis exploitation at Fuente Nueva 3 (Orce, southern Iberia) through taphonomy and microstratigraphy - José Yravedra; Lloyd A. Courtenay; Mario Gutiérrez-Rodríguez; Juan Francisco Reinoso-Gordo; Juha Saarinen; Natalia Égüez; Carmen Luzón; Juan José Rodríguez-Alba; José A. Solano; Stefania Titton; Eva Montilla-Jiménez; José Cámara-Donoso; et al. (Quaternary Science Reviews, 2024)

Assessment of the presence of Acinetobacter spp. resistant to β-lactams in commercial ready-to-eat salad samples - Ana Costa-Ribeiro; Sarah Azinheiro; Sandra Mota; Marta Prado; Alexandre Lamas; Alejandro Garrido-Maestu (Food Microbiology, 2024)

Effectiveness and safety of clove oil and common salt in the long-term transport of Cyprinus carpio - Karina Ventura Boechat Martins; Stella Bicalho Silva; Alex Júnio da Silva Cardoso; Ana Lúcia Salaro; Pollyanna de Moraes França Ferreira; Mariella Bontempo Freitas; Jener Alexandre Sampaio Zuanon (Aquaculture, 2024)

Microcystin influence on soil-plant microbiota: Unraveling microbiota modulations and assembly processes in the rhizosphere of Vicia faba - El Mahdi Redouane; Andrés Núñez; Wafa Achouak; Mohamed Barakat; Anoop Alex; José Carlos Martins; Zakaria Tazart; Richard Mugani; Soukaina El Amrani Zerrifi; Mohammed Haida; Ana M. García; Alexandre Campos; et al. (Science of The Total Environment, 2024)

Green technologies applied to low-NaCl fresh sausages production: Impact on oxidative stability, color formation, microbiological properties, volatile compounds, and sensory profile - Ana Carolina Mendes Dias Seibt; Priscila Nerhing; Mariana Basso Pinton; Suelen Priscila Santos; Yasmim Sena Vaz Leães; Fernanda De Candido De Oliveira; Silvino Sasso Robalo; Bianca Campos Casarin; Bibiana Alves Dos Santos; Juliano Smanioto Barin; Roger Wagner; Cristiano Ragagnin De Menezes; et al. (Meat Science, 2024)

Erythrocyte alterations in specimens of Danio rerio caused by exposure to metformin - Pablo Americo Barbieri; Luara Lupepsa; Brennda Ribeiro Paupitz; Camila Oliveira de Andrade; Adriana Aparecida Sinópolis Gigliolli; Ana Luiza de Brito Portela-Castro; Ricardo Pereira Ribeiro; Carlos Alexandre Fernandes; Luciana Andreia Borin-Carvalho (Environmental Toxicology and Pharmacology, 2024)

Environmental vulnerability index in Dipteryx alata: influence of abiotic stresses on central processes of plant physiology and metabolism - Leticia Ferreira Sousa; Paulo Eduardo Menezes-Silva; Priscila Ferreira Batista; Ana Paula Silva Alves; Maria Clara de Andrade PereiraSilva; Sabrina Emanuella da Silva Almeida; Rauander Douglas Ferreira Barros Alves; Lucas Loram Lourenço; Layara Alexandre Bessa; Adinan Alves da Silva; Alan Carlos Costa; Anderson Rodrigo da Silva; et al. (Acta Physiologiae Plantarum, 2024)

Local attitudes towards conservation governance in a large tropical multiple-use Marine Protected Area in Brazil - José Gilmar Cavalcante de Oliveira Júnior; Ana Paula de Oliveira Santos; Ana Claudia Mendes Malhado; Carolina Neves Souza; Chiara Bragagnolo; Aline Olímpio dos Santos; Evelynne Letícia dos Santos Farias Cardoso de Barros; Felipe Alexandre Santos Vieira; Inaê Farias Vieira Dantas; Jacqueline Costa Aldabalde; João Vitor Campos-Silva; Johnny Antonio da Silva Lima; et al. (Ocean & Coastal Management, 2024)

Small vertebrates from the Late Pliocene Las Higueruelas locality of central Spain with new biochronological and palaeoecological inferences - Hugues-Alexandre Blain; Tomáš Přikryl; Pedro Piñero; Christian Sánchez-Bandera; Almudena Martínez-Monzón; Ana Fagoaga (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Study of methane upgrading using an activated carbon 3D-printed adsorbent - Ana Pereira; Alexandre F.P. Ferreira; Alírio Rodrigues; Ana Mafalda Ribeiro; Maria João Regufe (Journal of Environmental Chemical Engineering, 2024)

Mating system and inbreeding depression in Hymenaea stigonocarpa - Darlin U.G. Zaruma; Alexandre M. Sebbenn; Bruno C. Rossini; Ana C.F. Pardo; Marcela A.M. Silvestre; Jose Cambuim; Alexandre M. da Silva; Silvelise Pupin; Carlos J. Rodrigues; Celso L. Marino; Mário L.T. de Moraes (Tree Genetics & Genomes, 2024)

New reports of Gilbertella persicaria causing post-harvest rot in different fruits in Brazil - Ana Elisa de Almeida Souza; André Luiz Cabral Monteiro de Azevedo Santiago; Amanda Cupertino de Queiroz Brito; Juliana Ferreira de Mello; José Vitorino da Silva Neto; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Journal of Plant Diseases and Protection, 2024)

Adaptability and stability of black bean genotypes with normal and early cycle - Moisés Ambrósio; Rogério Figueiredo Daher; Raiane Mariani Santos; Josefa Grasiela Silva Santana; Ana Kesia Faria Vidal; Maxwel Rodrigues Nascimento; Cleudiane Lopes Leite; Alexandre Gomes de Souza; Rafael Souza Freitas; Wanessa Francesconi Stida; João Esdras Calaça Farias; Benedito Fernandes de Souza Filho; et al. (Euphytica, 2024)

Brominated flame retardants and natural organobrominated compounds in a vulnerable delphinid species along the Brazilian coast - Lara G. Vidal; Nara De Oliveira-Ferreira; João Paulo M. Torres; Alexandre F. Azevedo; Ana Carolina O. Meirelles; Leonardo Flach; Camila Domit; Ana Bernadete L. Fragoso; Flávio J. Lima Silva; Vítor Luz Carvalho; Milton Marcondes; Lupércio A. Barbosa; et al. (Science of The Total Environment, 2023)

Mapping integrated crop-livestock systems in Brazil with planetscope time series and deep learning - Inacio T. Bueno; João F.G. Antunes; Aliny A. Dos Reis; João P.S. Werner; Ana P.S.G.D.D. Toro; Gleyce K.D.A. Figueiredo; Júlio C.D.M. Esquerdo; Rubens A.C. Lamparelli; Alexandre C. Coutinho; Paulo S.G. Magalhães (Remote Sensing of Environment, 2023)

Cryopreservation efficiency of red-rumped agouti (Dasyprocta leporina) sperm obtained from different origins through epididymal retrograde flushing or electroejaculation - Thibério de Sousa Castelo; Andréia Maria da Silva; Gislayne Christianne Xavier Peixoto; Ana Liza Paz Souza; Lívia Batista Campos; Gabriela Liberalino Lima; Maiko Roberto Tavares Dantas; João Batista Freire de Souza-Junior; Alexandre Rodrigues Silva (Cryobiology, 2023)

Detoxified castor seed meal replaces soybean meal in the supplement for Holstein-Zebu crossbred steers finished on tropical pasture during the rainy season - Silvia Layse Mendes Machado; Fabiano Ferreira da Silva; Gleidson Giordano Pinto de Carvalho; Laize Vieira Santos; João Wilian Dias Silva; Tarcísio Ribeiro Paixão; Vanessa Alexandre Vieira; Ana Paula Gomes da Silva; Marceliana da Conceição Santos; Dorgival Morais de Lima Júnior; Robério Rodrigues Silva (Tropical Animal Health and Production, 2023)

Bumetanide Attenuates Cognitive Deficits and Brain Damage in Rats Subjected to Hypoxia–Ischemia at Two Time Points of the Early Postnatal Period - Diorlon Nunes Machado; Luz Elena Durán-Carabali; Felipe Kawa Odorcyk; Andrey Vinicios Soares Carvalho; Ana Paula Rodrigues Martini; Livia Machado Schlemmer; Marcel de Medeiros de Mattos; Gabriel Pereira Bernd; Carla Dalmaz; Carlos Alexandre Netto (Neurotoxicity Research, 2023)

Energetic responses of head-out water immersion at different temperatures during post-exercise recovery and its consequence on anaerobic mechanical power - Marcelo Coertjens; Patricia Chaves Coertjens; Marcus Peikriszwili Tartaruga; Tatiane Gorski; Adriano Eduardo Lima-Silva; Lorival José Carminatti; Paulo Otto Beyer; Ana Paula Viola de Almeida; Jeam Marcel Geremia; Leonardo Alexandre Peyré-Tartaruga; Luiz Fernando Martins Kruel (European Journal of Applied Physiology, 2023)

Marine heatwaves can limit the role of surfgrasses as biofilters for wastewaters - Paula Bonet-Melià; Jose Miguel Sandoval-Gil; Guillermo Samperio-Ramos; Manuel Vivanco-Bercovich; Sergio R. Canino-Herrera; Reginaldo Durazo; Víctor F. Camacho-Ibar; Ana Alexandre (Marine Pollution Bulletin, 2023)

A discussion on the estimation of apparent colour of water with the Forel-Ule index for medium-width sections of rivers with high hydrodynamic activity - Ana Paula Falcão; Alexandre B. Gonçalves; Gonçalo F. Ferreira (Remote Sensing Applications: Society and Environment, 2023)

Identification of pegmatites zones in Muiane and Naipa (Mozambique) from Sentinel-2 images, using band combinations, band ratios, PCA and supervised classification - Ubaldo Gemusse; Joana Cardoso-Fernandes; Alexandre Lima; Ana Teodoro (Remote Sensing Applications: Society and Environment, 2023)

Unpacking bio-based alternatives to ethylene production in Brazil, Europe, and the United States: A comparative life cycle assessment - Marianne Zanon-Zotin; Clarissa Bergman-Fonte; Taísa Nogueira Morais; Pedro Luiz Barbosa Maia; Lucas Carvalho; Gerd Angelkorte; Ana Carolina Oliveira Fiorini; Pedro Rua Rodriguez Rochedo; Joana Portugal-Pereira; Alexandre Szklo; Roberto Schaeffer (Journal of Cleaner Production, 2023)

Nutritional and chemical composition of Alpinia zerumbet leaves, a traditional functional food - Jefferson Diocesano da Cruz; Maria A. Mpalantinos; Laena Rebouças de Oliveira; Tainara Garcia Branches; Alexandre Xavier; Francisca das Chagas do A. Souza; Jaime P. Lopes Aguiar; José Luiz P. Ferreira; Jefferson Rocha de Andrade Silva; Ana Claudia Fernandes Amaral (Food Research International, 2023)

Methodological insights from unmanned system technologies in a rock quarry environment and geomining heritage site: coupling LiDAR-based mapping and GIS geovisualisation techniques - Ana Pires; André Dias; Pedro Silva; António Ferreira; Paulo Rodrigues; Tiago Santos; Alexandre Oliveira; Liliana Freitas; Alfredo Martins; José Almeida; Eduardo Silva; Helder I. Chaminé (Arabian Journal of Geosciences, 2023)

Amazonian earthworm biodiversity is heavily impacted by ancient and recent human disturbance - Ana C. Conrado; Wilian C. Demetrio; David W.G. Stanton; Marie L.C. Bartz; Samuel W. James; Alessandra Santos; Elodie da Silva; Talita Ferreira; Agno N.S. Acioli; Alexandre C. Ferreira; Lilianne S. Maia; Telma A.C. Silva; et al. (Science of The Total Environment, 2023)

Hybrid multi-core shell magnetic nanoparticles for wet peroxide oxidation of paracetamol: Application in synthetic and real matrices - Adriano S. Silva; Fernanda F. Roman; Arnaldo V. Dias; Jose L. Diaz de Tuesta; Alexandre Narcizo; Ana Paula F. da Silva; Ihsan Çaha; Francis Leonard Deepak; Manuel Bañobre-López; Ana M.C. Ferrari; Helder T. Gomes (Journal of Environmental Chemical Engineering, 2023)

Repurposing miconazole and tamoxifen for the treatment of Mycobacterium abscessus complex infections through in silico chemogenomics approach - Laura Raniere Borges dos Anjos; Vinícius Alexandre Fiaia Costa; Bruno Junior Neves; Ana Paula Junqueira-Kipnis; André Kipnis (World Journal of Microbiology and Biotechnology, 2023)

Africanized honeybee (Apis mellifera) semen freezing using Tris-based and Collins extenders - Lucas da Silva Morais; Edgar Rodrigues de Araujo Neto; Andreia Maria da Silva; Luana Grasiele Pereira Bezerra; Ana Flávia Santos da Cunha; Nailton Oliveira de Sousa Chagas; Romário Parente dos Santos; Genevile Carife Bergamo; Débora Andrea Evangelista Façanha; Katia Peres Gramacho; Alexandre Rodrigues Silva (Tropical Animal Health and Production, 2023)

Mobile terrestrial laser scanner vs. UAV photogrammetry to estimate woody crop canopy parameters – Part 1: Methodology and comparison in vineyards - Alexandre Escolà; José M. Peña; Francisca López-Granados; Joan R. Rosell-Polo; Ana I. de Castro; Eduard Gregorio; Francisco M. Jiménez-Brenes; Ricardo Sanz; Francesc Sebé; Jordi Llorens; Jorge Torres-Sánchez (Computers and Electronics in Agriculture, 2023)

Mobile terrestrial laser scanner vs. UAV photogrammetry to estimate woody crop canopy parameters – Part 2: Comparison for different crops and training systems - Jorge Torres-Sánchez; Alexandre Escolà; Ana Isabel de Castro; Francisca López-Granados; Joan R. Rosell-Polo; Francesc Sebé; Francisco Manuel Jiménez-Brenes; Ricardo Sanz; Eduard Gregorio; José M. Peña (Computers and Electronics in Agriculture, 2023)

Plant-parasitic nematode community and enzyme activities in soils under no-till soybean crops in Brazil - Felipe Martins do Rêgo Barros; Alexandre Pedrinho; Gustavo da Cunha Sant’Ana; Caio César Gomes Freitas; Juliana Magrinelli Osório Rosa; Claudio Marcelo Gonçalves de Oliveira; Caique Rozada; Felipe Nogueira de Sá Marto; João Augusto Lopes Pascoalino; Luiz Antônio da Silva; Fernando Dini Andreote (Rhizosphere, 2023)

Glacial/interglacial climate variability in southern Spain during the late Early Pleistocene and climate backdrop for early Homo in Europe - Christian Sánchez-Bandera; Ana Fagoaga; Alexia Serrano-Ramos; José Solano-García; Deborah Barsky; Daniel DeMiguel; Juan Ochando; Juha Saarinen; Pedro Piñero; Iván Lozano-Fernández; Lloyd A. Courtenay; Stefania Titton; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Do ultrasound form spontaneously nitrous pigments in nitrite-free pork meat batter? - Yasmim Sena Vaz Leães; José Manuel Lorenzo; Ana Carolina Mendes Dias Seibt; Mariana Basso Pinton; Silvino Sasso Robalo; Renius De Oliveira Mello; Roger Wagner; Juliano Smanioto Barin; Cristiano Ragagnin De Menezes; Paulo Cezar Bastianello Campagnol; Alexandre José Cichoski (Meat Science, 2023)

COVID-19 and candiduria: an investigation of the risk factors and immunological aspects - Junya L. Singulani; Danielle L. Silva; Caroline M. Lima; Vanessa C. R. Magalhães; Ludmila M. Baltazar; Alexandre S. Moura; Ana Raquel O. Santos; Tatiani Fereguetti; Juliana C. Martins; Lívia F. Rabelo; Ana C. Lyon; Olindo A. Martins-Filho; et al. (Brazilian Journal of Microbiology, 2023)

How does the subtropical landscape configuration influence the ecomorphological traits and community composition of ground-dwelling beetles in southern Brazil? - Pâmela Niederauer Pompeo; Luís Carlos Iuñes Oliveira Filho; Douglas Alexandre; Ana Carolina Lovatel; Pedro Martins da Silva; José Paulo Sousa; Osmar Klauberg-Filho; Dilmar Baretta (Applied Soil Ecology, 2023)

Redox status of juvenile Nile tilapia, Oreochromis niloticus (Linnaeus, 1758), fed diets supplemented with poultry liver protein hydrolysate as feed aditive - Juliana Rodrigues Gomes; Alex Júnio da Silva Cardoso; Hamilton Hisano; Renata Maria Pereira de Freitas; Karina Ventura Boechat Martins; Filipe Silveira Azevedo; Mariella Bontempo Freitas; Pollyanna de Moraes França Ferreira; Ana Lúcia Salaro; Jener Alexandre Sampaio Zuanon (Animal Feed Science and Technology, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Larvicidal potential of extracts and isolated compounds from Piper cubeba fruits against Aedes aegypti (Diptera: Culicidae) larvae - Ana Carolina Gomes; Alexandre Borges; Daniela Garcia Zoca; Marcio Luís Andrade e Silva; Aline Rafaela da Silva Rodrigues Machado; Alex Martins Machado; Mario F. C. Santos; Rosangela da Silva de Laurentiz (Natural Product Research, 2023)

Redefining the MIS 3 climatic scenario for Neanderthals in northeastern Iberia: A multi-method approach - Ana Fagoaga; Mónica Fernández-García; Juan Manuel López-García; M. Gema Chacón; Palmira Saladié; Josep Vallverdú; Francisco Javier Ruiz-Sánchez; Hugues-Alexandre Blain (Quaternary Science Reviews, 2023)

Orange molasses as a new energy ingredient for feedlot lambs in Brazil - Isabela Jorge dos Santos; Paulo César Gonzales Dias Junior; Ana Carolina Silva Vicente; Adrielly Lais Alves; Rhaissa Garcia de Assis; Janaina Socolovski Biava; Mateus Vigo Vercesi Almada Nogueira; Alexandre Vaz Pires; Evandro Maia Ferreira (Tropical Animal Health and Production, 2023)

Effects of extruded urea levels on the productive performance and carcass and meat characteristics of Nellore cattle - Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Marina de Nadai Bonin Gomes; Vanessa Zirondi Longhini; Gelson dos Santos Difante; Alexandre Menezes Dias; Eduardo de Souza Leal; Manoel Gustavo Paranhos da Silva; Ana Hellen da Silva; Laura Beatriz Perez da Silva; Rafael Goes Cardoso Paro; Marcos Jácome de Araújo; et al. (Tropical Animal Health and Production, 2023)

Evaluation of Covalent Organic Frameworks for the low-cost, rapid detection of Shiga Toxin-producing Escherichia coli in ready-to-eat salads - Ana Costa-Ribeiro; Sarah Azinheiro; Soraia P.S. Fernandes; Alexandre Lamas; Marta Prado; Laura M. Salonen; Alejandro Garrido-Maestu (Analytica Chimica Acta, 2023)

The decline of the ecosystem services generated by anadromous fish in the Iberian Peninsula - Pedro R. Almeida; Catarina S. Mateus; Carlos M. Alexandre; Sílvia Pedro; Joana Boavida-Portugal; Ana F. Belo; Esmeralda Pereira; Sara Silva; Inês Oliveira; Bernardo R. Quintella (Hydrobiologia, 2023)
This work aims to present an historical review of the ecosystem services provided by anadromous fish (i.e., species that migrate from the sea to the river to spawn) throughout Human time, as well as of the main related threats, focusing on the Iberian Peninsula region. Anadromous fish provide important provision, cultural, regulatory and supporting ecosystem services across their distribution range and have been extensively exploited by humans since prehistoric times. In the Iberian Peninsula, sea lamprey, allis and twaite shads, sea trout, Atlantic salmon and European sturgeon were once abundantly present in several river basins covering what is now Portuguese and Spanish territory. These species have suffered a severe decline across their distribution range, mainly due to habitat loss and overexploitation. Considered regal delicacies, these fishes were once a statement on the tables of the highest social classes, a much appreciated bounty for the poorer population and are still an important part of the local gastronomy and economy. Such high economic and cultural interest encouraged intensive fishing. Currently, management efforts are being implemented, pairing habitat rehabilitation (e.g., construction of fish passes in obstacles to migration such as weirs and dams) with sustainable fisheries. Considering the present climate change scenario, these species are bound to endure increased pressures, demanding novel management approaches to ensure population numbers that are able to secure their sustainable exploitation.

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Musa spp. cultivars as a neutralising source against some toxic activities of Bothrops and Crotalus genus snake venoms - Márcia Matos da Silva; Gerso Pereira Alexandre; Marta Regina Magalhães; Ana Maria Torres; Lucilia Kato; Victória Costa da Silva; Simone Maria Teixeira de Saboia Morais; Armando Garcia Rodriguez; Taícia Pacheco Fill; Alana Kelyene Pereira; Jussara Roque; Jorge Luiz Souza Simão; et al. (Toxicon, 2023)

Evaluation of the volatiles’ chemical profile and antibacterial activity of Lavandula stoechas L. extracts obtained by supercritical carbon dioxide - Jelena Vladić; Igor Jerković; Sandra Svilović; Valentina Pavić; Kristian Pastor; Alexandre Paiva; Stela Jokić; Silvia Rebocho; Ana Rita Duarte (Sustainable Chemistry and Pharmacy, 2023)

Wet brewers’ grains as a source of protein for feedlot lambs: Impacts on intake, apparent nutrient digestibility, ruminal fermentation, and nitrogen balance - Rhaíssa G. de Assis; Isabela J. dos Santos; Jennifer M. Gasparina; Natalia A. Bandoria; Brenda Alves; Paulo C.G. Dias; Ana C.S. Vicente; Letícia C.B. Soares; Daniel M. Polizel; Janaina S. Biava; Alexandre V. Pires; Evandro M. Ferreira (Small Ruminant Research, 2023)

Phylogenomics reconciles molecular data with the rich fossil record on the origin of living turtles - Alexandre Pedro Selvatti; Filipe Romero Rebello Moreira; Daniel Cardoso Carvalho; Francisco Prosdocimi; Claudia Augusta de Moraes Russo; Ana Carolina Martins Junqueira (Molecular Phylogenetics and Evolution, 2023)

Territorial planning of rustic land constructions and their adaptation to climate change in the province of Málaga, Spain - Ana Crespo; Javier Velázquez; Fernando Herráez; Derya Gülçin; Ali Ugur Özcan; Ana Hernando; Rui Alexandre Castanho (Land Use Policy, 2023)

Benzophenone-3 causes oxidative stress in the brain and impairs aversive memory in adult zebrafish - Ana Luisa Pires Moreira; Weslley Souza Paiva; Augusto Monteiro de Souza; Maria Clara Galvão Pereira; Hugo Alexandre Oliveira Rocha; Silvia Regina Batistuzzo de Medeiros; Ana Carolina Luchiari (Environmental Toxicology and Pharmacology, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

Richness of Nigrospora spp. (Apiosporaceae) in Manihot esculenta in Brazil and the description of three new species - Amanda Cupertino de Queiroz Brito; Juliana Ferreira de Mello; Ana Elisa de Almeida Souza; Sandy dos Santos Nascimento; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Mycological Progress, 2023)

Recycled cement production energy consumption optimization - Vitor Sousa; José Alexandre Bogas; Sofia Real; Inês Meireles; Ana Carriço (Sustainable Chemistry and Pharmacy, 2023)

A systematic review of the effects of cold exposure on pathological cardiac remodeling in mice - Alexandre Martins Oliveira Portes; Ana Beatriz Rezende Paula; Denise Coutinho de Miranda; Letícia Teresinha Resende; Bianca Iara Campos Coelho; Maria Cecília Teles; Isabela Alcântara Barretto Araújo Jardim; Antônio José Natali; Ana Maria de Lauro Castrucci; Mauro César Isoldi (Journal of Thermal Biology, 2023)

Volatile organic compound (VOC) profile and plantlet growth of Aeollanthus suaveolens under conventional and alternative membrane systems - Diene Xavier Araújo; Tainá Teixeira Rocha; Alexandre Alves de Carvalho; Ana Paula Ribeiro Medeiros; Fernanda Naiara Santos Ribeiro; Rafael Marlon Alves de Assis; Suzan Kelly Vilela Bertolucci; José Eduardo Brasil Pereira Pinto (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Determinants of body core temperatures at fatigue in rats subjected to incremental-speed exercise: The prominent roles of ambient temperature, distance traveled, initial core temperature, and measurement site - Marcelo T. Andrade; Nicolas H. S. Barbosa; Roberto C. S. Souza-Junior; Cletiana G. Fonseca; William C. Damasceno; Kássya Regina-Oliveira; Lucas R. Drummond; Myla A. Bittencourt; Ana C. Kunstetter; Pedro V. R. Andrade; Alexandre S. R. Hudson; Pedro H. Paula; et al. (International Journal of Biometeorology, 2023)

Disruption of mitochondrial bioenergetics and calcium homeostasis by phytanic acid in the heart: Potential relevance for the cardiomyopathy in Refsum disease - Ângela Beatriz Zemniaçak; Ana Cristina Roginski; Rafael Teixeira Ribeiro; Julia Gabrieli Bender; Rafael Aguiar Marschner; Simone Magagnin Wajner; Moacir Wajner; Alexandre Umpierrez Amaral (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2023)

Processing methods of flint corn and protein supplement in forage-free diets for feedlot lambs - Thamires Ubices Sturion; Ana Carolina Silva Vicente; Matheus Sousa de Paula Carlis; Rhaissa Garcia de Assis; Terezinha Teixeira de Souza; Daniel Montanher Polizel; Paulo César Gonzales Dias Junior; Isabela Jorge dos Santos; Jamile Haddad Comelli; Janaina Socolovski Biava; Alexandre Vaz Pires; Evandro Maia Ferreira (Tropical Animal Health and Production, 2023)

Dwarf and tall elephant grass silages: intake, nutrient digestibility, nitrogen balance, ruminal fermentation, and ingestive behavior in sheep - Luciana Felizardo Pereira Soares; Adriana Guim; Alexandre Carneiro Leão de Mello; Marcelo de Andrade Ferreira; Francisco Fernando Ramos de Carvalho; Janaina de Lima Silva; Ana Caroline Cerqueira de Melo Vasco; Tomás Guilherme Pereira da Silva; Maria Luciana Menezes Wanderley Neves (Tropical Animal Health and Production, 2023)

Antimicrobial and Antibiofilm Activity of Copper-Based Metallic Compounds Against Bacteria Related with Healthcare-Associated Infections - Anna L. Pereira; Mayron A. Vasconcelos; Alexandre L. Andrade; Israel M. Martins; Alda K. M. Holanda; Ana C. S. Gondim; Dayana P. S. Penha; Katherine L. Bruno; Francisco O. N. Silva; Edson H. Teixeira (Current Microbiology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Essential oil from Arnica montana on feedlot performance, ingestive behavior, carcass characteristics, rumen morphometrics characteristics and meat fatty acids profile of lambs - Paulo César G. Dias Junior; Isabela J. dos Santos; Adrielly L.A. da Silva; Rhaissa G. de Assis; Ana Carolina S. Vicente; Matheus S.P. Carlis; Letícia C.B. Soares; Jamile H. Comelli; Janaina S. Biava; Rafael C. Araujo; Alexandre V. Pires; Evandro M. Ferreira (Small Ruminant Research, 2023)

Structural characterization of exopolysaccharides obtained from Porphyridium cruentum exhausted culture medium - Nathana L. Cristofoli; Alexandre R. Lima; Ana M. Rosa da Costa; Dmitry Evtyugin; Carlos Silva; João Varela; Margarida C. Vieira (Food and Bioproducts Processing, 2023)

Potential in vitro action of an adenosine analog and synergism with penicillin against Corynebacterium pseudotuberculosis - Pedro Negri Bernardino; Carolina Lechinski de Paula; Ana Flávia Marques Pereira; Márcio Garcia Ribeiro; Vasco Ariston de Carvalho Azevedo; Alexandre Secorun Borges; Ary Fernandes-Júnior; José Paes Oliveira-Filho (Brazilian Journal of Microbiology, 2023)

Tolerance in rice genotypes to the sugarcane borer Diatraea saccharalis (Lepidoptera: Crambidae) - Ana Paula Pelosi; Franciele Cristina da Silva; Adriana G. Vaz; André Cirilo de S. Almeida; Anderson Rodrigo da Silva; Flávio G. de Jesus; José Alexandre de F. Barrigossi (Biologia, 2023)

TimeFISH : Long‐term assessment of reef fish assemblages in a transition zone in the Southwestern Atlantic - Juan P. Quimbayo; Lucas T. Nunes; Fernanda C. Silva; Antônio B. Anderson; Diego R. Barneche; Angela M. Canterle; Isadora Cord; Andrea Dalben; Débora S. Ferrari; Luisa Fontoura; Thiago M. J. Fiuza; Ana M. R. Liedke; et al. (Ecology, 2023)
The TimeFISH database provides the first public time‐series dataset on reef fish assemblages in the southwestern Atlantic (SWA), comprising 15 years of data (2007–2022) based on standardized Underwater Visual Censuses (UVCs). The rocky reefs covered by our dataset are influenced by pronounced seasonal cycles of ocean temperatures with warm tropical waters from the Brazil Current in the summer (~27°C) and colder waters from the La Plata River Plume discharge and upwelling from the South Atlantic Central Water in the winter (~18°C). These oceanographic conditions characterize this area as the southernmost tropical–subtropical climatic transition zone in the Atlantic Ocean. As a result, reef fish assemblages are comprised of both tropical and subtropical species. All records included in TimeFISH were collected using UVCs, a nondestructive method that allows the estimation of fish species richness, abundance, and body size distributions. UVCs were performed through 40 m 2 belt transects by scuba diving in nine locations along the southern Brazilian coast (25–29°S). Four of these locations lie within the boundaries of the no‐entry Arvoredo Marine Biological Reserve, where fishing and recreational activities are forbidden, and the remaining locations are unprotected from these activities. During each belt transect, a diver swam at a constant depth above and parallel to the reef, identifying fish species, counting the number of individuals, and estimating the total body length (Lt in cm) of all detected individuals. All fish individuals in the water column (up to 2 m above the substratum) and at the bottom were targeted. In total, 202,965 individuals belonging to 163 reef fish species and 53 families were recorded across 1857 UVCs. All survey campaigns were funded by either public or mixed capital (private–public) sources, including seven grants from the Brazilian federal and Santa Catarina state governments. Part of the data has already been used in multiple MS.c. and Ph.D. theses and scientific articles. TimeFISH represents an important contribution for future studies aiming to examine temporal and spatial variations of reef fish assemblages in transition zones. No copyright restrictions apply to the use of this data set, other than citing this publication.

Embryotoxicity and visual-motor response of functionalized nanostructured hydroxyapatite-based biomaterials in zebrafish (Danio rerio) - Augusto Monteiro de Souza; Heloysa Araujo-Silva; Andréa Machado Costa; Andre Linhares Rossi; Alexandre Malta Rossi; José Mauro Granjeiro; Ana Carolina Luchiari; Silvia Regina Batistuzzo de Medeiros (Chemosphere, 2023)

Low dose of cyclosporine A disrupts sperm parameters and testosterone levels reversibly in mice - Gláucia Eloisa Munhoz de Lion Siervo; Noemia Aparecida Partelli Mariani; Alan Andrew S. Silva; Ana Paula Franco Punhagui-Umbelino; Ivana Regina da Costa; Alexandre Dorth de Andrade; Erick J.R. Silva; Glaura Scantamburlo Alves Fernandes (Toxicology and Applied Pharmacology, 2023)

Biological activities of organic extracts and specialized metabolites from different parts of Cryptomeria japonica (Cupressaceae) – A critical review - Ana Lima; Filipe Arruda; Alexandre Janeiro; Jorge Medeiros; José Baptista; João Madruga; Elisabete Lima (Phytochemistry, 2023)

Genotoxicity and cytotoxicity of textile production effluents, before and after Bacillus subitilis bioremediation, in Astyanax lacustris (Pisces, Characidae) - Josiane Rodrigues Rocha da Silva; Angelivia Gregorio; Ana Luiza de Brito Portela-Castro; Carlos Alexandre Fernandes (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Current developments and future perspectives on biotechnology applications of natural deep eutectic systems - Ana Rita Jesus; Alexandre Paiva; Ana Rita C. Duarte (Current Opinion in Green and Sustainable Chemistry, 2023)

Differential proteomics of Zika virus (ZIKV) infection reveals molecular changes potentially involved in immune system evasion by a Brazilian strain of ZIKV - Juliana M. Tatara; Rafael L. Rosa; Ana Paula M. Varela; Tais F. Teixeira; Patrícia Sesterheim; Anderson Gris; David Driemeier; Amanda N. S. Moraes; Markus Berger; Ramon D. Peña; Paulo M. Roehe; Diogo O. G. Souza; et al. (Archives of Virology, 2023)

Static Balance in Hereditary Spastic Paraplegias: a Cross-sectional Study - Diana Maria Cubillos-Arcila; Valéria Feijó Martins; Ana Paula Janner Zanardi; Gustavo Dariva Machado; Daniela Burguêz; Natalia Andrea Gomeñuka; Leonardo Alexandre Peyré-Tartaruga; Jonas Alex Morales Saute (The Cerebellum, 2023)

Uncovering biodegradability and biocompatibility of betaine-based deep eutectic systems - Inês João Ferreira; Alexandre Paiva; Mário Diniz; Ana Rita Duarte (Environmental Science and Pollution Research, 2023)
Deep eutectic systems (DES) have shown increasing popularity in last decade; however, the number of studies on the potential toxicity towards living organisms remains scarce. These studies are of the utmost importance to infer on the claimed non-toxicity and biocompatibility of DES. Most articles published, at this moment, only evaluate the toxicity towards a cell model or in different strains of bacteria. For this purpose, in this work, the effect of two DES (betaine:sorbitol:water 1:1:3 and betaine:glycerol 1:2) and their individual components were evaluated at different concentrations after administered via intraperitoneal injection in zebrafish ( Danio rerio ). The total antioxidant capacity, lipoperoxidation, and the activity of various enzymes that work in different antioxidant pathways (superoxide dismutase, glutathione peroxidase, catalase, and glutathione S-transferase) were assessed. The results show no significant toxicity within the tested concentrations: up to 5000 µM and 3000 µM, for the assays using the system betaine:sorbitol:water 1:1:3 and for betaine:glycerol 1:2, respectively. The toxicity of individual components was studied up to 1000 µM. Based on the encouraging results that have been obtained, it is safe to conclude that these two deep eutectic systems can be used as the new class of environmentally friendly solvents. Graphical Abstract

Improving the accuracy of beef cattle methane inventories in Latin America and Caribbean countries - Guilhermo F.S. Congio; André Bannink; Olga L. Mayorga; João P.P. Rodrigues; Adeline Bougouin; Ermias Kebreab; Paulo C.F. Carvalho; Telma T. Berchielli; Maria E.Z. Mercadante; Sebastião C. Valadares-Filho; Ana L.C.C. Borges; Alexandre Berndt; et al. (Science of The Total Environment, 2023)

Comparative study of the production of cellulose nanofibers from agro-industrial waste streams of Salicornia ramosissima by acid and enzymatic treatment - Alexandre R. Lima; Nathana L. Cristofoli; Ana M. Rosa da Costa; Jorge A. Saraiva; Margarida C. Vieira (Food and Bioproducts Processing, 2023)

Evaluating the alterations of the estrogen-responsive genes in Cyprinodon variegatus larvae for biomonitoring the impacts of estrogenic endocrine disruptors (EEDs) - Sandra Isabel Moreno Abril; Ana Olmos Pin; Alexandre M. Schonemann; Marina Bellot; Cristian Gómez-Canela; Ricardo Beiras (Environmental Toxicology and Pharmacology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Antimicrobial activity of dimeric acylphloroglucinols isolated from southern Brazilian Hypericum species against to resistant bacterial - Henrique Bridi; Ana Paula Pustay; Sérgio Augusto de Loreto Bordignon; Simone Ulrich Picoli; Gilsane Lino von Poser; Alexandre de Barros Falcão Ferraz (Natural Product Research, 2022)

Neuroprotective Effect of Exogenous Galectin-1 in Status Epilepticus - Amanda Larissa Dias Pacheco; Igor Santana de Melo; Maisa de Araujo Costa; Mariah Morais Celestino Amaral; Nívea Karla de Gusmão Taveiros Silva; Yngrid Mickaelli Oliveira Santos; Daniel Leite Góes Gitaí; Marcelo Duzzioni; Alexandre Urban Borbely; Robinson Sabino Silva; Ana Luiza Ferreira Donatti; Luisa Mestriner; et al. (Molecular Neurobiology, 2022)

Leptospira interrogans in bats in Rio Grande do Sul State, Brazil: epidemiologic aspects and phylogeny - Bruna Carolina Ulsenheimer; Ana Eucares von Laer; Alexandre Alberto Tonin; Aline Alves Scarpellini Campos; Helton Fernandes dos Santos; Luís Antônio Sangioni; Sônia de Avila Botton (Brazilian Journal of Microbiology, 2022)

The impact of COVID-19 on antimicrobial prescription and drug resistance in fungi and bacteria - Junya L. Singulani; Danielle L. Silva; Caroline M. Lima; Vanessa C. R. Magalhães; Ludmila M. Baltazar; Nalu T. A. Peres; Rachel B. Caligiorne; Alexandre S. Moura; Ana Raquel O. Santos; Tatiani Fereguetti; Juliana C. Martins; Lívia F. Rabelo; et al. (Brazilian Journal of Microbiology, 2022)

Silicon amendment induces resistance in rice to Diatraea saccharalis (Lepidoptera: Crambidae) - Ana Paula Pelosi; Franciele Cristina da Silva; Adriana G. Vaz; André Cirilo S. Almeida; Anderson Rodrigo da Silva; Michael J. Stout; Flávio G. de Jesus; José Alexandre F. Barrigossi (Arthropod-Plant Interactions, 2022)

Co-design of a marine protected area zoning and the lessons learned from it - Barbara Horta e Costa; M. Helena Guimarães; Mafalda Rangel; Adriana Ressurreição; Pedro Monteiro; Frederico Oliveira; Luís Bentes; Nuno Sales Henriques; Inês Sousa; Sofia Alexandre; João Pontes; Carlos M. L. Afonso; et al. (Frontiers in Marine Science, 2022)
Marine Protected Areas (MPAs) are a tool to safeguard marine natural systems, yet their effectiveness depends on how well they are integrated into the existing socioeconomic context. Stakeholder engagement in MPA design can contribute to increasing integration. This study focuses on the co-design of an MPA between researchers, public administration, the private sector, and non-governmental organizations. The proposed MPA is in Portugal and includes an area that is a hotspot for biodiversity and economic activities. This is the first MPA proposal in mainland Portugal co-designed using a participatory approach. This study highlights the steps of the zoning process and synthesizes the eight main lessons learned, useful for other cases, particularly for relatively small coastal MPAs with multiple socioeconomic activities. Three zoning proposals were developed and discussed within the participatory process. The proposals considered the best scientific and local knowledge available and were defined using ecological, socioeconomic, and shape-area guiding principles. In an iterative manner and following a participatory approach, compromises with stakeholders were achieved, and a final proposal, scientifically sound and socially accepted by most stakeholders, was delivered to the government. The final zoning plan will achieve ambitious conservation goals, including the largest fully protected area to be declared in mainland Portugal, while minimizing the impacts on the existing economic activities and promoting its sustainability. This process resulted in valuable lessons that may be applied elsewhere and guide future MPA implementation or rezoning of existing ones. These transdisciplinary and participatory processes can be time and resource-consuming but are vital for ensuring MPA effectiveness.

Simultaneous selection for yield, adaptability and stability and repeatability coefficient in full-sib families of elephant grass for energy purposes via mixed models - Ana Kesia Faria Vidal; Rogério Figueiredo Daher; Rafael Souza Freitas; Wanessa Francesconi Stida; Moisés Ambrósio; Josefa Grasiela Silva Santana; Alexandre Gomes de Souza; Geraldo de Amaral Gravina; Marcelo Vivas; Antônio Teixeira do Amaral Junior (Euphytica, 2022)

Performance, nutritional behavior, and carcass characteristics of feedlot lambs fed diets with non-forage fiber source or sodium bicarbonate - Ana Carolina Silva Vicente; Matheus Sousa de Paula Carlis; Isabela Jorge dos Santos; Adrielly Lais Alves da Silva; Paulo César Gonzales Dias Júnior; Rhaissa Garcia de Assis; Thamires Ubices Sturion; Janaina Socolovski Biava; Alexandre Vaz Pires; Evandro Maia Ferreira (Tropical Animal Health and Production, 2022)

Therapeutic hypothermia for the treatment of neonatal hypoxia-ischemia: sex-dependent modulation of reactive astrogliosis - Rafael Bandeira Fabres; Ricardo Ribeiro Nunes; Marcel de Medeiros de Mattos; Mirella Kielek Galvan Andrade; Ana Paula Rodrigues Martini; Isadora D’Ávila Tassinari; Eduardo Farias Sanches; Luciano Stürmer de Fraga; Carlos Alexandre Netto (Metabolic Brain Disease, 2022)

Inter-sectoral prioritization of climate technologies: insights from a Technology Needs Assessment for mitigation in Brazil - Fábio T. F. da Silva; Alexandre Szklo; Amanda Vinhoza; Ana Célia Nogueira; André F. P. Lucena; Antônio Marcos Mendonça; Camilla Marcolino; Felipe Nunes; Francielle M. Carvalho; Isabela Tagomori; Laura Soares; Márcio Rojas da Cruz; et al. (Mitigation and Adaptation Strategies for Global Change, 2022)

Southern hemisphere tectonics in the Cenozoic shaped the pantropical distribution of parrots and passerines - Alexandre Pedro Selvatti; Ana Galvão; Gerald Mayr; Cristina Yumi Miyaki; Claudia Augusta de Moraes Russo (Journal of Biogeography, 2022)
Aim Explanations of pantropical distributions are challenging for taxa that diverged during the Cenozoic, after Gondwana broke apart. The ‘boreotropics hypothesis’ suggests that pantropical birds originated in the Laurasian forests. Extant parrots (Psittaciformes) are one the most species‐rich pantropical avian clades, but their known evolutionary history does not fit a boreotropical origin. Most living parrots and the earliest diverging lineages of the Psittaciformes inhabit the remnants of Gondwana, whereas the oldest stem and crown fossils are from the remnants of Laurasia. Our study proposes a biogeographic hypothesis that focuses on the Cenozoic connections between Laurasia and Gondwana to explain extant and fossil geographical distributions. Location Global. Taxon Psittaciformes. Methods We generated a time tree using previously derived data from 32 molecular markers for 312 parrot species and reconstructed their biogeographic history using maximum likelihood. Two scenarios were compared: one with dispersal constrained to adjacent areas, including the connections between the Northern and Southern Hemispheres, and one without this constraint. Results Our results indicate that the pantropical distribution of parrots was shaped by two major geological events. First, the final breakup of parts of Gondwana may have caused the first splits within crown parrots, establishing two parallel radiations: Psittacidae in the Neotropics and Psittaculidae in Australasia. Second, igneous palaeoprovinces could have connected major biogeographic realms. It seems that Atlantogea and Eurogondwana were important, as they connected South America, Africa and Europe, thus reconciling the Gondwanan crown splits and the early Laurasian fossils. Main Conclusions Our time tree allowed more concise biogeographic correlations between parrots and their sister group, the passerines and Earth's tectonic history. The crown lineages of Psittacopasseres appear to have originated in the Southern Hemisphere remnants of Gondwana, but stem lineages appear to have been able to disperse into the Northern Hemisphere through palaeobiogeographic provinces in the Cenozoic.

Wound healing activity of lectin isolated from seeds of Centrolobium microchaete Mart. ex Benth. on cutaneous wounds in mice - Luiz Gonzaga do Nascimento Neto; Mayron Alves de Vasconcelos; Aryane de Azevedo Pinheiro; Ana Patrícia Magalhães Ramos; Renally Barbosa da Silva; Alexandre Lopes Andrade; Francisco Vassiliepe Sousa Arruda; José Ajax Nogueira Queiroz; Edson Holanda Teixeira (Natural Product Research, 2022)

General biosafety measures for laboratory environments, outpatient clinics, medical centers, and veterinary hospitals during the SARS-CoV-2 pandemic - Bruna Carolina Ulsenheimer; Daniela Isabel Brayer Pereira; Helton Fernandes dos Santos; Ana Eucares von Laer; Alexandre Alberto Tonin; Mateus Matiuzzi da Costa; Luís Antonio Sangioni; Sônia de Avila Botton (Brazilian Journal of Microbiology, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Trichoderma as a biological agent of Fusarium oxysporum species complex and Vigna unguiculata growth promoter - Ana Cláudia Tenório do Amaral; Marília de Holanda Cavalcanti Maciel; Alexandre Reis Machado; Luciana Gonçalves de Oliveira; Cristiano Souza Lima; Antonio Félix da Costa; Neiva Tinti de Oliveira (European Journal of Plant Pathology, 2022)

Cilostazol attenuates cardiac oxidative stress and inflammation in hypercholesterolemic rats - Rosane de Oliveira Lopes; Gabriel Ferreira Lima; Ana Beatriz Araújo Mendes; Lis Jappour Autran; Nikolas Cunha de Assis Pereira; Stephani Correia Brazão; Beatriz Alexandre-Santos; Eliete Dalla Corte Frantz; Christianne Brêtas Vieira Scaramello; Fernanda Carla Ferreira Brito; Nadia Alice Vieira Motta (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Prospecting of essential oils in combination with florfenicol against motile Aeromonas isolated from tambaqui (Colossoma macropomum) - Ana Maria Souza da Silva; Edsandra Campos Chagas; Francisco Célio Maia Chaves; Fernanda de Alexandre Sebastião (Archives of Microbiology, 2022)

Applying the UDA-ODA discrimination technique to a herpetological association: the case of the Middle Palaeolithic site of El Salt (Alcoi, Spain) - Rafael Marquina-Blasco; Ana Fagoaga; Vicente D. Crespo; Salvador Bailon; Carolina Mallol; Cristo M. Hernández; Bertila Galván; Hugues-Alexandre Blain; Francisco Javier Ruiz-Sánchez (Archaeological and Anthropological Sciences, 2022)
El Salt (Middle Palaeolithic; Alcoi, Spain) is a key site for understanding the disappearance of Neanderthals in the eastern Iberian Peninsula, a process that is observed along its stratigraphic sequence. To improve our understanding of the palaeoclimatic context in which this process took place, we applied the UDA-ODA discrimination technique to the fossil herpetological assemblages from Stratigraphic Units (SU) Xb (52.3 ± 4.6 ka) and V (45.2 ± 3.4/44.7 ± 3.4 ka). This method is based in the application of an ecological criterion, the maximum altitude of each species on each Iberian range, to discern and remove those areas that do not meet their ecological requirements (UDA) from those that do (ODA), which are included in its distribution from Atlases from which the common distribution species is going to be extracted. Results indicate the existence of an alternation between “cold and wet” moments with “warm and dry” ones, all of them in a more humid context than nowadays. Climate was slightly warmer than nowadays in SU Xb, whereas was cooler in SU V. Regarding MAP, our results show less variation between SUs than it has been provided by previous studies. These results do not fully agree with those provided by small mammals from the same SUs, which indicate an increase of the temperatures whereas rainfall experienced the contrary. These differences could be related with the wider distribution of the Iberian herpetofauna, and some differences in the applied ecological criterion. Furthermore, herpetofaunal palaeoclimatic reconstruction shows that the abandonment of the site by Neanderthals seems to have occurred during an arid phase.

Assessing an Ecological Revitalization Project of Urban Streams in Brazilian Southeastern Region by Analytic Hierarchy Process - Kristiane Ramos Primo; Rosiane Argenton e Silva; Beatriz Capelo Olimpio; Gabriela Bassi Silva; Ana Paula Moni Silva; Harry Edmar Schulz; Alexandre Marco da Silva (Water, Air, & Soil Pollution, 2022)

Progression of Functional Gait in Hereditary Spastic Paraplegias - Diana Maria Cubillos-Arcila; Gustavo Dariva Machado; Lauren Sehnem; Daniela Burguêz; Ana Paula Janner Zanardi; Valéria Feijó Martins; Leonardo Alexandre Peyré-Tartaruga; Jonas Alex Morales Saute (The Cerebellum, 2022)

A tubular ceramic membrane coated with TiO2-P25 for radial addition of H2O2 towards AMX removal from synthetic solutions and secondary urban wastewater - Alexandre Diório; Jennyfer Díaz-Angulo; Reynel M. Castellanos; Ana I. Gomes; Rosângela Bergamasco; Marcelo Fernandes Vieira; Márcia Dezotti; Miguel Angel Mueses; Fiderman Machuca-Martinez; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Oil Spill and Socioeconomic Vulnerability in Marine Protected Areas - Felipe Roberto da Silva; Alexandre Schiavetti; Ana Cláudia Mendes Malhado; Beatrice Ferreira; Caio Victor de Paula Sousa; Fábio Pessoa Vieira; Francisco Roberto Pinto; Gabriel Barros Gonçalves de Souza; George Olavo; Jéssica Borba Quintela dos Santos; Joao Vitor Campos-Silva; José Gilmar Cavalcante de Oliveira Júnior; et al. (Frontiers in Marine Science, 2022)
The extensive oil spill (> 2,900 km) that occurred in the southwestern Atlantic (2019/2020) increased the vulnerability of the Brazilian coast, affecting marine and coastal protected areas (MPAs). In addition to supporting conservation, MPAs are sustainably used by local populations to help maintain ocean-dependent livelihoods. In this sense, we aim to assess the socioeconomic vulnerability of human communities in MPAs affected by this major oil spill. Using digital mapping, we assessed the socioeconomic vulnerability of 68 human communities living in or near 60 MPAs of different categories that were impacted by this spill. This is the first assessment of the vulnerability status of human populations under significant levels of poverty and social inequality, which are particularly dependent on healthy and effective Brazilian MPAs. More than 6,500 enterprises and institutions were mapped, including trade activities, services, tourism, and leisure venues. Most enterprises (34.4%) were involved in the food sector, related to the ocean economy, and, therefore, highly vulnerable to oil spills. Furthermore, the majority (79.3%) of the vulnerable activities are concentrated in multiple-use MPAs, with extractive reserves coming second and accounting for 18%. This result shows the high vulnerability of this tropical coast to oil accidents and the risks to food security for traditional communities. We also found a heterogeneous vulnerability indicator along the coast, with the most vulnerable regions having an undiversified economic matrix heavily dependent on activities such as fishing, family farming, tourism, accommodation, and the food sector. Thus, this study provides a tool to help prevent and mitigate economic losses and increases the understanding of the weaknesses of MPAs in the face of large-scale disasters, thus helping to build socioeconomic and ecological resilience.

The influence of protected fat in supplements on the performance and carcass characteristics of Nellore beef bulls in tropical pasture - Ana Paula Viscardi da Silva; Alexandre Menezes Dias; Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Marina de Nadai Bonin Gomes; Ériklis Nogueira; Gelson dos Santos Difante; Eva Nara Oliveira Gomes; Luciana Junges (Tropical Animal Health and Production, 2022)

Characterisation of Trichoderma strains using FTIR-ATR spectroscopy and molecular analysis - Lucas Henrique Fantin; Ana Lúcia de Souza Madureira Felício; Ciro Hideki Sumida; Ricardo Marcelo Gonçalves; Karla Braga; José Alexandre de França; Marcelo Giovanetti Canteri (European Journal of Plant Pathology, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

Advances in Brazil Nut Tree Ecophysiology: Linking Abiotic Factors to Tree Growth and Fruit Production - Karen Cristina Pires da Costa; José Francisco de Carvalho Gonçalves; Alexandre Leão Gonçalves; Adamir da Rocha Nina Junior; Roberto Kirmayr Jaquetti; Vinícius Fernandes de Souza; Josiane Celerino de Carvalho; Andreia Varmes Fernandes; Joelma Keith Rodrigues; Gleisson de Oliveira Nascimento; Lúcia Helena de O. Wadt; Karen A. Kainer; et al. (Current Forestry Reports, 2022)

Genomic consequences of colonisation, migration and genetic drift in barn owl insular populations of the eastern Mediterranean - Ana Paula Machado; Alexandros Topaloudis; Tristan Cumer; Eléonore Lavanchy; Vasileios Bontzorlos; Renato Ceccherelli; Motti Charter; Nicolaos Kassinis; Petros Lymberakis; Francesca Manzia; Anne‐Lyse Ducrest; Mélanie Dupasquier; et al. (Molecular Ecology, 2022)
The study of insular populations was key in the development of evolutionary theory. The successful colonisation of an island depends on the geographic context, and specific characteristics of the organism and the island, but also on stochastic processes. As a result, apparently identical islands may harbour populations with contrasting histories. Here, we use whole genome sequences of 65 barn owls to investigate the patterns of inbreeding and genetic diversity of insular populations in the eastern Mediterranean Sea. We focus on Crete and Cyprus, islands with similar size, climate and distance to mainland, that provide natural replicates for a comparative analysis of the impacts of microevolutionary processes on isolated populations. We show that barn owl populations from each island have a separate origin, Crete being genetically more similar to other Greek islands and mainland Greece, and Cyprus more similar to the Levant. Further, our data show that their respective demographic histories following colonisation were also distinct. On the one hand, Crete harbours a small population and maintains very low levels of gene flow with neighbouring populations. This has resulted in low genetic diversity, strong genetic drift, increased relatedness in the population and remote inbreeding. Cyprus, on the other hand, appears to maintain enough gene flow with the mainland to avoid such an outcome. Our study provides a comparative population genomic analysis of the effects of neutral processes on a classical island‐mainland model system. It provides empirical evidence for the role of stochastic processes in determining the fate of diverging isolated populations.

Correction to: Physical Exercise as a Modulator of Vascular Pathology and Thrombin Generation to Improve Outcomes After Traumatic Brain Injury - Willian Link Papalia; Alexandre Seixas Nascimento; Gokul Krishna; Núbia Broetto; Ana Flavia Furian; Mauro Schneider Oliveira; Luiz Fernando Freire Royes; Michele Rechia Fighera (Molecular Neurobiology, 2022)

Physical Exercise as a Modulator of Vascular Pathology and Thrombin Generation to Improve Outcomes After Traumatic Brain Injury - Willian Link Papalia; Alexandre Seixas Nascimento; Gokul Krishna; Núbia Broetto; Ana Flavia Furian; Mauro Schneider Oliveira; Luiz Fernando Freire Royes; Michele Rechia Fighera (Molecular Neurobiology, 2022)

Chronic exposure to lead acetate promotes changes in the alveolar bone of rats: microstructural and physical–chemical characterization - Lodinikki Lemoy Davis; Walessa Alana Bragança Aragão; Géssica de Oliveira Lopes; Luciana Guimaraes Eiró; Alexandre Rodrigues Freire; Felippe Bevilacqua Prado; Ana Cláudia Rossi; Allan da Silva Cruz; Kelly das Graças Fernandes Dantas; Alan Rodrigo Leal Albuquerque; Simone Patricia Aranha Paz; Rômulo Simões Angélica; et al. (Environmental Science and Pollution Research, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Unexpected post‐glacial colonisation route explains the white colour of barn owls ( Tyto alba ) from the British Isles - Ana Paula Machado; Tristan Cumer; Christian Iseli; Emmanuel Beaudoing; Anne‐Lyse Ducrest; Melanie Dupasquier; Nicolas Guex; Klaus Dichmann; Rui Lourenço; John Lusby; Hans‐Dieter Martens; Laure Prévost; et al. (Molecular Ecology, 2022)
The climate fluctuations of the Quaternary shaped the movement of species in and out of glacial refugia. In Europe, the majority of species followed one of the described traditional postglacial recolonization routes from the southern peninsulas towards the north. Like most organisms, barn owls are assumed to have colonized the British Isles by crossing over Doggerland, a land bridge that connected Britain to northern Europe. However, while they are dark rufous in northern Europe, barn owls in the British Isles are conspicuously white, a contrast that could suggest selective forces are at play on the islands. Yet, our analysis of known candidate genes involved in coloration found no signature of selection. Instead, using whole genome sequences and species distribution modelling, we found that owls colonised the British Isles soon after the last glaciation, directly from a white coloured refugium in the Iberian Peninsula, before colonising northern Europe. They would have followed a hitherto unknown post‐glacial colonization route to the Isles over a westwards path of suitable habitat in now submerged land in the Bay of Biscay, thus not crossing Doggerland. As such, they inherited the white colour of their Iberian founders and maintained it through low gene flow with the mainland that prevents the import of rufous alleles. Thus, we contend that neutral processes probably explain this contrasting white colour compared to continental owls. With the barn owl being a top predator, we expect future research will show this unanticipated route was used by other species from its paleo community.

Nitrogen uptake kinetics of an enteric methane inhibitor, the red seaweed Asparagopsis armata - Raquel Torres; Leonardo Mata; Rui Santos; Ana Alexandre (Journal of Applied Phycology, 2021)

Ecological risks associated to trace metals of contaminated sediments from a densely urbanized tropical eutrophic estuary - Christiane do Nascimento Monte; Ana Paula de Castro Rodrigues; Alexandre Rafael de Freitas; Bernardo Ferreira Braz; Aline Soares Freire; Renato Campello Cordeiro; Ricardo Erthal Santelli; Wilson Thadeu Valle Machado (Environmental Monitoring and Assessment, 2021)

Swine influenza A virus subtypes circulating in Brazilian commercial pig herds from 2012 to 2019 - Ana Luiza Soares Fraiha; Ana Carolina Diniz Matos; João Luis Reis Cunha; Beatriz Senra Álvares da Silva Santos; Maria Vitória Chaves Peixoto; Anna Gabriella Guimarães Oliveira; Grazielle Cossenzo Florentino Galinari; Heloíza Irtes de Jesus Nascimento; Maria Isabel Maldonado Coelho Guedes; Alexandre de Magalhães Vieira Machado; Erica Azevedo Costa; Zélia Inês Portela Lobato (Brazilian Journal of Microbiology, 2021)

Too simple models may predict the island rule for the wrong reasons - José Alexandre F. Diniz‐Filho; Shai Meiri; Joaquin Hortal; Ana M. C. Santos; Pasquale Raia (Ecology Letters, 2021)
Biddick & Burns (2021) proposed a null/neutral model that reproduces the island rule as a product of random drift. We agree that it is unnecessary to assume adaptive processes driving island dwarfing or gigantism, but several flaws make their approach unrealistic and thus unsuitable as a stochastic model for evolutionary size changes.

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

Plant growth–promoting traits of yeasts isolated from the tank bromeliad Vriesea minarum L.B. Smith and the effectiveness of Carlosrosaea vrieseae for promoting bromeliad growth - Andréa R. Marques; Alessandra A. Resende; Fátima C. O. Gomes; Ana Raquel O. Santos; Carlos A. Rosa; Alexandre A. Duarte; José Pires de Lemos-Filho; Vera Lúcia dos Santos (Brazilian Journal of Microbiology, 2021)

Effects of cigarette smoke extract on bronchial epithelial cells stimulated with Cryptococcus neoformans - Aline Beatriz Mahler Pereira; Jhony Robison Oliveira; Ana Leticia Julio Souza; Leonardo Andrade-Silva; Marcos Vinicius Silva; Paulo Roberto Silva; Mario Leon Silva-Vergara; Alexandre Paula Rogerio (Medical Microbiology and Immunology, 2021)

Potential of Gliricidia sepium (jacq.) Kunth ex Walp. and Mimosa caesalpiniifolia Benth. in silvopastoral systems intercropped with signalgrass [Urochloa decumbens (Stapf) R.D. Webster] - Ana María Herrera; Alexandre Carneiro Leão de Mello; Valéria Xavier de Oliveira Apolinário; José Carlos B. Dubeux Júnior; Márcio Vieira da Cunha; Mércia Virginia Ferreira dos Santos (Agroforestry Systems, 2021)

Quantitative genetics of extreme insular dwarfing: The case of red deer on Jersey - José Alexandre F. Diniz‐Filho; Ana M. C. Santos; Elisa Barreto; Felipe Naves; Wanderson Santos; Kelly Silva Souza; Rejane Santos‐Silva; Ricardo Dobrovolski; Thannya Nascimento Soares; Rosana Tidon; Zander Augusto Spigoloni; Thiago F. Rangel; et al. (Journal of Biogeography, 2021)
Aim The Island Rule—that is, the tendency for body size to decrease in large mammals and increase in small mammals on islands has been commonly evaluated through macroecological or macroevolutionary, pattern‐orientated approaches, which generally fail to model the microevolutionary processes driving either dwarfing or gigantism. Here, we seek to identify which microevolutionary process could have driven extreme insular dwarfism in the extinct dwarf red deer population on the island of Jersey. Location Jersey, UK (Channel Islands). Taxon Red deer ( Cervus elaphus ). Methods We applied an individual‐based quantitative genetics model parameterized with red deer life‐history data to study the evolution of dwarfism in Jersey's deer, considering variations in island area and isolation through time due to sea level changes. Results The body size of red deer on Jersey decreased fast early on, due to phenotypic plasticity, then kept decreasing almost linearly over time down to the actual body size of the Jersey deer (36 kg on average). Only 1% of 10,000 replicates failed to reach that size in our simulations. The distribution of time to adaptation in these simulations was right skewed, with a median of 395 generations (equivalent to roughly 4 kyr), with complete dwarfism effectively occurring in less than 6 kyr 84.6% of times. About 72% of the variation in the time to adaptation between simulations was collectively explained by higher mutational variance, the number of immigrants from the continent after isolation, available genetic variance, heritability, and phenotypic plasticity. Main Conclusions The extreme dwarfing of red deer on Jersey is an expected outcome of high mutational variance, high immigration rate, a wide adaptive landscape, low levels of inbreeding, and high phenotypic plasticity (in the early phase of dwarfing), all occurring within a time window of around 6 kyr. Our model reveals how extreme dwarfism is a plausible outcome of common, well‐known evolutionary processes.

Phosphites for the management of anthracnose in soybean pods - Manoel Batista da Silva Junior; Mário Lucio Vilela de Resende; Edson Ampelio Pozza; Alexandre Ribeiro Resende; Victor Augusto Maia Vasconcelos; Ana Cristina Andrade Monteiro; Gustavo Cesar Dias Silveira; Deila Magna dos Santos Botelho (Journal of Plant Pathology, 2021)

Field Responses of Rice Stalk Stink Bug, Tibraca limbativentris, to Synthetic Sex Pheromone and Isomers of 1,10-Bisaboladien-3-ol - Thais F S De Freitas; E R Hickel; Ashot Khrimian; Miguel Borges; Mirian F F Michereff; José Alexandre Barrigossi; Raúl Alberto Laumann; S D Guggilapu; Josué Sant’Ana; Maria Carolina Blassioli-Moraes (Neotropical Entomology, 2021)

Genetic improvement of Capsicum frutescens: hybrid vigor for anthracnosis resistance and production traits - Ana Flávia Silva Amorim; Thiago Alexandre Santana Gilio; Janaina Barros de Jesus; Luiz Henrique Amorim de Souza; Isabela Vera dos Anjos; Kelly Lana Araujo; Marco Antonio Aparecido Barelli; Sandra da Costa Preisigke; Leonarda Grillo Neves (Euphytica, 2021)

Role of Modulation of Hippocampal Glucose Following Pilocarpine-Induced Status Epilepticus - Igor Santana de Melo; Yngrid Mickaelli Oliveira dos Santos; Amanda Larissa Dias Pacheco; Maisa Araújo Costa; Vanessa de Oliveira Silva; Jucilene Freitas-Santos; Cibelle de Melo Bastos Cavalcante; Reginaldo Correia Silva-Filho; Ana Catarina Rezende Leite; Daniel Góes Leite Gitaí; Marcelo Duzzioni; Robinson Sabino-Silva; et al. (Molecular Neurobiology, 2021)

Application of remote sensing data in gold exploration: targeting hydrothermal alteration using Landsat 8 imagery in northern Portugal - Rui Frutuoso; Alexandre Lima; Ana Cláudia Teodoro (Arabian Journal of Geosciences, 2021)

The impact of El Niño Southern Oscillation on cropping season rainfall variability across Central Brazil - Alexandre Bryan Heinemann; Julian Ramirez‐Villegas; Luís Fernando Stone; Ana Paula Garcia Abreu Silva; David Henriques da Matta; Mario Ernesto Piscoya Diaz (International Journal of Climatology, 2021)
Local‐level understanding of within‐season rainfall variability and its relationship with the El Niño Southern Oscillation (ENSO) can shed light on crop yield variations and establish appropriate cropping calendars in rainfed systems. This requires information on the growing season, including its length, the total rainfall, the onset and cessation of rainfall, the number of wet and dry days, and the optimal sowing window. The objective of this study was to examine the onset and cessation of both the rainy and growing seasons using historical daily rainfall datasets (1980–2013) from 50 weather stations distributed across the main grain production region of Brazil. We then correlated the interannual variability of the climate variables and crop water availability with ENSO (using the Oceanic Niño Index, ONI). Across the study region, the onset of the rainy period ranged from late September to early November, and the cessation period ranged from late March to mid‐April. The onset of the growing season followed that of the rainy season, beginning across central and northern Mato Grosso in mid‐October, followed by Goiás and Tocantins, and finally Rondônia by the end of October. The length of the sowing window was reduced, and the mean optimal sowing date was delayed during La Niña years for most weather stations in the study region. Our results infer the need to adjust the cropping calendars for specific ENSO phases only in regions that conduct crop rotations. Based on rice crop model simulations of water availability, we propose a mean optimal crop sowing calendar for annual crops in Central Brazil. Highlights We analysed the impact of El Niño Southern Oscillation (ENSO) on the growing season characteristics of Central Brazil. The length of the sowing period is markedly reduced during La Niña years across the region. We propose a mean optimal crop sowing calendar for Central Brazil based on crop modelling results of ENSO effects.

Molecular Responses of Mussel Mytilus galloprovincialis Associated to Accumulation and Depuration of Marine Biotoxins Okadaic Acid and Dinophysistoxin-1 Revealed by Shotgun Proteomics - José Carlos Martins; Dany Domínguez-Pérez; Catarina Azevedo; Ana Catarina Braga; Pedro Reis Costa; Hugo Osório; Vitor Vasconcelos; Alexandre Campos (Frontiers in Marine Science, 2020)
The molecular pathways behind the toxicity of diarrheic shellfish toxins (DSTs) in bivalves have been scarcely studied. Thus, a shotgun proteomics approach was applied in this work to understand bivalves’ molecular responses to the dinoflagellate Prorocentrum lima (1.0 × 10 6 cells/L). Protein expression along with toxins levels were analyzed in the gills and digestive gland of the mussel Mytilus galloprovincialis during and after exposure to this toxic strain. Results revealed an accumulation of OA and DTX1 only in the digestive gland with maximum amounts attained at the end of uptake phase (day 5; 2819.2 ± 522.2 μg OA/kg and 1107.1 ± 267.9 μg DTX1/kg). At the end of the depuration phase (day 20), 16% and 47% of total OA and DTX1 concentrations remained in the digestive gland tissues, respectively. The shotgun proteomic analyses yielded 3051 proteins in both organs. A total of 56 and 54 differentially expressed proteins (DEPs) were revealed in the digestive gland and gills, respectively. Both organs presented the same response dynamics along the experiment, although with tissue-specific features. The early response (3 days uptake) was characterized by a high number of DEPs, being more marked in gills, in relation to the latter time points (5 days uptake and depuration). Functional enrichment analysis revealed the up-regulation of carboxylic (GO:0046943) and organic acid transmembrane transporter activity (GO:0005342) pathways after 3 days uptake for digestive gland. Matching to these pathways are a group of proteins related to transmembrane transport and response to toxic substances and xenobiotics, namely P-glycoprotein (ABCB11), Sodium-dependent proline transporter (SLC6A7), and Sideroflexin-1 (SFXN1). According to Clusters of Orthologous Groups (GOs) categories, most of the DEPs found for digestive gland in all time-points were related with “cellular processes and signaling” and involving signal transduction mechanisms, cytoskeleton and post-translational modification, protein turnover, chaperone functions. In gills, the early uptake phase was marked by a balance between DEPs related with “cellular processes and signaling” and “metabolism.” Depuration is clearly marked by processes related with “metabolism,” mainly involving secondary metabolites biosynthesis, transport, and catabolism. Proteomic data are available via ProteomeXchange with identifier PXD022293.

Seasonality Effects on Antibacterial and Antibiotic Potentiating Activity against Multidrug-Resistant Strains of Escherichia coli and Staphylococcus aureus and ATR-FTIR Spectra of Essential Oils from Vitex gardneriana Leaves - Raimundo Luiz Silva Pereira; Thiago Sampaio de Freitas; Priscilla Ramos Freitas; Ana Carolina Justino de Araújo; Fábia Ferreira Campina; Kleber Ribeiro Fidelis; Jean Parcelli Costa do Vale; Antônio César Honorato Barreto; Henrique Douglas Melo Coutinho; Paulo Nogueira Bandeira; Alexandre Magno Rodrigues Teixeira; Hélcio Silva dos Santos (Current Microbiology, 2020)

Feasibility of Co-Treating Olive Mill Wastewater and Acid Mine Drainage - Jorge Dias Carlier; Ana Teresa Luís; Luís Miguel Alexandre; Maria Clara Costa (Mine Water and the Environment, 2020)
Previous tests using a growth medium and olive mill wastewater (OMWW) have shown that it supplies carbon and electron donors suitable for sulphate reducing bacteria (SRB). We assessed the co-treatment of acid mine drainage (AMD) and OMWW using SRB-enriched bioreactors and identified the most abundant bacterial populations present under optimized conditions. The process requires a neutralizing agent to create optimal pH conditions for successful removal of the AMD’s main contaminants. Concentrations of SO 4 2− , Al, Fe, Cu, Zn, and Mn decreased to below Portugal’s maximum admissible values for irrigation waters, and all but Mn were reduced to less than Portugal’s emission limit values (ELVs) for wastewater discharges. Phenol concentrations—the main pollutants in OMWW—dropped to values between 1/10 and 1/5 their initial concentrations in batch tests using mixtures of AMD and OMWW, and to 1/2 their initial concentrations in flow-through tests. The final total phenol concentrations were still above the ELV for wastewater discharges, but phenols are not regulated in irrigation waters, and OMWW is used by some producers to irrigate soils. Six main SRB groups were identified as likely having a fundamental role in the bioremediation process: the genera Desulfovibrio , Sulfurospirillum , and Acetobacter and the families Sphingomonadaceae , Prevotellaceae , and Deferribacteraceae .

Decomposition of senescent leaves of signalgrass (Urochloa decumbens Stapf. R. Webster) and arboreal legumes in silvopastoral systems - Ana María Herrera; Alexandre Carneiro Leão de Mello; Valéria Xavier de Oliveira Apolinário; José Carlos Batista Dubeux Júnior; Valdson José da Silva; Mércia Virginia Ferreira dos Santos; Márcio Vieira da Cunha (Agroforestry Systems, 2020)

Functional and structural evaluation of the antileukaemic enzyme l-asparaginase II expressed at low temperature by different Escherichia coli strains - Werner Alfinito Feio de Moura; Leonardo Schultz; Carlos Alexandre Breyer; Ana Laura Pires de Oliveira; Carlos Abrunhosa Tairum; Gabriella Costa Fernandes; Marcos Hikari Toyama; Adalberto Pessoa-Jr; Gisele Monteiro; Marcos Antonio de Oliveira (Biotechnology Letters, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Algrizea Minor Sobral, Faria & Proença (Myrteae, Myrtaceae): chemical composition, antinociceptive, antimicrobial and antioxidant activity of essential oil - Bruno Oliveira de Veras; Yago Queiroz dos Santos; Fernanda Granja da Silva Oliveira; Jackson Roberto Guedes da Silva Almeida; Alexandre Gomes da Silva; Maria Tereza dos Santos Correia; Katharina Marques Diniz; João Ricardhis Saturnino de Oliveira; Vera Lúcia de Menezes Lima; Daniela Maria do Amaral Ferraz Navarro; Júlio César Ribeiro de Oliveira Farias de Aguiar; Maria Betânia Melo de Oliveira; et al. (Natural Product Research, 2020)

CPAMD8 loss-of-function underlies non-dominant congenital glaucoma with variable anterior segment dysgenesis and abnormal extracellular matrix - Juan-Manuel Bonet-Fernández; José-Daniel Aroca-Aguilar; Marta Corton; Ana-Isabel Ramírez; Susana Alexandre-Moreno; María-Teresa García-Antón; Juan-José Salazar; Jesús-José Ferre-Fernández; Raquel Atienzar-Aroca; Cristina Villaverde; Ionut Iancu; Alejandra Tamayo; et al. (Human Genetics, 2020)

Current climate, but also long‐term climate changes and human impacts, determine the geographic distribution of European mammal diversity - Ana M. C. Santos; Marcus V. Cianciaruso; Ana Márcia Barbosa; Luis Mauricio Bini; José Alexandre F. Diniz‐Filho; Frederico V. Faleiro; Sidney F. Gouveia; Rafael Loyola; Nagore G. Medina; Thiago F. Rangel; Geiziane Tessarolo; Joaquín Hortal (Global Ecology and Biogeography, 2020)
Aim Historical climate variations, current climate and human impacts are known to influence current species richness, but their effects on phylogenetic and trait diversity have been seldom studied. We investigated the relationship of these three factors with the independent variations of species, phylogenetic and trait diversity of European mammals. Considering the position of the 0 ºC isotherm in the Last Glacial Maximum as a tipping point, we tested the following hypotheses: northern European assemblages host fewer species than southern European ones; northern areas harbour trait and phylogenetically clustered assemblages, while the more stable southern areas host random or overdispersed assemblages; and species richness correlates positively with human influence, while phylogenetic and trait diversity show clustered patterns in areas with stronger human influence. Location Western Palaearctic. Time period Current and Late Pleistocene effects on present‐day diversity. Major taxa studied Terrestrial mammals. Methods We used a novel analytical approach based on distance matrices to separate the independent variations of species, phylogenetic and trait diversity, and assessed their relationships with current climate, climate stability and human influence through structural equation models. Results The species‐poor assemblages from northern Europe show higher phylogenetic and trait clustering than the more stable richer southern areas. However, no assemblage presented trait or phylogenetic overdispersion. Current climate is the primary driver of phylogenetic and trait diversity, while species richness is affected similarly by both current and past climates. Higher human influence correlates positively with species richness and trait diversity, both directly and by mediating indirect effects of present climate. Main conclusions Current climate, climate stability and human influence affect the studied aspects of diversity, although the form and magnitude of their effects vary through space. Importantly, higher levels of human disturbances correlate with more species rich and trait diverse assemblages, an apparently counterintuitive result that deserves further study.

Phenolic compounds: antioxidant and larvicidal potential of Smilax brasiliensis Sprengel leaves - Paula Avelar Amado; Ana Hortência Fonsêca Castro; Stênio Nunes Alves; Denise Brentan Silva; Carlos Alexandre Carollo; Luciana Alves Rodrigues dos Santos Lima (Natural Product Research, 2020)

Bacillus thuringiensis endotoxin production: a systematic review of the past 10 years - José Manoel W. Duarte Neto; Maria Carolina de A. Wanderley; Túlio Alexandre F. da Silva; Daniela A. Viana Marques; Gilvanda R. da Silva; Josimar Fernandes Gurgel; José de Paula Oliveira; Ana Lúcia F. Porto (World Journal of Microbiology and Biotechnology, 2020)

Assessing drought in the drylands of northeast Brazil under regional warming exceeding 4 °C - Jose A. Marengo; Ana Paula M. A. Cunha; Carlos A. Nobre; Germano G. Ribeiro Neto; Antonio R. Magalhaes; Roger R. Torres; Gilvan Sampaio; Felipe Alexandre; Lincoln M. Alves; Luz A. Cuartas; Karinne R. L. Deusdará; Regina C. S. Álvala (Natural Hazards, 2020)

Proteus mirabilis causing cellulitis in broiler chickens - Matheus Silva Sanches; Ana Angelita Sampaio Baptista; Marielen de Souza; Maísa Fabiana Menck-Costa; Larissa Justino; Erick Kenji Nishio; Alexandre Oba; Ana Paula Frederico Rodrigues Loure Bracarense; Sergio Paulo Dejato Rocha (Brazilian Journal of Microbiology, 2020)

Response of soybean to soil waterlogging associated with iron excess in the reproductive stage - Allan de Marcos Lapaz; Liliane Santos de Camargos; Camila Hatsu Pereira Yoshida; Ana Carolina Firmino; Paulo Alexandre Monteiro de Figueiredo; Jailson Vieira Aguilar; Artur Bernardeli Nicolai; Wesller da Silva de Paiva; Victor Hugo Cruz; Rafael Simões Tomaz (Physiology and Molecular Biology of Plants, 2020)

The influence of species abundance, diet and phylogenetic affinity on the co-occurrence of butterflyfishes - Lucas T. Nunes; Alexandre C. Siqueira; Isadora Cord; Benjamin M. Ford; Ana M. R. Liedke; Carlos E. L. Ferreira; Sergio R. Floeter (Marine Biology, 2020)

Heavy metal concentrations in Brazilian port areas and their relationships with microorganisms: can pollution in these areas change the microbial community? - Bruna Del Busso Zampieri; Vanessa da Costa Andrade; Roberta Merguizo Chinellato; Carlos Alexandre Borges Garcia; Marcos Antônio de Oliveira; Gunther Brucha; Ana Julia Fernandes Cardoso de Oliveira (Environmental Monitoring and Assessment, 2020)

Seroepidemiological study of Caseous lymphadenitis in sheep from the Northeast region of Brazil using an indirect ELISA - José Romero Alexandre Alves; Areano Ethério Moreira de Farias; Denize Monteiro dos Anjos; Ana Milena Cézar Lima; Patrícia Yoshida Faccioli-Martins; Carlos José Hoff de Souza; Raymundo Rizaldo Pinheiro; Francisco Selmo Fernandes Alves; Sérgio Santos de Azevedo; Clebert José Alves (Tropical Animal Health and Production, 2020)

The Tropical Seagrass Halophila stipulacea: Reviewing What We Know From Its Native and Invasive Habitats, Alongside Identifying Knowledge Gaps - Gidon Winters; Sven Beer; Demian A. Willette; Inés G. Viana; Kelcie L. Chiquillo; Pedro Beca-Carretero; Betty Villamayor; Tomás Azcárate-García; Rachamim Shem-Tov; Bridget Mwabvu; Luciana Migliore; Alice Rotini; et al. (Frontiers in Marine Science, 2020)

Antimicrobial activity and antibiotic synergy of a biphosphinic ruthenium complex against clinically relevant bacteria - Alexandre Lopes Andrade; Mayron Alves de Vasconcelos; Francisco Vassiliepe de Sousa Arruda; Luiz Gonzaga do Nascimento Neto; José Marcos da Silveira Carvalho; Ana Claudia Silva Gondim; Luiz Gonzaga de França Lopes; Eduardo Henrique Silva Sousa; Edson Holanda Teixeira (Biofouling, 2020)

Novel specific primers for rapid identification of Macrophomina species - Kledson M. Santos; Graziele S. Lima; Ana P. O. Barros; Alexandre R. Machado; Cristina M. Souza-Motta; Kamila C. Correia; Sami Jorge Michereff (European Journal of Plant Pathology, 2020)

Correction to: Ecological restoration as a strategy for mitigating and adapting to climate change: lessons and challenges from Brazil - Mercedes M. C. Bustamante; José Salomão Silva; Aldicir Scariot; Alexandre Bonesso Sampaio; Daniel Luis Mascia Vieira; Edenise Garcia; Edson Sano; Geraldo Wilson Fernandes; Giselda Durigan; Iris Roitman; Isabel Figueiredo; Ricardo Ribeiro Rodrigues; et al. (Mitigation and Adaptation Strategies for Global Change, 2020)

Analyses of plumage coloration and genetic variation confirm the hybridization of Pipra fasciicauda and Pipra aureola in the Brazilian Amazon basin - Larissa Sampaio; Dnilson Oliveira Ferraz; Ana Carolina Moreira da Costa; Alexandre Aleixo; Pablo Vieira Cerqueira; Juliana Araripe; Péricles Sena do Rêgo (Journal of Ornithology, 2020)

Overcoming the worst of both worlds: integrating climate change and habitat loss into spatial conservation planning of genetic diversity in the Brazilian Cerrado - José Alexandre Felizola Diniz-Filho; Ana Clara de Oliveira Ferraz Barbosa; Lázaro José Chaves; Kelly da Silva e Souza; Ricardo Dobrovolski; Ludmila Rattis; Levi Carina Terribile; Matheus Souza Lima-Ribeiro; Guilherme de Oliveira; Fernanda Thiesen Brum; Rafael Loyola; Mariana Pires de Campos Telles (Biodiversity and Conservation, 2020)

Boron, zinc and manganese suppress rust on coffee plants grown in a nutrient solution - Cristian David Plaza Pérez; Edson Ampélio Pozza; Adélia Aziz Alexandre Pozza; Wade H. Elmer; Andreane Bastos Pereira; Daniel da Silva Gomes Guimarães; Ana Cristina Andrade Monteiro; Mário Lúcio Vilela de Rezende (European Journal of Plant Pathology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Do wind turbines impact plant community properties in mountain region? - Ileana Pătru-Stupariu; Ana-Maria Calotă; Mathieu Santonja; Paulina Anastasiu; Ioana Stoicescu; Iovu Adrian Biriş; Mihai-Sorin Stupariu; Alexandre Buttler (Biologia, 2019)

Growth, Sexual Maturity and Dimorphism in Six Species of Snapping Shrimps of the Genus Alpheus (Decapoda: Alpheidae) - Ana Carla Costa-Souza; José Roberto Botelho de Souza; Alexandre Oliveira Almeida (Thalassas: An International Journal of Marine Sciences, 2019)

Ecological restoration as a strategy for mitigating and adapting to climate change: lessons and challenges from Brazil - Mercedes M. C. Bustamante; José Salomão Silva; Aldicir Scariot; Alexandre Bonesso Sampaio; Daniel Luis Mascia; Edenise Garcia; Edson Sano; Geraldo Wilson Fernandes; Giselda Durigan; Iris Roitman; Isabel Figueiredo; Ricardo Ribeiro Rodrigues; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

Inventory and Quantification of Geosites in the State Tourist Park of Alto Ribeira (PETAR, São Paulo State, Brazil) - Ana Rita Rodrigues Ferreira; Heros Augusto Santos Lobo; José Alexandre de Jesus Perinotto (Geoheritage, 2019)

Experimental evidence that maleic acid markedly compromises glutamate oxidation through inhibition of glutamate dehydrogenase and α-ketoglutarate dehydrogenase activities in kidney of developing rats - Ana Cristina Roginski; Cristiane Cecatto; Simone Magagnin Wajner; Fernanda Dal’Maso Camera; Roger Frigério Castilho; Moacir Wajner; Alexandre Umpierrez Amaral (Molecular and Cellular Biochemistry, 2019)

Spectral characterization and quantification of Phakopsora pachyrhizi urediniospores by Fourier transformed infrared with attenuated total reflectance - Lucas Henrique Fantin; Ana Lúcia de Souza Madureira Felício; Karla Braga; Giancarlo Michelino Gaeta; José Alexandre de França; Marcelo Giovanetti Canteri (European Journal of Plant Pathology, 2019)

Zika Virus Infection of Human Mesenchymal Stem Cells Promotes Differential Expression of Proteins Linked to Several Neurological Diseases - Walter O. Beys-da-Silva; Rafael L. Rosa; Lucélia Santi; Markus Berger; Sung Kyu Park; Alexandre R. Campos; Paula Terraciano; Ana Paula M. Varela; Thais F. Teixeira; Paulo M. Roehe; André Quincozes-Santos; John R. Yates; et al. (Molecular Neurobiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Seroepidemiological characterization and risk factors associated with seroconversion to Corynebacterium pseudotuberculosis in goats from Northeastern Brazil - Areano Ethério Moreira de Farias; José Romero Alexandre Alves; Francisco Selmo Fernandes Alves; Raymundo Rizaldo Pinheiro; Patrícia Yoshida Faccioli-Martins; Ana Milena César Lima; Sérgio Santos de Azevedo; Clebert José Alves (Tropical Animal Health and Production, 2019)

Versican silencing in BeWo cells and its implication in gestational trophoblastic diseases - Keyla S. N. Pires; Sue Y. Sun; Camilla M. Gonçalves; Jaqueline C. Santos; Liliane P. G. Tenorio; Rayane M. Botelho; Ana Lucia M. Silva; Hillary Gabriela S. Oliveira; Karen Priscila T. Pendeloski; Silvia Daher; Karen S. C. Borbely; Alexandre U. Borbely (Histochemistry and Cell Biology, 2019)

Vegetable oil and carbohydrate-rich diets marginally affected intestine histomorphology, digestive enzymes activities, and gut microbiota of gilthead sea bream juveniles - Carolina Castro; Ana Couto; Alexandre F. Diógenes; Geneviève Corraze; Stéphane Panserat; Cláudia R. Serra; Aires Oliva-Teles (Fish Physiology and Biochemistry, 2019)

Heterologous expression of nifA or nodD genes improves chickpea-Mesorhizobium symbiotic performance - José Rodrigo da-Silva; Esther Menéndez; Fernando Eliziário; Pedro F. Mateos; Ana Alexandre; Solange Oliveira (Plant and Soil, 2019)

Chronic Metabolic Derangement-Induced Cognitive Deficits and Neurotoxicity Are Associated with REST Inactivation - Aline Pertile Remor; Rodrigo Augusto da Silva; Filipe José de Matos; Viviane Glaser; Roberta de Paula Martins; Karina Ghisoni; Débora da Luz Scheffer; Denise Carleto Andia; Daniele Portinho; Ana Paula de Souza; Paulo Alexandre de Oliveira; Rui Daniel Prediger; et al. (Molecular Neurobiology, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Layer-specific reduced neuronal density in the orbitofrontal cortex of older adults with obsessive–compulsive disorder - Katia Cristina de Oliveira; Lea Tenenholz Grinberg; Marcelo Queiroz Hoexter; Helena Brentani; Claudia Kimie Suemoto; Fabiano Gonçalves Nery; Luzia Carreira Lima; Ana Tereza Di Lorenzo Alho; José Marcelo Farfel; Renata Eloah de Lucena Ferretti-Rebustini; Renata Elaine Paraizo Leite; Ariane Cristine Moretto; et al. (Brain Structure and Function, 2019)

Age, growth, and reproductive biology of the Atlantic spadefish Chaetodipterus faber in southern Brazil - Marcelo Soeth; Luis Fernando Fávaro; Henry Louis Spach; Felippe Alexandre Daros; Ana Emília Woltrich; Alberto Teodorico Correia (Ichthyological Research, 2019)

Shotgun proteomics of ascidians tunic shed light into the interaction between host and their associated bacteria - Ana Matos; Dany Domínguez-Pérez; Daniela Almeida; Alexandre Campos; Hugo Osório; Vitor Vasconcelos; Agostinho Antunes (Frontiers in Marine Science, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Campylobacter jejuni virulence genes and immune-inflammatory biomarkers association with growth impairment in children from Northeastern Brazil - Herlice do Nascimento Veras; Pedro H. Q. S. Medeiros; Samilly A. Ribeiro; Thiago M. Freitas; Ana K. S. Santos; Marília S. M. G. Amaral; Mariana D. Bona; Alexandre Havt; Ila F. N. Lima; Noélia L. Lima; Alessandra Di Moura; Álvaro M. Leite; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Conflict between heterozygote advantage and hybrid incompatibility in haplodiploids (and sex chromosomes) - Ana‐Hermina Ghenu; Alexandre Blanckaert; Roger K. Butlin; Jonna Kulmuni; Claudia Bank (Molecular Ecology, 2018)
In many diploid species, the sex chromosomes play a special role in mediating reproductive isolation. In haplodiploids, where females are diploid and males haploid, the whole genome behaves similarly to the X/Z chromosomes of diploids. Therefore, haplodiploid systems can serve as a model for the role of sex chromosomes in speciation and hybridization. A previously described population of Finnish Formica wood ants displays genome‐wide signs of ploidally and sexually antagonistic selection resulting from hybridization. Here, hybrid females have increased survivorship but hybrid males are inviable. To understand how the unusual hybrid population may be maintained, we developed a mathematical model with hybrid incompatibility, female heterozygote advantage, recombination and assortative mating. The rugged fitness landscape resulting from the co‐occurrence of heterozygote advantage and hybrid incompatibility results in a sexual conflict in haplodiploids, which is caused by the ploidy difference. Thus, whereas heterozygote advantage always promotes long‐term polymorphism in diploids, we find various outcomes in haplodiploids in which the population stabilizes either in favour of males, females or via maximizing the number of introgressed individuals. We discuss these outcomes with respect to the potential long‐term fate of the Finnish wood ant population and provide approximations for the extension of the model to multiple incompatibilities. Moreover, we highlight the general implications of our results for speciation and hybridization in haplodiploids versus diploids and how the described fitness relationships could contribute to the outstanding role of sex chromosomes as hotspots of sexual antagonism and genes involved in speciation.

Estuarine flooding in urban areas: enhancing vulnerability assessment - Pedro Pinto Santos; Alexandre Oliveira Tavares; Paula Freire; Ana Rilo (Natural Hazards, 2018)

Thermoregulatory responses and reproductive traits in composite beef bulls raised in a tropical climate - Narian Romanello; José de Brito Lourenço Junior; Waldomiro Barioni Junior; Felipe Zandonadi Brandão; Cintia Righetti Marcondes; José Ricardo Macedo Pezzopane; Messy Hannear de Andrade Pantoja; Daniela Botta; Alessandro Giro; Ana Beatriz Bossois Moura; Andréa do Nascimento Barreto; Alexandre Rossetto Garcia (International Journal of Biometeorology, 2018)

5-Nitroimidazole-derived Schiff bases and their copper(II) complexes exhibit potent antimicrobial activity against pathogenic anaerobic bacteria - Alexandre A. Oliveira; Ana P. A. Oliveira; Lucas L. Franco; Micael O. Ferencs; João F. G. Ferreira; Sofia M. P. S. Bachi; Nivaldo L. Speziali; Luiz M. Farias; Paula P. Magalhães; Heloisa Beraldo (BioMetals, 2018)

Marine Biotechnology in Brazil: Recent Developments and Its Potential for Innovation - Fabiano Thompson; Ricardo Krüger; Cristiane C. Thompson; Roberto G. S. Berlinck; Ricardo Coutinho; Melissa F. Landell; Mauro Pavão; Paulo A. S. Mourão; Ana Salles; Naiane Negri; Fabyano A. C. Lopes; Vitor Freire; et al. (Frontiers in Marine Science, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

The Rocky Mountains as a dispersal barrier between barn owl ( Tyto alba ) populations in North America - Ana Paula Machado; Laura Clément; Vera Uva; Jérôme Goudet; Alexandre Roulin (Journal of Biogeography, 2018)
Aim Geological barriers within a species range play a key role in shaping patterns of genetic variation by restricting gene flow. Mountain ranges are particularly imposing barriers responsible for creating genetic differentiation across multiple taxa, from small amphibians to large mammals and birds. Here, we examined the population structure of North American barn owls ( Tyto alba ) and investigated whether the Rocky Mountains influence gene flow and dispersal at the continental scale. Location Continental North America. Methods We collected 292 museum samples covering the species range, genotyped them at 20 microsatellite markers and sequenced 410 bp of the mitochondrial gene ND 6 . Population and landscape genetics tools were used to study range‐wide patterns of structure and identify gene flow barriers. Ring recapture data were also analysed to investigate individual movement patterns and frequency of exchanges between both sides of the Rocky Mountains. Results We found faint overall genetic structure, which is consistent with barn owl's high mobility across its continuous range. Nonetheless, we identified two distinct genetic groups on the western and eastern regions of the Rocky Mountains with a likely contact point through the narrow southern pass between them and the Sierra Madre Occidental in Mexico. Accordingly, most recaptured barn owls remain on the same side of the mountains. The Rockies appear to significantly isolate the populations in the west, which, as a consequence, display lower genetic diversity than their counterparts to the east. Main conclusions The Rocky Mountains appear to constrain barn owl dispersal and gene flow. Our study supports the hypothesis that regional landscape barriers can shape gene flow and population structure even in highly mobile organisms.

Interactions between global climate change strategies and local air pollution: lessons learnt from the expansion of the power sector in Brazil - Joana Portugal-Pereira; Alexandre Koberle; André F. P. Lucena; Pedro R. R. Rochedo; Mariana Império; Ana Monteiro Carsalade; Roberto Schaeffer; Peter Rafaj (Climatic Change, 2018)

Population Structure of the Shrimp Alpheus estuariensis (Caridea: Alpheidae) in a Tropical Estuarine Tidal Mudflat - Ana Carla Costa-Souza; José Roberto Botelho de Souza; Marina de Sá Leitão Câmara de Araújo; Alexandre Oliveira Almeida (Thalassas: An International Journal of Marine Sciences, 2018)

BacHBerry: BACterial Hosts for production of Bioactive phenolics from bERRY fruits - Alexey Dudnik; A. Filipa Almeida; Ricardo Andrade; Barbara Avila; Pilar Bañados; Diane Barbay; Jean-Etienne Bassard; Mounir Benkoulouche; Michael Bott; Adelaide Braga; Dario Breitel; Rex Brennan; et al. (Phytochemistry Reviews, 2018)

Chemical composition, antioxidant and cytotoxic activities of extracts from the leaves of Smilax brasiliensis Sprengel (Smilacaceae) - Paula Avelar Amado; Vany Ferraz; Denise Brentan da Silva; Carlos Alexandre Carollo; Ana Hortência Fonsêca Castro; Luciana Alves Rodrigues dos Santos Lima (Natural Product Research, 2018)

Aquaporin-4 as a New Target against Methamphetamine-Induced Brain Alterations: Focus on the Neurogliovascular Unit and Motivational Behavior - Ricardo Alexandre Leitão; José Sereno; João Miguel Castelhano; Sónia Isabel Gonçalves; Vanessa Coelho-Santos; Carlos Fontes-Ribeiro; Miguel Castelo-Branco; Ana Paula Silva (Molecular Neurobiology, 2018)

Variation in the composition and activity of ants on defense of host plant Turnera subulata (Turneraceae): strong response to simulated herbivore attacks and to herbivore’s baits - Nayara G. Cruz; Paulo F. Cristaldo; Leandro Bacci; Camilla S. Almeida; Gabriela P. Camacho; Alisson S. Santana; Efrem J. M. Ribeiro; Alexandre P. Oliveira; Abraão A. Santos; Ana P. A. Araújo (Arthropod-Plant Interactions, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Morpho-physiological Tolerance Mechanisms of Talinum patens to Lead - Guilherme Gonzales de Souza; Ana Lúcia Mendes Pinheiro; Josiele Aparecida Silva; Valdir Veroneze-Júnior; Marília Carvalho; Alexandre Carvalho Bertoli; Sandro Barbosa; Thiago Corrêa de Souza (Water, Air, & Soil Pollution, 2018)

Patterns, biases and prospects in the distribution and diversity of Neotropical snakes - Thaís B. Guedes; Ricardo J. Sawaya; Alexander Zizka; Shawn Laffan; Søren Faurby; R. Alexander Pyron; Renato S. Bérnils; Martin Jansen; Paulo Passos; Ana L. C. Prudente; Diego F. Cisneros‐Heredia; Henrique B. Braz; et al. (Global Ecology and Biogeography, 2018)
Motivation We generated a novel database of Neotropical snakes (one of the world's richest herpetofauna) combining the most comprehensive, manually compiled distribution dataset with publicly available data. We assess, for the first time, the diversity patterns for all Neotropical snakes as well as sampling density and sampling biases. Main types of variables contained We compiled three databases of species occurrences: a dataset downloaded from the Global Biodiversity Information Facility (GBIF), a verified dataset built through taxonomic work and specialized literature, and a combined dataset comprising a cleaned version of the GBIF dataset merged with the verified dataset. Spatial location and grain Neotropics, Behrmann projection equivalent to 1° × 1°. Time period Specimens housed in museums during the last 150 years. Major taxa studied Squamata: Serpentes. Software format Geographical information system (GIS). Results The combined dataset provides the most comprehensive distribution database for Neotropical snakes to date. It contains 147,515 records for 886 species across 12 families, representing 74% of all species of snakes, spanning 27 countries in the Americas. Species richness and phylogenetic diversity show overall similar patterns. Amazonia is the least sampled Neotropical region, whereas most well‐sampled sites are located near large universities and scientific collections. We provide a list and updated maps of geographical distribution of all snake species surveyed. Main conclusions The biodiversity metrics of Neotropical snakes reflect patterns previously documented for other vertebrates, suggesting that similar factors may determine the diversity of both ectothermic and endothermic animals. We suggest conservation strategies for high‐diversity areas and sampling efforts be directed towards Amazonia and poorly known species.

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Production of Electrospun Fast-Dissolving Drug Delivery Systems with Therapeutic Eutectic Systems Encapsulated in Gelatin - Francisca Mano; Marta Martins; Isabel Sá-Nogueira; Susana Barreiros; João Paulo Borges; Rui L. Reis; Ana Rita C. Duarte; Alexandre Paiva (AAPS PharmSciTech, 2017)

Tidal effects on phytoplankton assemblages in a near‐pristine estuary: a trait‐based approach for the case of a shallow tropical ecosystem in Brazil - Gleyci A. O. Moser; Fernanda Reinhardt Piedras; Anna Beatriz J. Oaquim; Daiana S. Souza; Suzana G. Leles; Domênica T. de Lima; Ana Beatriz A. Ramos; Cássia de O. Farias; Alexandre M. Fernandes (Marine Ecology, 2017)
The study of near‐pristine estuaries can be used as a tool for mitigation projects of harmful effects in anthropogenic eutrophic systems, since one can analyze the effect of temporal and spatial variations generated mainly by natural forces. Phytoplankton taxonomy has been used as a classical indicator to assess changes in transitional water communities, however alternative methods based on morphological, behavioral and physiological traits offer the opportunity to compare sites or moments with different taxonomic compositions. Our goal, in this context, is to evaluate phytoplankton community short‐term and seasonal variability in a near‐pristine estuary, Barra Grande estuary (Ilha Grande, RJ , Brazil), through species functional traits and thus community functional diversity. Samplings were carried out in a mooring in complete tidal cycles, seasonally during 2012. Our results showed a diverse phytoplankton community with 38 frequent and abundant taxa, marked by density variation (1.2 × 10.4–2 × 10.7 cell L −1 ) in depth, with abundance inversely related to tidal currents. The functional structure of the phytoplankton community measured by functional diversity ( FD ), varied seasonally in and across a gradient of tidal energy. A core community, mainly represented by flagellates and dinoflagellates, occurred in all observations and was highly functional (high FD ), exploiting a variety of habitats. The chain‐forming diatoms were associated with high tidal energy, and occurred in higher densities during summer. Phytoplankton cell size, cell shape, and the ability to form colonies are extremely plastic traits that can be regulated by the environment, however, isolated tychopelagic diatoms were present in the study area across all seasons, with higher contributions in autumn and winter, reflecting the shallow characteristic of this system. During the winter, an exposed sandbar was formed, and the lack of connection with the ocean resulted in an abundance of riverine and brackish water taxa. In this near‐pristine estuary the densities and occurrences of HAB phytoplankton are low. Trait‐based analyses add information about community structure, which can be impacted by anthropogenic actions in urbanized coastal systems. Thus the information provided by this study regarding phytoplankton functional diversity and its relation to nutrients and hydrography in Barra Grande Estuary can be applied as a baseline model for the development of public policies.

Curcuma longa as additive in the diet for Astyanax aff. bimaculatus - Pollyanna de Moraes França Ferreira; Maria Tatiana Soares Martins; Débora Werneck Caldas; Juliana Rodrigues Gomes; Jerusa Maria de Oliveira; Ana Lucia Salaro; Juliana Silva Rocha; Jener Alexandre Sampaio Zuanon (Fish Physiology and Biochemistry, 2017)

Chromosomal characteristics of rDNA in a conserved karyotype of two Sternopygus macrurus (Gymnotiformes: Sternopygidae) populations from upper Paraná River basin - Carlos Alexandre Fernandes; Lucas Baumgärtner; Leonardo Marcel Paiz; Vladimir Pavan Margarido; Ana Luiza de Brito Portela-Castro (Biologia, 2017)

Arcobacter spp. in fecal samples from Brazilian farmed caimans (Caiman yacare, Daudin 1802) - Maria Gabriela Xavier Oliveira; Leandro Nogueira Pressinotti; Giovane Spínola Carvalho; Mirela Caroline Vilela Oliveira; Luisa Zanolli Moreno; Carlos Emilio Cabrera Matajira; Alessandro Spínola Bergamo; Victor Manuel Aleixo; Alexandre Caixeta Veiga; Elvis de Souza Corsino; Ana Paula Guarnieri Christ; Maria Inês Zanolli Sato; et al. (Tropical Animal Health and Production, 2017)

Effects of Chrysosporum (Aphanizomenon) ovalisporum extracts containing cylindrospermopsin on growth, photosynthetic capacity, and mineral content of carrots (Daucus carota) - Remedios Guzmán-Guillén; Alexandre Campos; Joana Machado; Marisa Freitas; Joana Azevedo; Edgar Pinto; Agostinho Almeida; Ana M. Cameán; Vitor Vasconcelos (Ecotoxicology, 2017)

A local-scale approach to estuarine flood risk management - Paula Freire; Alexandre O. Tavares; Luís Sá; Anabela Oliveira; André B. Fortunato; Pedro P. dos Santos; Ana Rilo; João L. Gomes; João Rogeiro; Rui Pablo; Pedro J. Pinto (Natural Hazards, 2016)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

Involvement of β adrenergic receptors in spasmolytic effect of caulerpine on guinea pig ileum - Luiz Henrique Agra Cavalcante-Silva; Ana Carolina de Carvalho Correia; Jéssica Celestino Ferreira Sousa; José Maria Barbosa-Filho; Bárbara Viviana de Oliveira Santos; George Emmanuel C. de Miranda; Magna Suzana Alexandre-Moreira; Fabiana de Andrade Cavalcante (Natural Product Research, 2016)

Oxidative Stress, Disrupted Energy Metabolism, and Altered Signaling Pathways in Glutaryl-CoA Dehydrogenase Knockout Mice: Potential Implications of Quinolinic Acid Toxicity in the Neuropathology of Glutaric Acidemia Type I - Bianca Seminotti; Alexandre Umpierrez Amaral; Rafael Teixeira Ribeiro; Marília Danyelle Nunes Rodrigues; Ana Laura Colín-González; Guilhian Leipnitz; Abel Santamaría; Moacir Wajner (Molecular Neurobiology, 2016)

Nitrogen Uptake and Internal Recycling in Zostera marina Exposed to Oyster Farming: Eelgrass Potential as a Natural Biofilter - Jose Sandoval-Gil; Ana Alexandre; Rui Santos; Víctor F. Camacho-Ibar (Estuaries and Coasts, 2016)

Distribution and sources of sterol biomarkers in sediments collected from a tropical estuary in Northeast Brazil - Morgana Frena; Ana Paula Stein Santos; Ewerton Santos; Rosianne P. Silva; Michel R. R. Souza; Luiz A. S. Madureira; Marcelo R. Alexandre (Environmental Science and Pollution Research, 2016)

Chemical composition and anti-inflammatory activity of the leaves of Byrsonima verbascifolia - Aline Aparecida Saldanha; Lucas Fernandes do Carmo; Sara Batista do Nascimento; Natália Alves de Matos; Clarice de Carvalho Veloso; Ana Hortência Fonsêca Castro; Ric C. H. De Vos; André Klein; João Máximo de Siqueira; Carlos Alexandre Carollo; Thalita Vieira do Nascimento; Mônica Cristina Toffoli-Kadri; et al. (Journal of Natural Medicines, 2016)

Guiana Dolphins (Sotalia guianensis) and DR-CALUX for Screening Coastal Brazilian Environments for Dioxins and Related Compounds - Paulo R. Dorneles; José Lailson-Brito; Tatiana L. Bisi; Camila Domit; Lupércio A. Barbosa; Ana C. O. Meirelles; Vitor L. Carvalho; Olaf Malm; Alexandre F. Azevedo; François Brose; Krishna Das; Marie-Louise Scippo (Archives of Environmental Contamination and Toxicology, 2016)

Nitrogen uptake in light versus darkness of the seagrass Zostera noltei : integration with carbon metabolism - Ana Alexandre; João Silva; Rui Santos (Marine Ecology, 2016)
We conducted a study that shows that light and dark conditions do not affect the uptake rates of ammonium and nitrate by the seagrass Zostera noltei . This is an important advantage over some seaweed species in which these rates are severely reduced at night. In the light, the ammonium uptake rates were initially higher (15 and 20 μmol·g −1 ·h −1 ) and stabilized at a rate of 5 μmol·g −1 ·h −1 after 1 h, whereas in the dark the rates remained constant at a rate of 10 μmol·g −1 ·h −1 over the first 180 min of incubation. The rates of nitrate uptake in the light were high within the first 120 min of incubation (7.2–11.1 μmol·g −1 ·h −1 ) and decreased afterwards to lower values (0.8–3.9 μmol·g −1 ·h −1 ), whereas in the dark the rates fluctuated around 0.0–11.1 μmol·g −1 ·h −1 throughout the whole incubation time (7 h). The soluble sugar content of Z. noltei leaves increased significantly with both ammonium and nitrate incubations in the light, indicating the metabolic outcome of photosynthesis. In the dark, there was no significant variation in either the soluble sugar or in the starch content of leaves, rhizomes or roots in either the ammonium or nitrate incubations. However, the total starch content of plants decreased at night whereas the total soluble sugars increased, suggesting a process of starch catabolism to generate energy with the consequent production of smaller monosaccharide products. The starch content of rhizomes decreased significantly during the light incubations with nitrate but not with ammonium. These results suggest that carbohydrate mobilization is necessary for Z. noltei to account for extra energetic costs needed for the uptake and assimilation of nitrate. Furthermore, our results suggest that nitrate uptake, at least during the day, requires the mobilization of starch whereas the uptake of ammonium does not.

Three-dimensional and stereological characterization of the human substantia nigra during aging - Ana Tereza Di Lorenzo Alho; Claudia Kimie Suemoto; Lívia Polichiso; Edilaine Tampellini; Kátia Cristina de Oliveira; Mariana Molina; Glaucia Aparecida Bento Santos; Camila Nascimento; Renata Elaine Paraizo Leite; Renata Eloah de Lucena Ferreti-Rebustini; Alexandre Valotta da Silva; Ricardo Nitrini; et al. (Brain Structure and Function, 2016)

Resource availability influences aggression and response to chemical cues in the Neotropical termite Nasutitermes aff. coxipoensis (Termitidae: Nasutitermitinae) - Paulo F. Cristaldo; Ana P. A. Araújo; Camilla S. Almeida; Nayara G. Cruz; Efrem J. M. Ribeiro; Marcos L. C. Rocha; Alisson S. Santana; Abraão A. Santos; Alexandre Passos; Og De Souza; Daniela F. Florencio (Behavioral Ecology and Sociobiology, 2016)

Climate change in the Iberian Upwelling System: a numerical study using GCM downscaling - Ana Cordeiro Pires; Rita Nolasco; Alfredo Rocha; Alexandre M. Ramos; Jesus Dubert (Climate Dynamics, 2016)

Fate and Analysis of Endocrine-Disrupting Compounds in a Wastewater Treatment Plant in Portugal - Ana Rita Carvalho; Vítor Cardoso; Alexandre Rodrigues; Maria João Benoliel; Elizabeth Duarte (Water, Air, & Soil Pollution, 2016)

Assessment of the toxicity of wastewater from the metalworking industry treated using a conventional physico-chemical process - Rodrigo Matuella Machado; Luiz Olinto Monteggia; Alexandre Arenzon; Ana Cristina Curia (Environmental Monitoring and Assessment, 2016)

Anti-inflammatory Effect and Toxicology Analysis of Oral Delivery Quercetin Nanosized Emulsion in Rats - Gabriela Hädrich; Gustavo Richter Vaz; Michelle Maidana; Jadel Muller Kratz; Gecioni Loch-Neckel; Daniely Cornélio Favarin; Alexandre de Paula Rogerio; Flávio Manoel Rodrigues da Silva; Ana Luiza Muccillo-Baisch; Cristiana Lima Dora (Pharmaceutical Research, 2016)

Barn owl feathers as biomonitors of mercury: sources of variation in sampling procedures - Inês Roque; Rui Lourenço; Ana Marques; João Pedro Coelho; Cláudia Coelho; Eduarda Pereira; João E. Rabaça; Alexandre Roulin (Ecotoxicology, 2016)

Larval hatching and development of the wedge shell (Donax trunculus L.) under increased CO2 in southern Portugal - Alexandre Miguel Pereira; Pedro Range; Ana Campoy; Ana Paula Oliveira; Sandra Joaquim; Domitília Matias; Luís Chícharo; Miguel Baptista Gaspar (Regional Environmental Change, 2016)

Strategy for waste management in the production and application of biosurfactant through surface response methodology - Brunno Ferreira dos Santos; Alexandre Nunes Ponezi; Ana Maria Frattini Fileti (Clean Technologies and Environmental Policy, 2016)

Intake, performance, and carcass characteristics of lambs fed spineless cactus replacing wheat bran - Sabrina Carla Rodrigues Felix; Ricardo Alexandre Silva Pessoa; Marcelo de Andrade Ferreira; Luciana Felizardo Pereira Soares; Janaina de Lima Silva; Karen Santos Felix de Abreu; Ana Caroline Cerqueira de Melo (Tropical Animal Health and Production, 2016)

Influence of verapamil on the pharmacokinetics of oxcarbazepine and of the enantiomers of its 10-hydroxy metabolite in healthy volunteers - Natalícia de Jesus Antunes; Lauro Wichert-Ana; Eduardo Barbosa Coelho; Oscar Della Pasqua; Veriano Alexandre Junior; Osvaldo Massaiti Takayanagui; Eduardo Tozatto; Maria Paula Marques; Vera Lucia Lanchote (European Journal of Clinical Pharmacology, 2016)

Sand smelt ability to cope and recover from CO2-induced ocean acidification stress during early stages assessed through development and biochemical responses - Silva Cátia; Lemos Marco; Lopes Ana; Prasuhn Mareen; Seixas Manuel; Marques Alexandre; Faria Ana; Gonçalves Emanuel; Novais Sara (Frontiers in Marine Science, 2016)

Spatial autocorrelation analysis and ecological niche modelling allows inference of range dynamics driving the population genetic structure of a Neotropical savanna tree - José Alexandre F. Diniz‐Filho; Ana Clara O. F. Barbosa; Rosane G. Collevatti; Lázaro J. Chaves; Levi Carina Terribile; Matheus S. Lima‐Ribeiro; Mariana P. C. Telles (Journal of Biogeography, 2016)
Aim Spatial autocorrelation analysis of genetic diversity was combined with ecological niche modelling ( ENM ) to better infer how ecological and evolutionary processes underlie population structure in Eugenia dysenterica, a widely distributed tree in the ‘Cerrado’ region of Central Brazil. Location ‘Cerrado’ region, Central Brazil. Methods Data were derived from 11 microsatellite loci in 23 populations of E. dysenterica , totalling 249 allele frequencies. The expected heterozygosity ( He ) within populations and the first principal coordinates extracted from pairwise F ST and from the difference between R ST and F ST among populations were correlated with shifts in suitability from ENM . Frequencies were then analysed using a spatial autocorrelation analysis based on Moran's I and Mantel tests to contrast population differentiation for mean allele frequencies, allele size and shifts in suitability since the Last Glacial Maximum inferred from ENM . Results Spatial correlograms based on Moran's I and Mantel tests showed a linear decrease in autocorrelation with distance, which revealed north‐west–south‐east gradients in allele frequencies, genetic diversity and differences between R ST and F ST . These spatial patterns varied among loci and alleles, and the strongest spatial patterns were found for more common alleles with higher levels of differentiation among populations and for those correlated with shifts in ENM suitability. Main conclusions Current genetic diversity and population structure in E. dysenterica can be explained by geographical range shifts associated with Quaternary climate dynamics, thus demonstrating the value of applying spatial analyses to study the ecological and evolutionary processes underlying differentiation even within populations possessing a continuous distribution.

Epiphytes Modulate Posidonia oceanica Photosynthetic Production, Energetic Balance, Antioxidant Mechanisms, and Oxidative Damage - Monya M. Costa; Isabel Barrote; João Silva; Irene Olivé; Ana Alexandre; Sílvia Albano; Rui Santos (Frontiers in Marine Science, 2015)

Biochemical and growth performance of the aquatic macrophyte Azolla filiculoides to sub-chronic exposure to cylindrospermopsin - Catarina Santos; Joana Azevedo; Alexandre Campos; Vitor Vasconcelos; Ana L. Pereira (Ecotoxicology, 2015)

Horizontal study of vaccinia virus infections in an endemic area: epidemiologic, phylogenetic and economic aspects - Felipe L. Assis; Ana Paula M. Franco-Luiz; Luis M. Paim; Graziele P. Oliveira; Alexandre F. Pereira; Gabriel M. F. de Almeida; Leandra B. Figueiredo; Adriano Tanus; Giliane S. Trindade; Paulo P. Ferreira; Erna G. Kroon; Jônatas S. Abrahão (Archives of Virology, 2015)

Inhibition of cyclin-dependent kinase CDK1 by oxindolimine ligands and corresponding copper and zinc complexes - Rodrigo Bernardi Miguel; Philippe Alexandre Divina Petersen; Fernando A. Gonzales-Zubiate; Carla Columbano Oliveira; Naresh Kumar; Rafael Rodrigues do Nascimento; Helena Maria Petrilli; Ana Maria da Costa Ferreira (JBIC Journal of Biological Inorganic Chemistry, 2015)

Experimental characterization of the out-of-plane performance of regular stone masonry walls, including test setups and axial load influence - Tiago Miguel Ferreira; Alexandre A. Costa; António Arêde; Ana Gomes; Aníbal Costa (Bulletin of Earthquake Engineering, 2015)

Dissolved organic nitrogen: A relevant, complementary source of nitrogen for the seagrass Zostera marina - Ana Alexandre; Paul W. Hill; Davey L. Jones; Rui Santos (Limnology and Oceanography, 2015)
Dissolved organic nitrogen (DON) forms a significant pool of bioavailable N in the water column (62%) and in sediments of Ria Formosa lagoon (53%). We assessed the uptake rates of inorganic and organic nitrogen and its interactions in the seagrass Zostera marina , and further explored the possibility of seagrasses to use complex organic substrates (peptides). Uptake rates by leaves and roots were quantified in choice‐uptake experiments where plants were exposed to mixed N solutions containing both 15 N inorganic (ammonium + nitrate) and 13 C 15 N organic (alanine + trialanine) nitrogen at field‐relevant concentrations, and compared with uptake rates of single inorganic or organic N forms. Ammonia was the preferred N source, but plants preferred DON to nitrate. DON uptake was significantly higher through roots than leaves, coinciding with the one‐order of magnitude higher concentration of DON in the sediment than in the water. Not only amino acids, as reported elsewhere for other seagrasses, but also peptides constitute relevant N sources for Z. marina (10% and 4% of the total N uptake). Seagrasses may thus compete with microbes for organic substrates at an earlier stage of protein degradation in the N cycle than previously thought. Because no interactions occurred between inorganic and organic N sources, the total N uptake by Z. marina was higher when both sources were present, showing that organic nitrogen is a complementary rather than alternative source of nitrogen. The uptake of organic nitrogen should be included in future studies assessing the total N budgets of seagrass meadows.

Microscopic and proteomic analysis of Zea mays roots (P30F53 variety) inoculated with Azospirillum brasilense strain FP2 - Alexandro Cézar Faleiro; Pedro Alexandre Valentim Neto; Thaysi Ventura de Souza; Marisa Santos; Ana Carolina Maisonnave Arisi (Journal of Crop Science and Biotechnology, 2015)

Transient expression of rabies virus G-glycoprotein using BHK-21 cells cultured in suspension - Eutimio Gustavo Fernández-Núñez; Alexandre Gonçalves de Rezende; Ana Lia Pradella Puglia; Jaci Leme; Vera Lucia Lopes Boldorini; Celso Pereira Caricati; Aldo Tonso (Biotechnology Letters, 2015)

Mycobacteria species in wild mammals of the Pantanal of central South America - Letícia Alves Gomes Albertti; Antonio Francisco Souza-Filho; Antônio Augusto Fonseca-Júnior; Michele Eduardo Freitas; Aiesca de Oliveira-Pellegrin; Namor Pinheiro Zimmermann; Walfrido Moraes Tomás; Igor Alexandre Hany Fuzeta Schabib Péres; Isabella Fontana; Ana Luiza Alves Rosa Osório (European Journal of Wildlife Research, 2015)

Identification of familial clustering for cancer through the family health strategy program in the municipality of Angra dos Reis, Rio de Janeiro, Brazil - Daniela Koeller Rodrigues Vieira; Margareth Attianezi; Ana Carolina Esposito; Anneliese Barth; Cecília Sequeira; Nathália Krause; Vivian Oliveira; Alexandre Lucidi; Cassio Serao; Juan C. Llerena (Journal of Community Genetics, 2015)

Evaluating a vertical slot fishway in the recolonization of upstream stretch of River Mondego that was not available to sea lamprey - Pereira Esmeralda; Quintella Bernardo; Mateus Catarina; Alexandre Carlos; Cardoso Gabriela; Belo Ana; Telhado Ana; Quadrado Maria; De Almeida Pedro (Frontiers in Marine Science, 2015)

Evaluating potential man-induced changes in fish communities at estuarine and surf-zone areas: a long-term case study in Southern Brasil - Vieira Joao; Lameiro Fábio; Garcia Alexandre; Martins Ana (Frontiers in Marine Science, 2015)

Monitoring anadromous fish populations in a context of habitat fragmentation and commercial exploitation - Cardoso Gabriela; Quintella Bernardo; Mateus Catarina; Alexandre Carlos; Belo Ana; Pereira Esmeralda; Telhado Ana; Quadrado Maria; De Almeida Pedro (Frontiers in Marine Science, 2015)

Tyms double (2R) and triple repeat (3R) confers risk for human oral squamous cell carcinoma - Alexandre Medeiros Bezerra; Thalita Araújo Sant’Ana; Adriana Vieira Gomes; Aurora Karla de Lacerda Vidal; Maria Tereza Cartaxo Muniz (Molecular Biology Reports, 2014)

Germline CDKN2A mutations in Brazilian patients of hereditary cutaneous melanoma - Alexandre Leon Ribeiro de Ávila; Ana Cristina Victorino Krepischi; Luciana Facure Moredo; Talita Ferreira Marques Aguiar; Felipe Carneiro da Silva; Bianca Costa Soares de Sá; Amanda França de Nóbrega; Maria Isabel Waddington Achatz; João Pedreira Duprat; Gilles Landman; Dirce Maria Carraro (Familial Cancer, 2014)

Inorganic nitrogen acquisition by the tropical seagrass H alophila stipulacea - Ana Alexandre; Dimos Georgiou; Rui Santos (Marine Ecology, 2014)
The tropical seagrass H alophila stipulacea is dominant in most regions of the I ndo‐ P acific and the R ed S ea and was introduced into the M editerranean S ea after the opening of the S uez canal. The species is considered invasive in the M editerranean S ea and has been progressively colonizing new areas westward. Growth and photosynthetic responses of H . stipulacea have been described but no information is yet available on the nitrogen nutrition of the species. Here we simultaneously investigated the uptake kinetics of ammonium and nitrate and the internal translocation of incorporated nitrogen in H . stipulacea using 15 N ‐labelled substrates across a range of N i levels (5, 25, 50 and 100 μ m ). The ammonium uptake rates exceeded the nitrate uptake rates 100‐fold, revealing a limited capacity of H . stipulacea to use nitrate as an alternative nitrogen source. The uptake rates of ammonium by leaves and roots were comparable up to 100 μ m 15 NH 4 Cl . At this concentration, the leaf uptake rate was 1.4‐fold higher (6.22 ± 0.70 μmol·g −1 DW h −1 ) than the root uptake rate (4.54 ± 0.28 μmol·g −1 DW h −1 ). The uptake of ammonium followed Michaelis–Menten kinetics, whereas nitrate uptake rates were relatively constant at all nutrient concentrations. The maximum ammonium uptake rate ( V max ) and the half‐saturation constant ( K m ) of leaves (9.79 μmol·g −1 DW h −1 and 57.95 μ m , respectively) were slightly higher than that of roots (6.09 μmol·g −1 DW h −1 and 30.85 μ m , respectively), whereas the affinity coefficients (α = V max /K m ) for ammonium of leaves (0.17) and roots (0.20) were comparable, a characteristic that is unique among seagrass species. No substantial translocation ( 15 N incorporated as ammonium was detected between plant parts, whereas the translocation of 15 N incorporated as nitrate was higher (40–100%). We conclude that the N i acquisition strategy of H . stipulacea , characterized by a similar uptake capacity and efficiency of leaves and roots, favors the geographical expansion potential of the species into areas with variable water‐sediment N levels throughout the M editerranean.

First isolation of Pseudogymnoascus destructans in bats from Portugal - Maria das Neves Paiva-Cardoso; Francisco Morinha; Paulo Barros; Hélia Vale-Gonçalves; Ana Cláudia Coelho; Lisete Fernandes; Paulo Travassos; Ana Sofia Faria; Estela Bastos; Mário Santos; João Alexandre Cabral (European Journal of Wildlife Research, 2014)

Global climate models as forcing for regional ocean modeling: a sensitivity study in the Iberian Basin (Eastern North Atlantic) - Ana Cordeiro Pires; Rita Nolasco; Alfredo Rocha; Alexandre M. Ramos; Jesus Dubert (Climate Dynamics, 2014)

Rainfall stochasticity controls the distribution of invasive crayfish and its impact on amphibian guilds in Mediterranean temporary waters - Carmen Díaz-Paniagua; Claudia Keller; Margarita Florencio; Ana C. Andreu; Alexandre Portheault; Carola Gómez-Rodríguez; Ivan Gomez-Mestre (Hydrobiologia, 2014)

HBV infection in HIV-infected subjects in the state of Piauí, Northeast Brazil - Evaldo H. Oliveira; Roseane M. C. Lima Verde; Luiz Marcelo L. Pinheiro; Marcos G. Benchimol; Ana Luisa E. D. Aragão; José Alexandre R. Lemos; Aldemir B. Oliveira-Filho; Antonio C. R. Vallinoto (Archives of Virology, 2014)

Development of Genomic SSR Markers and Molecular Characterization of Magnaporthe oryzae Isolates from Wheat in Brazil - Jorge Fernando Pereira; Luciano Consoli; Estevon Alexandre de Souza Bombonatto; Ana Lídia Variani Bonato; João Leodato Nunes Maciel (Biochemical Genetics, 2014)

Baccharis trimera (Less.) DC as Genotoxicity Indicator of Exposure to Coal and Emissions from a Thermal Power Plant - Ana Paula Simões Menezes; Juliana Da Silva; Joice Roloff; Juliana Reyes; Rafaela Debastiani; Johnny F. Dias; Paula Rohr; Alexandre de Barros Falcão Ferraz (Archives of Environmental Contamination and Toxicology, 2013)

Effect of Stearic Acid on Enalapril Stability and Dissolution from Multiparticulate Solid Dosage Forms - Talita A. Cunha; Raphael C. Serpa; Ana Paula M. de Oliveira; Letícia N. Nasser; Luis Alexandre P. de Freitas; Stephania F. Taveira; Danielle G. A. Diniz; Eliana M. Lima; Ricardo N. Marreto (AAPS PharmSciTech, 2013)

A steroidal molecule present in the egg wax of the tick R hipicephalus ( B oophilus ) microplus inhibits bacterial biofilms - Karine R. Zimmer; Alexandre J. Macedo; Raquel B. Giordani; Jordan M. Conceição; Gianlucca G. Nicastro; Ana Laura Boechat; Regina L. Baldini; Wolf‐Rainer Abraham; Carlos Termignoni (Environmental Microbiology, 2013)
Summary The cattle tick R hipicephalus ( B oophilus) microplus lays eggs in the soil near the roots of grass, or in similar highly moist environments that are prone to biofilm formation. Tick eggs have a protective wax coating that may be a source of nutrients for microorganisms. However, as the eggs remain viable and show no visible signs of microbial colonization, we hypothesized that the coating might have anti‐biofilm properties. We show here that the coating inhibits biofilm formation by both G ram‐negative and G ram‐positive bacteria, though by different mechanisms. We have identified the anti‐biofilm molecule as N ‐(3‐sulfooxy‐25‐cholest‐5‐en‐26‐oyl)‐ L ‐isoleucine (boophiline), and we show that it inhibits the expression of fliC (flagellin) and cdrA (biofilm scaffold), whose products are necessary for biofilm formation in P seudomonas aeruginosa . Boophiline is a novel biofilm inhibitor being also effective against S taphylococcus epidermidis biofilm. In our study we show evidences of the boophiline mode of action in the protection of arthropod eggs against biofilm colonization.

New insights into the functional morphology of the male copulatory apparatus of bullid gastropods - Ana Amorim; Elsa Oliveira; Manuel António E. Malaquias; Alexandre Lobo-da-Cunha (Zoomorphology, 2013)

NDP-MSH inhibits neutrophil migration through nicotinic and adrenergic receptors in experimental peritonitis - Jozi Figueiredo; Ana Elisa Ferreira; Rangel Leal Silva; Luis Ulloa; Paolo Grieco; Thiago Mattar Cunha; Sérgio Henrique Ferreira; Fernando de Queiróz Cunha; Alexandre Kanashiro (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Tricellulin expression in brain endothelial and neural cells - Cibelle Mariano; Inês Palmela; Pedro Pereira; Adelaide Fernandes; Ana Sofia Falcão; Filipa Lourenço Cardoso; Ana Rita Vaz; Alexandre Rainha Campos; António Gonçalves-Ferreira; Kwang Sik Kim; Dora Brites; Maria Alexandra Brito (Cell and Tissue Research, 2013)

Estimating greenhouse gas emissions from cattle raising in Brazil - Mercedes M. C. Bustamante; Carlos A. Nobre; Roberto Smeraldi; Ana P. D. Aguiar; Luis G. Barioni; Laerte G. Ferreira; Karla Longo; Peter May; Alexandre S. Pinto; Jean P. H. B. Ometto (Climatic Change, 2012)

Salix rubens and Salix triandra Species as Phytoremediators of Soil Contaminated with Petroleum-Derived Hydrocarbons - Ana Cristina Borba da Cunha; Sydney Sabedot; Carlos Hoffmann Sampaio; Claudete Gindri Ramos; Alexandre Rodrigues da Silva (Water, Air, & Soil Pollution, 2012)

Contemporary pollen flow, mating patterns and effective population size inferred from paternity analysis in a small fragmented population of the Neotropical tree Copaifera langsdorffii Desf. (Leguminosae-Caesalpinioideae) - Ricardo O. Manoel; Patrícia F. Alves; Cecília L. Dourado; Ana P. S. C. Gaino; Miguel L. M. Freitas; Mário L. T. Moraes; Alexandre M. Sebbenn (Conservation Genetics, 2012)

Optimizing the location of weather monitoring stations using estimation uncertainty - Ana M. T. Amorim; Alexandre B. Gonçalves; Luís Miguel Nunes; António Jorge Sousa (International Journal of Climatology, 2012)
In this article, we address the problem of planning a network of weather monitoring stations observing average air temperature (AAT). Assuming the network planning scenario as a location problem, an optimization model and an operative methodology are proposed. The model uses the geostatistical uncertainty of estimation and the indicator formalism to consider in the location process a variable demand surface, depending on the spatial arrangement of the stations. This surface is also used to express a spatial representativeness value for each element in the network. It is then possible to locate such a network using optimization techniques, such as the used methods of simulated annealing (SA) and construction heuristics. This new approach was applied in the optimization of the Portuguese network of weather stations monitoring the AAT variable. In this case study, scenarios of reduction in the number of stations were generated and analysed: the uncertainty of estimation was computed, interpreted and applied to model the varying demand surface that is used in the optimization process. Along with the determination of spatial representativeness value of individual stations, SA was used to detect redundancies on the existing network and establish the base for its expansion. Using a greedy algorithm, a new network for monitoring average temperature in the selected study area is proposed and its effectiveness is compared with the current distribution of stations. For this proposed network distribution maps of the uncertainty of estimation and the temperature distribution were created. Copyright © 2011 Royal Meteorological Society

Integrating biogeographical processes and local community assembly - Joaquín Hortal; Paulo De Marco Jr; Ana M. C. Santos; J . Alexandre F. Diniz‐Filho (Journal of Biogeography, 2012)

Keratinases and sulfide from Bacillus subtilis SLC to recycle feather waste - Sabrina Martins Lage Cedrola; Ana Cristina Nogueira de Melo; Ana Maria Mazotto; Ulysses Lins; Russolina Benedeta Zingali; Alexandre Soares Rosado; Raquel S. Peixoto; Alane Beatriz Vermelho (World Journal of Microbiology and Biotechnology, 2012)

SLCO1B1 haplotypes are not associated with atorvastatin-induced myalgia in Brazilian patients with familial hypercholesterolemia - Paulo Caleb Junior Lima Santos; Ana Carolina Moron Gagliardi; Márcio Hiroshi Miname; Ana Paula Chacra; Raul Dias Santos; Jose Eduardo Krieger; Alexandre Costa Pereira (European Journal of Clinical Pharmacology, 2012)

High-fat diet based on dried bovine brain: an effective animal model of dyslipidemia and insulin resistance - Tiago Gomes Araújo; Ana Catarina Rezende Leite; Caíque Silveira Martins da Fonseca; Bruno Melo Carvalho; Alexandre Ricardo Pereira Schuler; Vera Lúcia de Menezes Lima (Journal of Physiology and Biochemistry, 2011)

Plastic Pollution at a Sea Turtle Conservation Area in NE Brazil: Contrasting Developed and Undeveloped Beaches - Juliana Assunção Ivar do Sul; Isaac R. Santos; Ana Cláudia Friedrich; Alexandre Matthiensen; Gilberto Fillmann (Estuaries and Coasts, 2011)

Biodegradation of feather waste by extracellular keratinases and gelatinases from Bacillus spp. - Ana Maria Mazotto; Ana Cristina N. de Melo; Andrew Macrae; Alexandre Soares Rosado; Raquel Peixoto; Sabrina M. L. Cedrola; Sônia Couri; Russolina B. Zingali; Ana Lúcia V. Villa; Leon Rabinovitch; Jeane Q. Chaves; Alane B. Vermelho (World Journal of Microbiology and Biotechnology, 2011)

Understanding the effects of isolation on seed and pollen flow, spatial genetic structure and effective population size of the dioecious tropical tree species Myracrodruon urundeuva - Ana P. S. C. Gaino; Alexandre M. Silva; Marcela A. Moraes; Patrícia F. Alves; Mario L. T. Moraes; Miguel L. M. Freitas; Alexandre M. Sebbenn (Conservation Genetics, 2010)

Effect of ketogenic diet on nucleotide hydrolysis and hepatic enzymes in blood serum of rats in a lithium-pilocarpine-induced status epilepticus - Vanessa Gass da Silveira; Giana de Paula Cognato; Alexandre Pastoris Müller; Fabrício Figueiró; Carla Denise Bonan; Marcos L. Santos Perry; Ana Maria Oliveira Battastini (Metabolic Brain Disease, 2010)

Identification of bacterial protein markers and enolase as a plant response protein in the infection of Olea europaea subsp. europaea by Pseudomonas savastanoi pv. savastanoi - Alexandre Campos; Gonçalo da Costa; Ana Varela Coelho; Pedro Fevereiro (European Journal of Plant Pathology, 2009)

Genetic analysis of a local population of Oryza glumaepatula using SSR markers: implications for management and conservation programs - Ana Rosa de Campos Vaz; Tereza Cristina de Oliveira Borba; Claudio Brondani; Paulo Hideo Nakano Rangel; Graziela Silvia de Oliveira Camargo; Mariana Pires de Campos Telles; José Alexandre Felizola Diniz Filho; Rosana Pereira Vianello Brondani (Genetica, 2009)

Microsatellite diversity and effective population size in a germplasm bank of Hymenaea courbaril var. stilbocarpa (Leguminosae), an endangered tropical tree: recommendations for conservation - Juliana Massimino Feres; Marcela Corbo Guidugli; Moacyr Antonio Mestriner; Alexandre Magno Sebbenn; Ana Yamaguishi Ciampi; Ana Lilia Alzate-Marin (Genetic Resources and Crop Evolution, 2009)

Development and characterization of 15 microsatellite loci for Cariniana estrellensis and transferability to Cariniana legalis, two endangered tropical tree species - Marcela Corbo Guidugli; Tatiana de Campos; Adna Cristina Barbosa de Sousa; Juliana Massimino Feres; Alexandre Magno Sebbenn; Moacyr Antonio Mestriner; Eucleia Primo Betioli Contel; Ana Lilia Alzate-Marin (Conservation Genetics, 2009)

Influence of ketone bodies on oxidative stress parameters in brain of developing rats in vitro - Ana Paula Beskow; Carolina Gonçalves Fernandes; Guilhian Leipnitz; Lucila de Bortoli da Silva; Bianca Seminotti; Alexandre U. Amaral; Angela T. S. Wyse; Clóvis M. D. Wannmacher; Carmen R. Vargas; Carlos S. Dutra-Filho; Moacir Wajner (Metabolic Brain Disease, 2008)

Epidemiological Profile of Cryptococcal Meningitis Patients in Rio Grande do Sul, Brazil - Ana Lusia Leal; Josiane Faganello; Alexandre Meneghello Fuentefria; Juliano Tomazzoni Boldo; Maria Cristina Bassanesi; Marilene H. Vainstein (Mycopathologia, 2008)

Antinociceptive and anti-inflammatory effects of a mucin-binding agglutinin isolated from the red marine alga Hypnea cervicornis - Flávio da S. Bitencourt; Jozi G. Figueiredo; Mário R. L. Mota; Carla C. R. Bezerra; Priscila P. Silvestre; Marcus R. Vale; Kyria S. Nascimento; Alexandre H. Sampaio; Celso S. Nagano; Silvana Saker-Sampaio; Wladimir R. L. Farias; Benildo S. Cavada; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Modulation of branchial ion transport protein expression by salinity in glass eels (Anguilla anguilla L.) - Jonathan Mark Wilson; Alexandre Leitão; Ana Filipa Gonçalves; Catarina Ferreira; Patrick Reis-Santos; Ana-Violeta Fonseca; Joana Moreira da Silva; José Carlos Antunes; Cristina Pereira-Wilson; João Coimbra (Marine Biology, 2007)

Vatairea macrocarpa (Leguminosae) lectin activates cultured macrophages to release chemotactic mediators - Nylane M. N. Alencar; Ana M. S. Assreuy; Alexandre Havt; Raquel G. Benevides; Tales R. de Moura; Romoaldo B. de Sousa; Ronaldo A. Ribeiro; Fernando Q. Cunha; Benildo S. Cavada (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

A promising action of riboflavin as a mediator of leukaemia cell death - Ana Carolina Santos de Souza; Liudmila Kodach; Fernanda R. Gadelha; Carina L. Bos; Alexandre D. Martins Cavagis; Hiroshi Aoyama; Maikel P. Peppelenbosch; Carmen Veríssima Ferreira (Apoptosis, 2006)

Fungal Thyroiditis: An Overview - Luciano Z. Goldani; Alexandre P. Zavascki; Ana Luiza Maia (Mycopathologia, 2006)

Null models and spatial patterns of species richness in South American birds of prey - José Alexandre Felizola Diniz‐Filho; Carlos Eduardo Ramos De Sant'Ana; Márcia Christianne De Souza; Thiago F. L. V. B. Rangel (Ecology Letters, 2002)
In this paper, we used geostatistical approaches to describe bi‐dimensional spatial patterns in species richness of South American birds of prey (Falconiformes and Strigiformes). They indicated strong spatial patterns both across latitude and longitude, for the two groups. These patterns were then correlated with those expected by a bi‐dimensional null model constructed to take into account South America continental edges. As considerable departures from the null model were observed, there may be other ecological or evolutionary explanations for spatial patterns in species richness. Variation seems to be related to habitat heterogeneity across the continent, especially when considering differences between habitats in the central and south‐eastern portion of the continent and in the Andean region. This supports previous conclusions that habitat type and heterogeneity affect species richness and abundance at different spatial scales.

Induction and inhibition of human lymphocyte transformation by the lectin from the red marine alga Amansia multifida - Hermenio C. Lima; Francisco H. F. Costa; Alexandre H. Sampaio; Samya A. Neves; Norma M. B. Benevides; Darlio I. A. Teixeira; David J. Rogers; Ana Lúcia P. Freitas (Journal of Applied Phycology, 1998)